Effects and mechanisms of NMB knockdown on cell proliferation, apoptosis and steroidogenesis in porcine ovarian granulosa cells - Hongxia Li; Guangzhen Chen; Jia Li; Dandan Wang; Sheng Yang; Qi Liu; Fenglei Chen; Zhiyu Ma (Theriogenology, 2026)

Structure-Dominated Deactivation: Unraveling the Multiscale architecture of coke in bio-oil co-cracking - Xianbang Yin; Qi Shen; Mengru Sun; Zhonghao Qu; Xiaoguang Chen; Meiyu Zhang; Mengnan Ma; Zhiyu Zhao; Yunyun Li; Hao Yan; Xiaobo Chen; Yibin Liu; et al. (Fuel, 2026)

Redox-regulated cell death in gastric cancer: Molecular insights and therapeutic opportunities - He Qi; Chenbin Cao; Wenyan Li; Wenshuai Zhu; Yuanxin Xing; Xiaoli Ma; Yunshan Wang; Yanfei Jia (Journal of Physiology and Biochemistry, 2026)

Identification of novel biomarkers and therapeutic targets for type II ketosis in dairy cows through metabolomics and snRNA-Seq - Xue Feng; Qi Feng; Shuang Liu; Lingkai Zhang; Sayed Haidar Abbas Raza; Bei Cai; Yanfen Ma; Fen Li; Yun Ma (Functional & Integrative Genomics, 2026)

Constructing structure-charge dual-regulated nanofiltration membranes via swelling embedding strategy for efficient separation - Ping Li; Yuan Zhou; Chunxi Hai; Wenjie Liu; Ying Cheng; Yu Tang; Yanxia Sun; Shengde Dong; Luxiang Ma; Xin He; Qi Xu (Desalination, 2026)

Constructing Co-O-P bridging to induce spin state reconfiguration: In situ electro-oxidation of P for industrial-scale alkaline water electrolysis - Miao Ma; Chuan-De Qi; Qiao Xia; Qian-Xi Lv; Xin-Jie Tian; Man-Man Li; Sheng-Jun Xu; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2026)

Efficient purification of bio-oil-derived levoglucosenone via a multi-stage synergistic separation strategy - Kai Li; Yong-sheng Ma; Bo Wang; Ding-wang Qiao; Qi Niu; Cheng-long Ruan; Bi-heng Bao; Xin-hua Yuan; Qiang Lu (Biomass and Bioenergy, 2026)

Nitrogen source composition shapes productivity–greenhouse gas trade-offs in saline–alkali rice systems - Xiang Zhang; Yang Liu; Jun Li; Xiaoyu Geng; Yue Jiang; Jizou Zhu; Lulu Wang; Weiyi Ma; Xiaozhou Sheng; Xiaoyong Qi; Yinglong Chen; Pinglei Gao; et al. (Agriculture, Ecosystems & Environment, 2026)

Urbanization drives rapid convergence of riverine greenhouse gas levels in the urban agglomeration, North China - Ling Wen; Zhengkui Ge; Yulin Qi; Dietrich A. Volmer; Chao Ma; Chunmei Chen; Zhifeng Yan; Pingqing Fu; Si-Liang Li (Agriculture, Ecosystems & Environment, 2026)

Chromatin accessibility dynamics reveal regulatory mechanisms of hypoxia tolerance in the Pacific oyster (Crassostrea gigas) - Zhihan Lu; Hongwei Ma; Chenyu Shi; Yitian Bai; Mengmeng Xu; Tianchang Wang; Qi Li; Shikai Liu (Aquaculture, 2026)

Monitoring-constrained GPR inversion reveals profile-scale hydrothermal heterogeneity in a retrogressive thaw slump - Shunshun Qi; Fei Wang; Guoyu Li; Wei Ma; Dun Chen; Fujun Niu; Mingtang Chai; Yougang Yang; Qingsong Du; Kai Gao; Yapeng Cao; Jiawei Yang (Journal of Hydrology, 2026)

The co-ecotoxicity of microplastics and associated contaminants (PFOA) on soil ecosystems - Si-Yu Liu; Feng Han; Li-Qi Ma; Zheng Li; Chun-Ru Qin; Ikram Yaqine; Yi-kai Wang; Jian Su; Jie Chen (Journal of Environmental Chemical Engineering, 2026)

Intrinsic-extrinsic protein complexes as biomimetic interfacial barriers in artificial oil body systems: 1H NMR-guided mechanistic insights into oxidation resistance - Yi Liao; Yu Gao; Lewei Ma; Yukun Pei; Baokun Qi; Yang Li (Food Research International, 2026)

Comparative analysis of composition, volatile compounds, and bioactivities in pomace skins and seeds from different wine grape varieties prior to and following fermentation - Juan-Juan Zhu; Jia-Ning Yan; Xiao-Fang Li; Hao-Hao Zhao; Wen-Qi Wang; Hai-Jun Ma (Food Chemistry, 2026)

Chitosan/indole-3-acetic acid/silver nanoparticle composite films: Preparation, characterization and efficacy in inhibiting postharvest potato dry rot - Hongze Lv; Ke Shi; Chuchu Zhang; Jing Wang; Li Ma; Yi Wu; Hui Ma; Pengfei Zhang; Wenliang Qi; Xiaofeng Niu; Yaoting Guan; Erihemu (Food Chemistry, 2026)

Divergent impacts of microplastics and related leachates on sediment carbon and nitrogen transformation by regulating microbial communities and functions - Wenjuan He; Jinhui Huang; Jinying Hu; Zhexi Liu; Simiao Wang; Yuanyuan Li; Mengyu Ma; Qi Qiao; Lizi Zhao; Lin Shi (Environmental Pollution, 2026)

From traditional observation to intelligent monitoring of estuarine, coastal, and shelf-sea environments: A review - Qi Li; Yongxiang Chi; Weiwei Jiang; Haitian Tang; Qianwen Sun; Deyou Ma; Donghua Zhang; Zhijun Gong (Estuarine, Coastal and Shelf Science, 2026)

Temporal graph convolutional networks with morphological adjacency matrix: microclimate prediction for building energy modeling - Qi Li; Maomao Hu; Rui Ma; Jiayu Chen; Xiaowei Luo (Energy and Buildings, 2026)

BO33− lattice engineering regulates the flexibility of Li+ channels in LiFePO4 for Li+ extraction from Salt Lakes at low temperatures - Xin Zeng; Luxiang Ma; Jiacheng Li; Weiqing Lai; Huifang Li; Chaofei Song; Chunxi Hai; Shengde Dong; Yanxia Sun; Qi Xu; Xin He; Yuan Zhou (Chemical Engineering Journal, 2026)

Cobalt-based carbon catalysts for ultrafast and broad-spectrum degradation of refractory organics via peroxymonosulfate activation - Jiao He; Xiaoli Xiang; Shunxi Li; Qi Ma; Renkun Li; Jin Zhou; Jianshen Feng; Xu Liao; Chenglong Deng; Yulong Li (Chemical Engineering Journal, 2026)

Salinity gradients drive bacterial–fungal divergence through diversity variation, network fragility, and stochastic assembly in saline-alkali soils - Xiaoxuan Ma; Lijuan Chen; Changsheng Li; Jinxia Zhang; Kaiyuan Gan; Qi Feng (Soil Ecology Letters, 2026)

Intracellular imaging and therapeutic application of liver fibrosis via a microRNA-on self-stacking amplification circuit - Xiao-Meng Sun; Yin-Xiang Chen; Lin-Ru Xu; Rui Bai; Li-Zeng Zhu; Gaoxiang Ma; Lian-Wen Qi; Yu Gu; Qun Liu (Analytica Chimica Acta, 2026)

Fe-modified hydroxyapatite with regulated surface properties for enhanced Mn2+ adsorption: Structural evolution and adsorption mechanism - Yike Liu; Qi Zhou; Siwen Lao; Saibo Wang; Feilong Liang; Zhiling Li; Anning Song; Zhen Chen; Wei Ma (Chemosphere, 2026)

Bisphenol A induces osteoporosis by targeting LAMA4 and OLR1: Novel insights into environmental bone toxicity - Zhenyang Wang; Yongqin Chen; Jiling Ma; Yuxuan Yang; Ke Li; Xiejia Jiao; Biteng Xu; Guidong Shi; Liang Wang; Lei Qi (Toxicology, 2026)

Insight into the inhibitory role of rhamnolipid in the adsorption of neonicotinoid pesticides onto biochars - Songting Wang; Bin Wang; Kunyu Wen; Yanbin Ma; Usman Farooq; Zhichong Qi; Taotao Lu; Li Zhang; Shuangcheng Tang (Journal of Contaminant Hydrology, 2026)

Non-targeted metabolomics technology elucidates the metabolic mechanism of flavor formation in Xinjiang's distinctive apricot (Prunus armeniaca L.) varieties - Jian Ma; Peng Li; Yanhong Ma; Zhigang Zhang; Qi Cao; Yadong Xiao; Haihong Wu; Dajing Li; Chunju Liu; Liying Niu (Food Research International, 2026)

CXCL8 is associated with aflatoxin B1–triggered injury and caspase-3 activation in porcine kidney epithelial PK15 cells: integrated transcriptomics and CRISPR/Cas9 knockout - Jianlin Yuan; Yuhan Ma; Jinfeng Li; Xizhu Chen; Yiping Wen; Rui Wu; Xinfeng Hang; Heng Huang; Senyan Du; Yiping Wang; Qi-Gui Yan; Xiaobo Huang; et al. (Food and Chemical Toxicology, 2026)

Weekly thermal-hydrologic activation windows of retrogressive thaw slumps: Implications for early warning of slope instability in degrading permafrost regions - Shunshun Qi; Guoyu Li; Wei Ma; Dun Chen; Fujun Niu; Mingtang Chai; Yougang Yang; Jiawei Yang; Fei Wang; Qingsong Du; Yapeng Cao; Xiaoran Duan (Engineering Geology, 2026)

Cold exposure induced cognitive impairment: A systematic review - Bing-Yao Liu; Xin-Mei Ma; Si-Wei Wang; Qi-Feng Li; Jun-Hua Chen; Sen Li; Hai-Yan Wang; Xiu-Min Lu; Yong-Tang Wang (Cryobiology, 2026)

Construction of low-pressure separation membranes with hierarchically porous structure via cross-linked cyclodextrin polymer modification for efficient dye/salt separation - Jing Yang; Xinyang Li; Zining Guo; Ligang Lin; Wensong Ma; Huiyang Shang; Yue Sun; Mengzhuo Zhang; Hao Wu; Qi Wang; Mengfan Hou; Hongchao Li (Chemical Engineering Journal, 2026)

Redox-sensitive genetic circuits enhance microbial stress tolerance to complex inhibitors in lignocellulose biorefinery - Wen-Tao Wang; Qi Feng; Ting-Ting Li; Muhammad Aamer Mehmood; Hui Zhu; Ning Wang; Yi Ma; Chen-Guang Liu; Feng-Wu Bai (Chemical Engineering Journal, 2026)

Biomass-burning smoke water-soluble organic matter reverses ferrihydrite colloid-inhibited mobility of Cd2+ through saturated porous media via interface fractionation and selective binding - Bin Wang; Nan Yang; Kunyu Wen; ZhiWei Chen; Boyun Zheng; Yanbin Ma; Li Zhang; Zhichong Qi (Chemical Geology, 2026)

Pristimerin disrupts blood-testis barrier (BTB) integrity via ferroptosis and apoptosis by the NUR77/ATF3/CHOP pathway - Jiaqi Li; Haoyu Chen; Zhengxin Lu; Yuanbiao Ma; Shanshan Li; Zhiyu Chen; Zhewen Deng; Qi Zhang; Bo Ma (Chemico-Biological Interactions, 2026)

An experimental investigation on heat transfer in a naturally stratified two-layer melt pool - Mengyi Wang; Fengyang Quan; Wei Li; Jie Pei; Zhenfeng Qi; Qiang Guo; Yidan Yuan; Weimin Ma (Annals of Nuclear Energy, 2026)

Optimized fast desensitized Kalman filter - Tai-shan Lou; Liang Ma; Li-ying Jiang; Yu-zhao Jiao; Liang-Yu Zhao; Ren-long Qi (Advances in Space Research, 2026)

Botany, extraction methods, chemical constituents, pharmacological activities, and food applications of Stauntonia chinensis - Chen-Yu Chang; Xiao-Yun Wang; Ke-Jia Liu; Qi Li; Shu-Yan Lu; Qin-Ge Ma; Rong-Rui Wei (Natural Product Research, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

A new compound from the flowers of Trollius chinensis Bunge and its anti-inflammatory activity by modulating NF-κB signalling pathway - Yu Hong; Yukun Ma; Lebing Zeng; Qingqing Li; Can Liu; Hui Teng; Qi Liu; Tiancheng Ma; Yu Sun (Natural Product Research, 2026)

Erratum to “Sulfur disproportionation in engineered environmental systems: A critical review of mechanisms, applications, and emerging perspectives” [Water Research, Volume 300, 1 August 2026, 125856] - Yu Zhang; Yu-Tong Li; Quan Zhang; Wei Wang; Xue-Ting Wang; Lei Zhao; Ai-jie Wang; Jun Ma; Duu-Jong Lee; Nan-qi Ren; Chuan Chen (Water Research, 2026)

A risk assessment of the environmental and clinical implications of aquaculture-associated, multidrug-resistant Aeromonas veronii - Baili Zheng; Jian Qi; Lan Ma; Cuilan Hao; Xiaofeng Zheng; Yongchao Li; Yaling Cheng; Cheng Yue; Yingyu Liu (Water Research, 2026)

Sulfur disproportionation in engineered environmental systems: A critical review of mechanisms, applications, and emerging perspectives - Yu Zhang; Yu-Tong Li; Quan Zhang; Wei Wang; Xue-Ting Wang; Lei Zhao; Ai-jie Wang; Jun Ma; Duu-Jong Lee; Nan-qi Ren; Chuan Chen (Water Research, 2026)

Big data enabled flavor quality control: Visualized recognition of edible oils via intelligent hardware modules - Xiangning Tang; Fangzheng Zhou; Jiyue Li; Yanxin Lin; Fenghong Huang; Peihua Ma; Qi Zhou (Trends in Food Science & Technology, 2026)

Grain tailoring enables robust high-temperature ferroelectricity in ultrathin Hf1–xZrxO2 films - Haoyu Lu; Yu Li; Liyang Ma; Geng Huangfu; Xuanyu Zhao; Changsong Xu; Hongjun Xiang; Yingfen Wei; Hao Jiang; Qi Liu; Ming Liu (Science Bulletin, 2026)

Corrigendum to “A phospho-switch centered on OsAHL23 orchestrates immune homeostasis in rice” [Sci. Bull. 71(11) (2026), 2701-2705] - Zhaotang Ma; Qi He; Haicheng Liao; Junjie Yin; Xiaobo Zhu; Xiang Lu; Li Song; Long Wang; Hai Qing; Yu Fang; Kangjian Niu; Langqing Chen; et al. (Science Bulletin, 2026)

Ferritin-mediated copper delivery induces dual cell death across diverse leukemia types - Huaiji Wang; Wenjing Wang; Wenqiang Sun; Feifan Liu; Caopei Zheng; Xiaoyun Lin; Yuhua Li; Weier Bao; Xiaoming Hu; Guobin Qi; Feng Li; Guanghui Ma; et al. (Science Bulletin, 2026)

The cytokinin oxidase/dehydrogenase MdCKX4 regulates drought tolerance in Malus domestica - Tong Li; Yu-Feng Zhang; Joy Xin-Yue Zhai; Zi-Quan Feng; Shuo Ma; Xin-Yi Li; Huai-Na Gao; Long-Xin Luo; Zhi Li; Qi Zhang; Min-Min Zhou; Ya-Li Zhang; et al. (Plant Science, 2026)

A multi-objective critical component group identification method based on the NSGA-II-PSO-KCAD optimization algorithm: A case study of an automated container terminal - Shipeng Wang; Haiyan Wang; Yang Li; Wenjing Wang; Fuyou Tan; Guoqing Xue; Xushi Ma; Yang Han; Qi Qin (Ocean Engineering, 2026)

SlCOMT1-dependent melatonin biosynthesis is required for auxin-mediated alleviation of cadmium toxicity in tomato - Zi-Qi Pei; Cheng Ma; Peng Xing; Liang-Hao Li; Xin-Xin Mou; Tong Guo; Lu Wang; Juan Wang; Sheng Zheng; Teng-Guo Zhang (Journal of Plant Physiology, 2026)

A BODIPY-based nanotheranostic suppresses osteosarcoma via dual photodynamic/photothermal action by disruption of YAP1/β-catenin Axis - Zhewen Deng; Mengyuan Zhang; Senqiang Zhu; Yunlong Zhang; Haitao Liao; Jiaqi Li; Peiyu Yan; Qi Zhang; Rui Liu; Bo Ma (Journal of Photochemistry and Photobiology B: Biology, 2026)

Co-exposure to lead and copper induces ferroptosis-related neurotoxicity in zebrafish larvae via oxidative stress and mitochondrial dysfunction - Samra; Rongjian Liu; Xuan Ma; Jiamin Shi; Dongqiong Wei; Lei Yang; Qian Li; Cong Yuan; Yongmei Qi; Yingmei Zhang; Dejun Huang (Journal of Hazardous Materials, 2026)

Three-dimensional configuration engineering of organic materials for sensitive and selective detection of bisphenol A - Xinxue Li; Chuantao Gu; Yu Qi; Lingxia Wu; Yonglin Liu; Pengfei Yang; Zhu-Zhu Sun; Yong Tian; Jiping Ma (Journal of Environmental Chemical Engineering, 2026)

Highly selective photocatalytic degradation of antibiotics enabled by synergistic π-π stacking and Zr-coordination over UiO-66-(COOH)2/ZnCr2O4 - Kaijun Xie; Xianhui Qi; Jinxuan Han; Guozhu Li; Qingling Bai; Rukeyamu Kayisier; Shuaishuai Hu; Yuhua Ma (Journal of Environmental Chemical Engineering, 2026)

Pressure-regulated Fe-Ni/HZSM-5 catalysis promotes selective monocyclic aromatic hydrocarbon production from LDPE/biomass co-pyrolysis - Xiaojie Tian; Qingqing Ma; Nan Zhou; Qi Zhang; Leilei Dai; Xiaoling Ma; Hui Li; Yuan Zeng; Linyao Ke; Qiuhao Wu; Roger Ruan; Yunpu Wang (Journal of Cleaner Production, 2026)

Quantitative climate and elevation reconstruction of the Hezuo Basin in China and its constraints for uplift amplitude of the northeastern Tibetan Plateau across the Oligocene/Miocene boundary - Xiaomiao Li; Yixuan Li; Tingjiang Peng; Huan Yang; Yanning He; Xiaoxue Yue; Qi Zhao; Zhenhua Ma; Chunhui Song (Journal of Asian Earth Sciences, 2026)

Antibacterial activity and mechanism of mangosteen extract garcinone D against Bacillus cereus - Ya-Ya Lei; Guan-Qiu Zhou; Yu-Chen Sun; Jin-Cheng Ma; Fu-Li Liu; Bao-Qi Zhang; Wen Zhang; Li-jing Zhang; Yan-Ze Wang; Ying-Qian Liu (International Journal of Food Microbiology, 2026)

Machine learning-assisted carbon dot sensing for iron speciation in Auricularia auricula soaking solutions under various processing conditions - Jing Mao; Fenghua Li; Yang Ma; Liping Qi; Mingming Yuan; Xin Yuan; Ke Huang (Food Chemistry, 2026)

Nicotine promotes cell proliferation through α5-nAChR/RRM2 axis in lung adenocarcinoma - Jingting Wang; Jingtan Li; Qiang Li; Qi Liu; Jiaying Cai; Zengping Wang; Shuran Yang; Mengdan Yang; Yanfei Jia; Haiji Sun; Xiaoli Ma (Food and Chemical Toxicology, 2026)

Advancing fine-scale ecological restoration in human-impacted mountain foothills through vegetation-informed biotope mapping and Habitat Quality modeling - Danchen Yang; Qi Liu; Denggao Xue; Dongyang Gao; Ling Zhu; Yumeng Ma; Qiang Li; Tian Gao; Ling Qiu (Ecological Engineering, 2026)

Vertical distribution of dust aerosols and transport mechanisms during dust pollution events - Yan Peng; Hongsheng Zhang; Kuifeng Zhao; Chuang Chen; Yuxin Kuang; Yongyong Ma; Chang Liu; Xingmin Li; Yixin Du; Xiaowen Song; Fei Qi (Atmospheric Pollution Research, 2026)

Survey on Dioxin Contamination in Chinese-Produced Pesticides and Evaluation of Dioxin Emissions During their Application - Wei Xie; Ya-chen Zhou; Bin Fang; Hui-li Ma; Na Li; Shu-qi Zhang (Water, Air, & Soil Pollution, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

Seawater mixing as a mechanism to enrich gold ore: Insights from the Ludousou gold deposit (China) - Hao-Cheng Yu; Jun Deng; Kun-Feng Qiu; A. E. Williams-Jones; Ya-Qi Huang; Lian Zhang; Lei Wang; Ke Geng; Xiao-Fei Yu; Deng-Yang He; Jia-Dong Ma; Yong-Sheng Li (Mineralium Deposita, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Biochemical and multi-omics analyses reveal skeletal muscle adaptation to chronic low-salinity stress of marine medaka (Oryzias melastigma) - Tian-Hong Chen; Qing-Hao Zhan; Xiao-Yu Zeng; Ning-Ning Ma; Qi-Liang Li; Run-Jie Jin; Jia-Lang Zheng; Qing-Ling Zhu (Fish Physiology and Biochemistry, 2026)

Chinese AgroMeteorological Model CAMM 2.0–3.0: System Framework, Mechanistic Innovations, and Operational Applications - Yuping Ma; Dingrong Wu; Jianying Yang; Youhao E; Qi Wang; Shuang Sun; Linli Sun; Min Xu; Dianchen Han; Yang Li; Yuanda Zhang; Qianchuan Mi; et al. (Journal of Meteorological Research, 2026)

The gut microbiota mediates the antidepressant effects of imipramine: Evidence from fecal microbiota transplantation and prebiotic inulin intervention - Yonglan Chen; Yuxin Lan; Jingyan Yi; Xiaoyi Qi; Li Liu; Sha Liu; Xinxin Xu; Huan Liu; Yufeng He; Bing He; Xiaochi Ma; Muhan Lü; et al. (Psychopharmacology, 2026)

Integrating Clinical Evidence with PBPK Modeling to Assess PPI-Clopidogrel-CYP2C19 Interactions in Chinese ACS Patients - Ya-xin Liu; Yun Kuang; Jun-long Ma; Jin-long Liu; Nuo Xu; Qi Pei; Li-ying Gong; Guo-ping Yang (Pharmaceutical Research, 2026)

Merbecoviruses exploit APN for entry: expanding the receptor toolkit of betacoronaviruses - Yu Wang; Jie Chen; Wanjie Song; Xin-Xin Li; Xing Ma; Qi Cui; Michael Veit; Andres Merits; Marina Gulyaeva; Ivan Sobolev; Xiaofeng Zhai; Xiaoguang Zhang; et al. (Science China Life Sciences, 2026)

Microplastics Inhibit Microbial Abundance and Enzyme Activities in Pb/Cd Co-contaminated Soil: The Alleviating Role of Biochar - Si-Yu Liu; Feng Han; Li-Qi Ma; Zheng Li; Chun-Ru Qin; Ikram Yaqine (Journal of Soil Science and Plant Nutrition, 2026)

Unraveling the Exosome-Derived ceRNA Network of Cartilage Injury in Kashin-Beck Disease Chondrocytes - Chaowei Wang; Lulu Bai; Liangyu Cui; Pengyan Jiao; Zhouyun Chen; Yang Liu; Yirong Qin; Hui Wang; Lian Liu; Qi Jing; Yuyang Ma; Yuequan Yuan; et al. (Biological Trace Element Research, 2026)

Revised analysis of phosphorus adsorption mechanisms: response to Khim Hoong Chu's comment on our aerogel study. [Water Research 282 (2025) 123709] - Mengting Wu; Xinlong Hua; Zhifei Ma; Yalan Zhang; Wei Liu; Qi Li; Yanyan Zhong; Wenrong Xiong; Yankai Zhou; Xiaohao Guo; Yondong Zhang; Jianjun Dai; et al. (Water Research, 2026)

Mean warming enhances insect resilience to high temperatures: species-specific evidence from two wheat aphids - Xue-Jing Wang; Yu Wang; Shu-Lin Ning; Jia-Qi Li; Biao Cui; Long-Fei Yue; Li-Yan Wang; Chun-Sen Ma (Journal of Insect Physiology, 2026)

Genome-wide interactions with cadmium exposure in dysglycemia: populational effects and molecular insights - Qi Jiang; Bin Li; Yunfei Ma; Wanying Shi; Liang Ding; Naifan Hu; Yunhao Zhao; Yingli Qu; Zheng Li; Peijie Sun; Yifu Lu; Donghui Zhang; et al. (Journal of Hazardous Materials, 2026)

Microbial adaptation and environmental co-selection drive antimicrobial resistance risk in agricultural ditches, evidence from the multilevel ditch-river continuum - Xiangyao Wu; Yulin Qi; Lingchen Meng; Keyan Li; Chao Ma; Dietrich A. Volmer; Chunmei Chen; Peizhe Sun; Pingqing Fu; Zhifeng Yan (Journal of Hazardous Materials, 2026)

Shifting relative importance of vegetation filtering and cold trapping in PCB deposition along a 1000 km transect toward the Qinghai–Tibet Plateau - Chengyou Ma; Yang Ding; Jun Li; Wei Chen; Kaifeng Sun; Huanfang Huang; Shihua Qi (Journal of Hazardous Materials, 2026)

A new pathway to enhance the oceanic carbon sink: inorganic carbonate precipitation driven by calcium–alkali coupling - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Lei Li; Bao Xiao Qu; Qi Dong Wang; Jun Ma; Jian Wei Xing; Zhi Bo Wang; Rui Wang; et al. (Journal of Environmental Management, 2026)

Carbohydrate conversion and microbial community restructuring following Saccharomyces cerevisiae inoculation during Pu-erh tea fermentation - Ruoyu Li; Teng Wang; Qiuyue Chen; Yanhui Guan; Nianguo Bo; Qi Wang; Yiqing Guan; Dihan Yang; Ping Liang; Yan Ma; Tiejun Ling; Ming Zhao (International Journal of Food Microbiology, 2026)

Microbial fermentation modulates flavor formation and quality characteristics of Undaria pinnatifida and Saccharina japonica: Insights from multi-omics and volatile profiling - Yuchen Yang; Huiying Piao; Baijie Wang; Saijie Ma; Runze Li; Liping Leng; Hang Qi (Food Bioscience, 2026)

Cajaninstilbene acid induced apoptosis and cell cycle arrest in glioblastoma multiforme through mitochondrial ROS–mediated MAPK pathways - Yong-Ang Li; Tian-Zeng Bian; Hong Li; Jia-Wen Li; Liu-Tao Ma; Hao-Di Wu; Shuai Chen; Jia-Yi Chen; Hao Zeng; You-Bing Mao; Peng Wang; Qi Qiao (Food and Chemical Toxicology, 2026)

Integrating BEST and structural equation modelling quantifies mechanistic pathways linking ridge-furrow systems with chopped straw to soil hydraulic functioning and sainfoin yield in semi-arid region - Ibrahim Awuku; Abdul Qadeer; Wen Ma; Qi Wang; Xiaole Zhao; Rizwan Azim; Kwame Anokye; Fujia Li; Taoxia Xue; Yonghui Sun; Xuchun Li; Bing Liu (Field Crops Research, 2026)

A layered approach to secure the safety and therapeutic efficacy of hiPSC-derived functionalized neuronal tissueoid for repair after complete spinal cord lnjury in rats - Qing-shuai Wei; Quan-ying Xing; Yuan-huan Ma; Ke-jun Zhang; Wen-tao Ma; Mei-ling Zhang; Hui-juan Shi; Li-zhi Peng; Jun-hua Wang; Qi-xing Hu; Hou-ge Li; Ying Liu; et al. (Chemical Engineering Journal, 2026)

Lithium recovery from clay lithium deposits using ammonium persulfate: Process and mechanism study - Zhixiang Li; Luxiang Ma; Weiqing Lai; Jiacheng Li; Chunxi Hai; Yanxia Sun; Shengde Dong; Xin He; Qi Xu; Yuan Zhou; Xiwei Qin; Yuliang Ma (Chemical Engineering Journal, 2026)

Bio-inspired functionalization of PA1012 into piezoelectric ionomers via molecular asymmetry and ion-cluster polarization - Guangmou Cao; Rong Li; Qi Liang; Jingwen Liu; Pengyuan Luo; Haomeng Ma; Yang Yu; Linyi Cui; Le Xu; Jingjing Ma; Tong Lin; Liuchun Zheng (Chemical Engineering Journal, 2026)

Insights into Fe0, Fe2O3, and Fe3O4–Mediated reduction of antibiotic resistance genes and horizontal gene transfer via reactive oxygen species during composting - Tianhuan Chen; Peng Zhang; Dapeng Xin; Yingchao Zhang; Jun Ma; Qi Chang; Yinqiu Li; Ruxue Wang; Lijun Chen; Hongqiong Zhang (Bioresource Technology, 2026)

Research on microseismic source localization method combining supervised machine learning and 3-dimensional ray tracing method - Qi Ma; Peng Chen; Yunpeng Zhang; Tiancheng Shan; Kailong Qian; Jiahui Du; Xinke Chang; Xue Li; Shanxi Wu (Arabian Journal of Geosciences, 2026)

Nemo-like kinase enhances immunosuppressive activity of CD4+CD25+Foxp3+ Treg cells in eosinophilic chronic rhinosinusitis through phosphorylation-mediated Foxp3 protein stabilization - Ying Wang; Wei Ma; Li Xu; Jie Lu; Bin Zhu; Qi Yan; Bing Guan (Molecular & Cellular Toxicology, 2026)

Dysregulated KIF2A correlates with p53 expression pattern in breast cancer - Yun Hao; Si-Qin Ma; Ting Xu; Jia-Qi Wu; Rong Ma; Ya-Wen Wang; Jian-Li Wang (Molecular and Cellular Biochemistry, 2026)

Life cycle assessment of bottom-sown ark shell (Scapharca subcrenata) aquaculture in Jiaozhou Bay, China: Environmental impacts and carbon balance - Mengyao Liu; Yingkun Cao; Qi Yu; Yuqian Gao; Yao Li; Futang Ma; Meixin Chen; Jianxia Liu; Yujie Liu; Zhe Pan; Xiaotian Gao (Aquaculture, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Orchestrated multicopper heterostructural motifs in MOF enable tandem CO2 valorization via photothermal-photocatalytic C–N coupling - Jian-Qiang Zhao; Hui-Li Zheng; Yu-Jia Cheng; Cheng-Xia Chen; Xiong-Feng Ma; Zheng Yin; Jia-Wei Li; Dong-Dong Ma; Hua Lin; Xin-Tao Wu; Cheng-Yong Su; Qi-Long Zhu (Science Bulletin, 2026)

A phospho-switch centered on OsAHL23 orchestrates immune homeostasis in rice - Zhaotang Ma; Qi He; Haicheng Liao; Junjie Yin; Xiaobo Zhu; Xiang Lu; Li Song; Long Wang; Hai Qing; Yu Fang; Kangjian Niu; Langqing Chen; et al. (Science Bulletin, 2026)

Synthesis, characterization, and antimicrobial properties of 8-Hydroxyquinoline-based group 4 metal complexes for plant pathogen control - Tiankun Zhao; Baoqing Lv; Yinan Ding; Dongyu Mei; Jing Ma; Qi Zhang; Li Zhang; Qipin Qin; Zhongduo Yang; Shanjia Li; Isabel Correia; Hong Liang; et al. (Pesticide Biochemistry and Physiology, 2026)

Undescribed polyketides and alkaloids from the endophytic fungus Penicillium steckii HJT-A-10 - Dongliang Xiao; Xinge Yu; Junkai Qi; Xiaobao Li; Chuan Tang; Baomin Feng; Juan Guo; Xiaoyao Ma; Xuan Lu (Phytochemistry, 2026)

Bioinspired perception: Advancements for underwater robots - Fei Nie; Chuang Zhang; Qi Zhang; Hengshen Qin; Yuyang Li; Yiwei Zhang; Haojie Du; Lianchao Yang; Yue Ma; Lianqing Liu (Ocean Engineering, 2026)

Process-based controls on antibiotic ecological risk in aquaculture systems: Contrasting roles of DOM sources and system openness based on machine learning - Haojing Zhang; Ji Qi; Yan Hao; Huibin Yu; Jingjing Ma; Wei Shi; Qingqian Li (Journal of Environmental Chemical Engineering, 2026)

Deficit irrigation combined with wolfberry-alfalfa intercropping enhances soil carbon sequestration in saline-alkali soils: A soil microenvironment-driven perspective - Yuanbo Jiang; Minhua Yin; Yanxia Kang; Guangping Qi; Yanlin Ma; Yayu Wang; Haiyan Li; Wenjing Yu; Yalin Gao; Jinxi Chen; Jiapeng Zhu; Junxian Chen; et al. (Journal of Cleaner Production, 2026)

Cretaceous high Ba-Sr alkaline magmatism in the East Kunlun Orogen, northern Tibetan plateau: Constraints on lithospheric reactivation and geodynamic process - Zhanqing Ma; Shanzhi Qi; Chengxiang Li; Huajun Wen; Dongdong Yan; Fuhao Xiong (Geochemistry, 2026)

Construction of PtIn@S-1 || hollow H-ZSM-5 composite catalyst for propane aromatization - Zhao Ma; Sen Wang; Shiying Li; Zhikai Li; Han Wang; Qi Li; Baichao Li; Dezhi Shi; Pengfei Wang; Mei Dong; Weibin Fan (Fuel, 2026)

Fresh Portulaca oleracea L. exhibits stronger anti-gastric cancer activity than dried purslane: Insights from integrated metabolomics and machine learning - Tian-Qi Ma; Long-Zhu Li; Zi-Yuan Wang; Geng Li; Yan-Chao Wu; Xin-Yue Li; Hui-Jing Li (Food Bioscience, 2026)

Differential effects of sulfide-induced transformation of biodegradable and conventional microplastics on sedimentary CO2 and CH4 emissions: Underlying microbiome-mediated mechanisms - Jinying Hu; Wenjuan He; Zhexi Liu; Qi Qiao; Lizi Zhao; Yuanyuan Li; Mengyu Ma; Hanbo Yu; Lin Shi; Jinhui Huang (Environmental Research, 2026)

Mechanistic insight into the “intermediate effect”: Competitive adsorption and surface coverage model in controlling hydrate formation in a closed-cell foam–SDS system - Yi-Feng Wang; Zhen-Guo Qi; Zhen Pan; Li-Yan Shang; Zhi-Ming Liu; Jie Liu; Zhuo-Fan Ma; Long-Qi Meng (Chemical Engineering Journal, 2026)

Dynamic modulation of metal active sites via an oxide overlay strategy for selective furfural transformation - Jiang Wu; Ai-Jun Guo; Li-Ying Xie; Xiao-Qi Zhang; Yi-Qiang Qi; Kai Meng; Xiao-Yu Li; He Liu; Shuang-Long Ma (Chemical Engineering Journal, 2026)

Andrographolide induces testicular damage by triggering ferroptosis in Sertoli cells via disruption of β-TrCP-mediated ATF4 ubiquitination and degradation - Jiaqi Li; Zhengxin Lu; Nan Zhang; Xiaowei Zhou; Yuanbiao Ma; Jia-qi Li; Yimu Zhang; Zhewen Deng; Na Lin; Peng Yue; Yilin Yang; Qi Zhang; et al. (Chemico-Biological Interactions, 2026)

Innovative model-optimized machine learning for high-accuracy predicting and exploring nitrogen transformation in biomass pyrolysis - Xinran Zhou; Zhenting Zha; Bowen Li; Rui Diao; Fenglei Qi; Xiaohao Liu; Chengxin Wang; Peiyong Ma (Bioresource Technology, 2026)

Exosomal Protein Biomarkers for Predicting Early Neurological Deterioration Following Intravenous Thrombolysis in Acute Ischemic Stroke - Jiamin Li; Zixin Wang; Yingnan Zhou; Xinyi Wang; Qi Kong; Jiameng Li; Boyi Yuan; Yun Chen; Wan Wang; Jiapeng Zhao; Jinming Sheng; Haiping Zhao; et al. (Translational Stroke Research, 2026)

A Model for Rock Fragment Size Based on Crack Propagation Dynamics - Yanjie Feng; Chengzhi Qi; Xiaoyu Ma; Siyu Wu; Yue Li; Zefan Wang (Rock Mechanics and Rock Engineering, 2026)

PLAUR Exacerbates Neuroinflammation in Diabetic Ischemic Stroke by Driving Neutrophil-Mediated Blood-Brain Barrier Disruption and Reprogramming Microglial Metabolism - Si-qi Ma; Long Wang; Xu Liu; Yi-ning Yue; Si-nian Wang; Yuan Feng; Shuhui Xin; Pu Zhu; Feng-sheng Li; Shi-min Yin (NeuroMolecular Medicine, 2026)

Efficient combined use of electroacupuncture with ordered collagen scaffolds enhances the therapeutic efficacy of human spinal cord-derived neural progenitor cells therapy in spinal cord injury rats - Yunlong Zou; Weiwei Xue; Bo Guo; Lu Li; Yannan Zhao; Xianming Wu; Zhifeng Xiao; Qi Zhang; Dezun Ma; Xinhao Zhao; Bing Chen; He Shen; et al. (Science China Life Sciences, 2026)

Sustainable Chicken Manure Valorization in China: An Integrated Environmental and Economic Assessment - Qi Li; Hanqiao Liu; Guoxia Wei; Hanyang Lu; Qiuyu Yu; Shuo Ma (BioEnergy Research, 2026)

Co-existence of blaCTX-M and mcr-1 in avian pathogenic Escherichia coli in Southern Xinjiang: current status and antimicrobial resistance characteristics - Bin Yang; Guofeng Xing; Wenxuan Ma; Meng Qi; Bo Jing; Jing Li; Jing Wu (Folia Microbiologica, 2026)

Structural equation modelling for sustainable land management: Assessing ridge-furrow rainwater harvesting and chopped straw effects on soil moisture dynamics and sainfoin yield in semi-arid slopes - Ibrahim Awuku; Abdul Qadeer; Xiaole Zhao; Rizwan Azim; Qi Wang; Wen Ma; Fujia Li; Muhammad Ishfaq; Xuchun Li; Bing Liu (Computers and Electronics in Agriculture, 2026)

Tumor-associated bacterial effectors: novel frontiers in tumor biology and immunity - Jia-Hao Dai; Ying-Qi Lu; Sen-Yu Feng; Xi-Rong Tan; Li-Li Li; Yue-Can Zeng; Jian-Zhou Chen; Jun Ma; Na Liu (Science Bulletin, 2026)

Reveal the potential key role of characteristic metabolites of wet glycosylated Pleurotus eryngii protein-Oat β-glucan complex in the process of improving intestinal barrier function-from the perspective of intestinal digestion and microbial fermentation - Qi Tao; Xinyi Li; Yaning Duan; Yunyan Yu; Qiuhui Hu; Ning Ma; Anxiang Su; Chenlu Yang; Gaoxing Ma (Food Bioscience, 2026)

From UAV imagery to mapping: Detecting sunflower heads in fields using a novel lightweight deep learning network - Rui Jing; Qinglin Niu; Qingqing Zhao; Jingcui Shao; Zongpeng Li; Bowei Qi; Guize Chao; Yuanzhi Ma; Dongwei Li; Xinguo Zhou (European Journal of Agronomy, 2026)

Heteroatom bridging chemistries enabling fast polysulfide redox and stable lithium deposition - Guangfeng Zeng; Ruiqing Luo; Yumei Qin; Xue Li; Fangting Xie; Jiajia Wang; Shulong Wang; Jingru Liang; Zhiqi Ma; Duming Wei; Qi-Pin Qin; Xiang-Long Huang (Chemical Engineering Journal, 2026)

Ultrathin Na4Mn3(PO4)2P2O7 and Na4Fe3(PO4)2P2O7 nanoplates with multivacancies defects and short pathway for high rate and long-life Na+ storage - Jixian Ma; Shijie Wang; Miaoning Yao; Chaoguang Kong; Dashan Wu; Zhibin Lei; Ruibin Jiang; Jie Sun; Xuexia He; Nan Zhang; Zong-huai Liu; Qi Li (Chemical Engineering Journal, 2026)

Segmented dynamic photovoltaic shading façade based on kiri-origami: Multi-objective decision-making and interpretable machine learning analysis - Zongxin Qi; Jiaxin Li; Menghui Yu; Qingsong Ma; Dewancker Bart; Weijun Gao (Building and Environment, 2026)

Stability and structure of adaptive plant-pollinator networks under climate change - Liangliang Li; Qi Ma; Min Su (BioSystems, 2026)

Interpopulation Variation in Reproductive Strategies of Leymus chinensis Along Geographical Gradients in Northeast China: From Phenotypic Patterns to Adaptive Mechanisms - Wenwen Qi; Yaxiao Li; Hongyuan Ma; Dandan Zhao; Shaoyang Li; Lingxue Yu; Haitao Wu (Chinese Geographical Science, 2026)

Ablation of FBXO38 triggers lysosome-dependent STING degradation to drive chemotherapy resistance in cervical cancer - Xihua Shen; Qi Liu; Yan Li; Xiaoping Ma; Cengceng Lu; Rongyan Ma; Rui Han; Zhiyi Lin; Hu Han (Apoptosis, 2026)

BECN1-mediated autophagy activates the glycolytic pathway to promote lactate synthesis in Sertoli cells of Tibetan sheep - Xingcai Qi; Yi Wu; Qiao Li; Huihui Wang; Youji Ma (Theriogenology, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Enhanced pollutant removal in multi-pollutants contaminated water by bioaugmented slow filtration - Tingming Ye; Peng Li; Zilong Zhou; Bijing Xiong; Yunpeng Zhao; Jian Zhao; Jing Qi; Baiwen Ma; Yasong Chen (Journal of Hazardous Materials, 2026)

Functional divergence of MdMYB123 and its truncated variant modulates Cd uptake and detoxification in apple - Litong Zheng; Yangyang Yuan; Xun Qi; Jiarui Wang; Shujie Song; Guangya Sha; Haiyan Zhao; Xiaoyu Wei; Lingcheng Zhu; Fengwang Ma; Mingjun Li; Baiquan Ma (Journal of Hazardous Materials, 2026)

Effects of different ecological restoration approaches on soil nitrogen cycling in abandoned mine lands on the alpine plateau - Lili Ma; Wenchao Yan; Fuzhen Jiang; Zhengpeng Li; Mei Han; Zhe Wang; Kaibin Qi (Journal of Environmental Management, 2026)

Multi-point joint prediction of zone-wise arch dam displacements based on spatial partition and deep ensemble selective regression chain - Mingchao Li; Jiamei Ma; Qiubing Ren; Zhiyong Qi; Xuhuang Du; Dawen Tan (Engineering Structures, 2026)

Bioinspired capillary-transport membranes with bubble-guided and gel channels for efficient dye salt separation at ultra-low-pressure - Wensong Ma; Ligang Lin; Hongchao Li; Zining Guo; Jing Yang; Mengfan Hou; Qi Wang; Bingchen Yu; Zhize Yu; Xu Yang (Chemical Engineering Journal, 2026)

From a static 3D scaffold to a dynamic interfacial network: A synergistic binder for silicon anodes under extreme volume change - Mengyu Qi; Li Wang; Sida Huo; Shuzhen Li; Mingguo Ma; Xiangming He (Chemical Engineering Journal, 2026)

Toward energy-efficient recycling of spent LiFePO4 cathode: Lowering reduction temperature though bamboo-assisted pyrolysis and sodium carbonate-mediated in-situ mineralization - Rui Diao; Cunzhang Yang; Liting Fu; Xinran Zhou; Bowen Li; Yakai Ma; Zhenting Zha; Fenglei Qi; Xiaohao Liu; Peiyong Ma (Chemical Engineering Journal, 2026)

Fructan PKP-1b from Polygonatum kingianum attenuates aging and neurodegeneration by inhibiting insulin/IGF-1 signaling - Haitao Guo; Jiahui Wang; Yueying Yuan; Jinchai Qi; Shuqi Li; Heng Chen; Zhixing Huang; Hao Liu; Shaojun Yu; Zekun Yu; Gengyang Liu; Jing Han; et al. (Carbohydrate Polymers, 2026)

Optimizing check dams construction and afforestation for debris flows mitigation in slag and landslides- prone gullies - Liqun Lyu; Guanyu Zhou; Jun Li; Chenyou Hou; Yunqi Wang; Chao Ma; Zihan Qi; Mengzhen Xu; Zhaoyin Wang (CATENA, 2026)

Oxidative stress in frailty among older adults: are malondialdehyde and superoxide dismutase the key biomarkers? - Yuyang Zhang; Jiali Zheng; Xiaoxiao Zhang; Yanwen Zhang; Kexin Zhang; Yujiao Hao; Yang Li; Tingting Ma; Xinyu Bai; Yulu Wang; Yaogang Wang; Qi Lu; et al. (Biogerontology, 2026)

NUFIP1-engineered exosomes modulate propofol-induced neurotoxicity in neonatal rats via the ERS apoptotic pathway - Pengyue Zhao; Yang Yan; Bin Lan; Xingpeng Yang; Yizhao Ma; Yichen Bao; Lin Qi; Xiaohui Du; Songyan Li; Wen Sun (Apoptosis, 2026)

Simultaneous detection of Mycobacterium tuberculosis complex and rifampin/isoniazid resistance with sanity 2.0 MTBC-MDR: a moderate-complexity automated NAAT - Xichao Ou; Bing Zhao; Hui Xia; Xundi Bao; Dongfang Xu; Qi Ma; Ye Xu; Jingjing Li; Wenzhi Shi; Feina Li; Yajie Guo; Ruida Xing; et al. (World Journal of Microbiology and Biotechnology, 2026)

Pseudosparassis yunnanensis, gen. et sp. nov. (Sclerotiniaceae, Helotiales, Ascomycota) from Yunnan Province, Southwestern China - Yuan-Hao Ma; Qi Zhao; Li-Mei Huang; Ping Liu; Hong-Mei Chai; Yong-Chang Zhao; Hong-Li Su; Ishika Bera; Wei-Min Chen (Mycological Progress, 2026)

Structural equation modeling revealed optimized ridge-furrow configuration integrated with straw-soil crust enhancing carbon sequestration and sainfoin yield in semiarid agroecosystems - Abdul Qadeer; Qi Wang; Rizwan Azim; Xiaole Zhao; Wen Ma; Ibrahim Awuku; Fujia Li; Qinglin Liu; Yanping Liu; Bing Liu; Xuchun Li; Muhammad Sanaullah; et al. (Computers and Electronics in Agriculture, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

Experimental and numerical study on local erosion mechanism of flexible elbows under gas-liquid-solid three-phase flow - Pengcheng Li; Chonghe Ma; Jinghua Chen; Yu Wang; Qi Xiang; Jianheng Chen; Xiaoming Luo (Ocean Engineering, 2026)

Magnetic chronology of the late Miocene Wulangou red clay sequences in the northern Otindag Sandy Land - Hongyu Qi; Yali Zhou; Jiangli Pang; Xiaoke Qiang; Jiale Wang; Baofeng Ma; Tong Feng; Xichen Li; Yiting Zhao; Yingying Cui; Liping Jiang; Siying Yue (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Corrigendum to “Multiscale simulation and analysis of coal tar asphaltene nanoaggregation behaviour” [Fuel 407(Part B) (2026) 137317] - Akang Liu; Jiaojiao Liu; Pengju Huo; Sijie Wang; Shudi Han; Xue Ma; Yi Wang; Qi Xin; Mulan Xu; Chongpeng Du; Zengzhi He; Yonghong Zhu; et al. (Fuel, 2026)

Multiscale simulation and analysis of coal tar asphaltene nanoaggregation behavior - Akang Liu; Jiaojiao Liu; Pengju Huo; Sijie Wang; Shudi Han; Xue Ma; Yi Wang; Qi Xin; Mulan Xu; Chongpeng Du; Zengzhi He; Yonghong Zhu; et al. (Fuel, 2026)

A machine learning framework to assess global mangrove forestation potential under current and future climate scenarios - Guohao Li; Yifei Ma; Tianyu Zhuo; Xinyu Qi; Xueyi You (Environmental Research, 2026)

Advanced message encryption, airtightness detection based on high-temperature stimuli-induced dynamic fluorescent color change - Yan Chen; Junhao Li; Rongze Ma; Chunli Zhao; Cang Zhang; Kunpeng Shi; Qi Wang; Yong Yang; Chunjian Wang; Dacheng Zhou; Jianbei Qiu (Chemical Engineering Journal, 2026)

H₂-rich syngas from synergistic steam gasification of biomass with spent LIB cathodes: Catalytic kinetics and metal recovery - Ran Jiao; Lijie Sun; Bowen Li; Xinran Zhou; Yifei Xu; Yu Chen; Fenglei Qi; Xiaohao Liu; Rui Diao; Zhenting Zha; Peiyong Ma (Chemical Engineering Journal, 2026)

Thermosensitive hydrogel with Ganoderma lucidum polysaccharide–ferulic acid nanoparticles and rhEGF for enhanced diabetic wound healing - Fei Li; Tingting Liu; Qi Zhang; Wenbao Wang; Xiaoxing Ma; Rui Ma; Cheng Yuan; Cuiyan Han; Xiaoyu Sui (Chemical Engineering Journal, 2026)

Thawing permafrost under Qinghai-Xizang Highway and its impacts on road performance based on multi-source observed data - Guoyu Li; Mingtang Chai; Wei Ma; Fujun Niu; Dun Chen; Qingsong Du; Yu Zhou; Shunshun Qi; Yapeng Cao; Jianbing Chen; Liyun Tang; Yan Zhang (Cold Regions Science and Technology, 2026)

Combined Straw Return and Organic Fertilizer Increases Soil Quality in Low-SOC Soils: Evidence from a Soil Quality Assessment - Guanjun Li; Zhi Ma; Ze Zhang; Qi Zhao; Chaoyun Ying; Shuang Wang; Liang Wei; Cuiyan Wu (Journal of Soil Science and Plant Nutrition, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Research progress on chemical constituents and biological activities of medicinal plants from Euonymus genus - Ying-Jun Ma; Xin-Ru Li; Meng-Qi Gao; Jia-Jia Liu; Ammara Khalid; Jie-Ting Chen; Fan-Cheng Meng (Natural Product Research, 2026)

Photochemical transformation of dissolved organic matter: source, particulate matter interaction and disinfection byproduct formation potential - Dapeng Guo; Ruochun Zhang; Huiying Ma; Hao Zhang; Zekun Zhang; Yulin Qi; Peizhe Sun; Ding He; Si-Liang Li (Water Research, 2026)

Sediment yield prediction in ridge-furrow rainwater harvesting using coupled USLE–SCS-CN model on the Loess Plateau, China - Ibrahim Awuku; Xiaole Zhao; Rizwan Azim; Qi Wang; Abdul Qadeer; Wen Ma; Xuchun Li; Bing Liu (Soil and Tillage Research, 2026)

Organic chemicals of Arctic concern in Russian coastal seas - Xi-Ze Min; Xianming Zhang; Zhi-Yong Xie; Anatoly Nikolaev; Katrin Vorkamp; Jian-Min Ma; Lars-Otto Reiersen; Li Li; Ming-Hong Cai; Nan-Qi Ren; Yi-Fan Li; Zi-Feng Zhang; et al. (Science Bulletin, 2026)

Bombyx mori RPS3 participates in the UV damage repair of Bombyx mori nucleopolyhedrovirus by interacting with Bm65 - Qi Tang; Jiayin Huang; Qiannan Su; Guohui Li; Feifei Zhu; Qian Yu; Lindan Sun; Huiqing Chen; Liang Chen; Shangshang Ma; Xiaoyong Liu; Keping Chen (Pesticide Biochemistry and Physiology, 2026)

Evolution of the westerlies and the East Asian winter monsoon during the late Miocene and Pliocene - Yan Zhao; Long Ma; Kang-Jun Huang; Yuanqiang Guo; Feng Pan; Ruiming Chen; Jianxing Li; Qi Wang; Jianan Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The sequestration of metal nanoparticles in the liver: A trade-off between density and degradability - Junjie Ma; Li Zeng; Yaquan Liu; Shunhao Wang; Min Li; Linlin Yao; Gang Tang; Ziniu Wang; Jiexia Cheng; Qi Wu; Guangxuan Wang; Chunzhen Shi; et al. (Journal of Environmental Sciences, 2026)

Study of atmospheric radon concentration in a suburban area of Beijing and its correlation with meteorological factors - Shaohang An; Yazhou Niu; Ruiqin Zhang; Mengyao Ma; Shilian Wang; Yungang Zhao; Xinjun Zhang; Shujiang Liu; Qi Li (Journal of Environmental Radioactivity, 2026)

Complex convolutional sparse coding InSAR phase filtering Incorporating directional gradients and second-order difference regularization - Pengcheng Hu; Xu Li; Junhuan Peng; Xu Ma; Yuhan Su; Xiaoman Qi; Xinwei Jiang; Wenwen Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Origin and forming mechanism of coking substance in ester aviation lubricating oil - Teng Chen; Huashuai Gao; Ping Qi; Shizhao Yang; Xin Xu; Jun Ma; Li Guo; Jingpei Cao; Jianqiang Hu (Fuel, 2026)

Physically crosslinked polyphenol-chitosan edible coating for the application of walnut kernels during roasting - Xinhui Wang; Junjun Zhou; Bing Qi; Zhou Chen; Siting Li; Aijin Ma; Yingmin Jia (Food Chemistry, 2026)

Occurrence, drivers, and risk assessment of non-antibiotic pharmaceuticals in urban sewer systems - Fan Meng; Shaojing Sun; Jialu Cheng; Ziyi Wang; Changshun Wang; Jinpan Jiang; Lu Lu; Jingchao Li; Yajie Tian; Lixin Ma; Bo Li; Xiaoyu Feng; et al. (Environmental Pollution, 2026)

Ancient landslide on the Tibet Plateau(China): Reactivation mechanism and post-failure behavior prediction - Ruian Wu; Yongshuang Zhang; Chang Qi; Wenbo Zhao; Xiang Li; Deguang Song; Haishan Ma; Qijun Zou (Engineering Geology, 2026)

Elimination performance of NOx and chlorobenzene over VOx/TiO2-based commercial SCR catalysts at low temperature: Sulfur poisoning and regeneration - Yunfeng Ma; Jiayao Wu; Jianwen Lai; Hongbo Qi; Fanxiang Meng; Bingcheng Lin; Rong Jin; Zhongkang Han; Minghui Zheng; Xiaodong Li; Xiaoqing Lin (Chemical Engineering Journal, 2026)

Corrigendum to “Non-lytic nanozyme hydrogel for the treatment of fungal keratitis by silent pathogen eradication and host inflammation suppression” [Chem. Eng. J. 527 (2026) 171844/ CEJ_171844] - Na Li; Xia Qi; Li Ma; Xiaoyu Zhang; Yuxin Liu; Shijiu Chen; Fengmei Shan; Qun Wang; Qingjun Zhou; Ting Wang; Hongwei Wang; Weiyun Shi (Chemical Engineering Journal, 2026)

A phytoalexin-inspired, natural product-based marine antifouling coating with synergistic active antimicrobial and passive anti-adhesive performances - Liang Ma; Xing-Yu Lei; Qi Xu; Ya-Fu Li; Yu-Hao Li; Peng-Fei Chen; Jian-Cai Chen; Hui-Jing Li; Yan-Chao Wu (Chemical Engineering Journal, 2026)

Pretreatment sequence of torrefaction and leaching for high–alkali biomass valorization: Focus on elemental migration, mineral evolution, carbon structure and torrefaction mechanism - Bowen Li; Junling Du; Rui Diao; Xu Hu; Cunzhang Yang; Ran Jiao; Fenglei Qi; Zhenting Zha; Xiaohao Liu; Peiyong Ma (Bioresource Technology, 2026)

Integrating graphic building group height distribution grids to assess city’s microclimate with wind-direction-dependent deep transfer learning neural networks - Qi Li; Wei Wang; Rui Ma; Jiayu Chen; Xiaowei Luo (Building and Environment, 2026)

Flexible silver nanoflower SERS substrates with optical spot-size matching: Preparation and high-performance detection of veterinary drug residues - Deying Wang; Chunsheng Ren; Junfei Chen; Qi Zhang; Yan Chen; Changhao Li; Yong Jin; Xiaohua Qi; Qiang Ma (Analytica Chimica Acta, 2026)

Determination of reference point for Sheshan SLR telescope using self-driven prism system - Zhikang Wang; Zhibin Zhang; Bin Wang; Shuzhen Yuan; Zhipeng Mei; Xiaohui Ma; Liangquan Jia; Yong Liu; Haifeng Zhang; Si Qin; Li Zhang; Chengli Huang; et al. (Advances in Space Research, 2026)

EBV-miR-BART14-3p Targets LACTB to Enhance Gastric Cancer Cell Proliferation and Migration - Xiaomin Huang; Xuhui Zhao; Yujiao Qi; Tian Lan; Ruiling Wang; Shuang Liang; Yuxiu Ma; Cuixia Di; Hongling Li (Biochemical Genetics, 2026)

Rainfall shapes CO₂ emission and dissolved organic matter dynamics in a karst catchment: Controlling factors revealed by isotopic and molecular signatures - Jinfeng Ge; Yulin Qi; Yuanbi Yi; Chao Ma; Wenrui Yao; Xin Liu; Haoyang Wang; Keyan Li; Fu-Jun Yue; Tao Peng; Si-Liang Li (Water Research, 2026)

Antimicrobial resistance profiling and molecular typing of beta-2 toxin-producing Clostridium perfringens from pig-derived isolates in Xinjiang, China - Wang zekun; Ma wenxuan; Yang Bin; Yu yuetong; Ma zhiyuan; Zhao aiyun; Qi meng; Li jing (Veterinary Microbiology, 2026)

Polymorphisms of XKR4 and ANGPTL4 genes and their association with growth traits in Hu sheep - Qijia Dai; Xiaobin Yang; Qi Zhang; Chengqi Yan; Lianjun Feng; Yukun Zhang; Deyin Zhang; Zongwu Ma; Yanchao Li; Hongmei Hou; Tong Cai; Bo Ma; et al. (Small Ruminant Research, 2026)

Orthogonal-optimized n-doped biochar via microwave pyrolysis for efficient peroxymonosulfate activation and tetracycline hydrochloride degradation - Shihao Xu; Xiaobo Huang; Zhongyu Tao; Li Chen; Yujia Zhang; Xinhong Fu; Haoyu Ma; Yongze Jiang; Jingying Wen; Wenrui Zhou; Cornelis F. de Hoop; Jinqiu Qi; et al. (Process Safety and Environmental Protection, 2026)

Experimental investigation on the motion responses of a moored outfitting ship with and without pontoons under extreme conditions - Zhangjian Wang; Lin Qi; Mingxiao Liang; Junzheng Li; Zihan Liu; Yuxiang Ma; Congfang Ai (Ocean Engineering, 2026)

Autophagy, ROS, and their interplay in plant adaptive responses - Chi Zhang; Song-Qi Li; Pengwei Jing; Run-Xin Wu; Yu-Qing Ma; Ji-Xiao Wu; Ru-Feng Song; Wen-Cheng Liu (Journal of Plant Physiology, 2026)

Mineralogical analysis: The light-induced oxidation driving mechanism of heavy metals in lead-zinc smelting slag - Hanjing Yu; Chenchen Li; Jin Yan; Yaoqiang Ma; Xinyu Zhou; Wanquan Yu; Huiying Kan; Qi Meng; Ruosong Xie; Peng Dong (Journal of Geochemical Exploration, 2026)

From inhibition to enhancement: Time-staged complementary roles of sugarcane bagasse ash and red mud in sustainable cementitious composites - Chaofan Yi; Xingguo Ma; Yuheng Li; Qi Cui; Zheng Chen; Jianhui Liu; Yichen Wang (Journal of Cleaner Production, 2026)

Distinct links between climate warming, mariculture activities, and coastal benthic ecosystem change - Yong Xu; Jixing Sui; Lin Ma; Jinbao Wang; Qi Kou; Zhibin Gan; Lin Gong; Mei Yang; Qingxi Han; Xinzheng Li; Dong Dong (Journal of Environmental Management, 2026)

Preparation of KMnO4 modified N-doped bamboo biochar by microwave pyrolysis for enhancing heavy metals adsorption from aqueous solution - Xiaobo Huang; Shihao Xu; Li Chen; Zhongyu Tao; Haoyu Ma; Yujia Zhang; Xinhong Fu; Jinqiu Qi; Xingyan Huang (Journal of Contaminant Hydrology, 2026)

The role of interfacial protein composition in the stability of soybean oil bodies: Elucidating the mechanism of protein-lipid co-oxidation under different extraction conditions - Yi Liao; Lewei Ma; Yu Gao; Yukun Pei; Baokun Qi; Yang Li (Food Research International, 2026)

Phage-induced inner filter effect powers sensitive dual-mode detection of E. coli O157:H7 - Xiaoyong Ma; Peihao Yuan; Saqlain Ali Bukhari; Weixiao Kong; Liping Yu; Qian Wen; Dong Xu; Wang Li; Qi Chen; Ying Xiong; Jiali Ren (Food Chemistry, 2026)

Facile molten salt synthesis of Co@N-C catalysts enables highly efficient HMF-to-FDCA conversion under mild conditions - Hao-Yue Ma; Jun-Fei Gu; Xing-Chuan Li; Zhan Chen; Qi-Yu Fu; Francis Verpoort; Wen-Jie Mo; Zheng Liu; Cheng Chen; Soon Hyeok Hong; Zongkui Kou (Chemical Engineering Journal, 2026)

Corrigendum to “Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment” [Chem. Eng. J. Volume 515, 1 July 2025, 163509/CEJ-D-25-01484R1] - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2026)

Non-lytic nanozyme hydrogel for the treatment of fungal keratitis by silent pathogen eradication and host inflammation suppression - Na Li; Xia Qi; Li Ma; Xiaoyu Zhang; Yuxin Liu; Shijiu Chen; Fengmei Shan; Qun Wang; Qingjun Zhou; Ting Wang; Hongwei Wang; Weiyun Shi (Chemical Engineering Journal, 2026)

Green and efficient alkaline DES pretreatment for full-component fractionation of reed biomass: Hemicelluloses, uncondensed lignin and easily digestible cellulose - Haozhi Zhang; Qian Sun; Yi-Bing Liu; Cheng-Ye Ma; Jia-Long Wen; Zhenglong Li; Tong-Qi Yuan (Chemical Engineering Journal, 2026)

Injectable piezoelectric nanomicelle hydrogels encapsulating α-tocopherol for the treatment of intervertebral disc degeneration by regulating the metabolic homeostasis of nucleus pulposus cells - Futong Wu; Jiarui Liu; Xiaolin Wu; Hao Li; Nana Shen; Xiaoying Qi; Yuanye Ma; Zhihao Zhang; Zhongze Zhu; Mingyu Gao; Yixiao Chen; Xiaoxiong Wang; et al. (Chemical Engineering Journal, 2026)

Oridonin exposure induces testicular impairment through regulating ferroptosis via HIF-1α/HO-1 activation and STUB1-driven GPX4 ubiquitination-dependent degradation - Zhongchi Xu; Jiaqi Li; Yuyang Hou; Zhewen Deng; Qi Zhang; Bo Ma (Chemico-Biological Interactions, 2026)

Inhalation associated health risk assessment of atmospheric gaseous and size-resolved particulate PAHs in a large temperature range of 50 °C - De-Qi Wang; Shi-Ming Jia; Li-Yan Liu; Chang-Yu Weng; Wan-Li Ma (Atmospheric Pollution Research, 2026)

Experimental and Numerical Research on the Mechanism of Hydraulic Fracture Growth for the Multi-Lithology and Multi-Layered Shale Reservoirs - Wenchao Wang; Xinfang Ma; Yushi Zou; Xingwang Zhu; Shicheng Zhang; Li Liu; Peng Yang; Yin Qi; Xiaojia Xue; Wenbin Chen; Jie Bai (Rock Mechanics and Rock Engineering, 2026)

Unveiling β Subunit-Dependent Gating Defects in CaV2.1 Channelopathies: Investigation of a de novo CACNA1A Variant - Kunpeng Ma; Haiyan Chen; Li Chen; Shuainan Zhao; Huafang Zou; Dongfang Zou; Qi Zeng; Dezhi Cao; Jianyuan Sun; Lin Li; Xuefeng Shen (Neuroscience Bulletin, 2026)

The sesquiterpene lactone components of Cichorium glandulosum suppress both in vitro and in vivo inflammatory responses by reducing IL-1β levels - Xiaoyan Ma; Yang Li; Shuwen Qi; Chunzi Zhang; Juan Zhang; Tuxia Pang; Wenhui Hou; Xiaoli Ma (Inflammopharmacology, 2026)

Survey of hard ticks in high-incidence area of Severe Fever with Thrombocytopenia Syndrome in China - Min Wang; Lei Gong; Yujie Wang; Lesheng Zhang; Fengfeng Wang; Qi Wang; Qingyue Li; Xiaohe Ma; Zhiguo Cao; Jiabing Wu (Experimental and Applied Acarology, 2026)

Multifactorial differential evolution enhanced by adaptive Gaussian-mixture-model-based knowledge transfer - Yan Wang; Guoxing Luo; Xiaodong Li; Lei Wang; Yutao Qi; Xiaoliang Ma (Swarm and Evolutionary Computation, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

The balance application of nano-macronutrients promote growth, productivity and quality through modulation of antioxidative activities in wheat - Mingliang Ding; Lijun Tang; Lin Zhang; Yan Yang; Hongsheng Li; Qi Ma; Shaoxiang Li; Jia Liu; Cuiping Zhang; Kun Liu; Shah Fahad; Sidra Fatima; et al. (Plant Science, 2025)

Wave spectral characteristics of Northern South China Sea during tropical cyclones insights from two different tracks: Nesat and Sarika - Junzheng Li; Yuxiang Ma; Congfang Ai; Yue Liu; Shuxia Bu; Botao Xie; Qi Zhang (Ocean Engineering, 2025)

Simulating and predicting lake dynamics by fusing HBV modeling, machine learning approach and remote sensing data - Muhammad Naeem; Yongqiang Zhang; Ning Ma; Zixuan Tang; Ping Miao; Xiaoqiang Tian; Congcong Li; Qi Huang; Zhenwu Xu; Longhao wang; Zhen Huang (Journal of Hydrology, 2025)

Three-dimensional pore structure characteristics of intact and compacted loess and their controls on hydraulic permeability - Xiaokun Hou; Shengwen Qi; Songfeng Guo; Linxin Zhang; Lina Ma; Yan Li; Yu Wang; Tonglu Li; Jianbing Peng (Journal of Hydrology, 2025)

Identifying conservation gaps and proposing climate-smart strategies for amphibians and reptiles on the Qinghai-Tibet Plateau - Lu-Lu Sui; Zhong-Yi Yao; Shun Ma; Sheng-Chao Shi; Xiu-Dong Shi; Li-Wen Liang; Song Tan; Jie Wang; Bo Cai; Feng Xie; Jing-Feng Chen; Bin Wang; et al. (Journal of Environmental Management, 2025)

Aluminum-modified diatomite efficiently catalyzes the CO2 desorption to achieve low-energy consumption regeneration of amine solution - Pan Li; Xin He; Yanxia Sun; Qi Xu; Shengde Dong; Luxiang Ma; Chunxi Hai; Wenyang Lu; Yuan Zhou (Journal of Environmental Chemical Engineering, 2025)

Split-step Fourier migration of TEM pseudo wavefields via enhanced time-sweep wavefield transformation - Ziyuan Li; Hang Yang; Jie Ma; Zhipeng Qi; Xiu Li; Yanfu Qi (Journal of Applied Geophysics, 2025)

Characterization of peptide-enriched walnut meal paste via microbial diversity and metabolite profiling - Wei Chen; Shuo Zhang; Bing Qi; Siting Li; Zhou Chen; Yiling Tian; Aijing Ma; Yingmin Jia (International Journal of Food Microbiology, 2025)

Phosphorylated eggshell membrane peptides and proanthocyanidin aggregates could be used as emulsion stabilizers: Structural characterization, molecular interactions, and applications in emulsion products - Weiyi Ma; Jingbo Liu; Metta Cita Andriani; Shengrong Dang; Chenman Li; Qi Yang; Ting Zhang; Siwen Lyu (Food Research International, 2025)

Global mangrove natural regeneration potential assessment for identifying carbon potentials of natural regeneration and plantation - Guohao Li; Tianyu Zhuo; Yifei Ma; Xinyu Qi; Xue-yi You (Forest Ecology and Management, 2025)

Beyond waste to bioactive potential: advances in olive by-product valorization and resource recovery - Qi Sun; Meiqi Huang; Jian Zeng; Miaomiao Ma; Jianmei Li; Tao Le (Food Chemistry, 2025)

Structural characterization, functional properties, and antioxidant potential of a novel mannogalactoglucan from Boletus auripes peck - Yucheng Ma; Yu Mao; Li Liu; Banghua Liao; Xufeng Zhang; Xi Jin; Shiqian Qi; Dongxue Yang; Kunjie Wang; Min Zhao (Food Hydrocolloids, 2025)

Efficient lithium extraction from salt lakes brine via regulating the electric double-layer interface of high-loading film electrodes with CMC Li - Yawen Gao; Luxiang Ma; Xin Zeng; Zhixiang Li; Ting Li; Chunxi Hai; Tiandong Chen; Yanxia Sun; Shengde Dong; Xin He; Qi Xu; Xiaowang Wu; et al. (Desalination, 2025)

A lightweight Co1Ni0.5@NC/SiCf filler with excellent low-frequency electromagnetic wave absorption and heat dissipation for electronic packaging - Xingtao Liu; Luyang Li; Qi Cao; Yongjun Huo; Xiulan Wang; Lihong Gao; Zhuang Ma; Gang Zhang; Miao Jiang (Chemical Engineering Journal, 2025)

Preparation of excellent flame retardant system for high-performance triboelectric nanogenerators using electrospinning and two-step coating methods - Qi Liu; Ce Li; Xing-Xiang Ji; Lei Chen; Jia-Qi Lang; Ming-Guo Ma (Chemical Engineering Journal, 2025)

High-brightness, atomic precision gold clusters for three-dimensional visualized pathological monitoring - Shasha Li; Kefeng Jia; Ling Liu; Haoyue Yan; Jiayan Zang; Siyu Ao; Qi Xin; Di Ma; Shibo Li; Shuyu Yang; Xiao-Dong Zhang; Zhidong Wang; et al. (Chemical Engineering Journal, 2025)

Alcohol-assisted efficient hydrodeoxygenation of biomass holocellulose derived furans into branched long-chain alkanes - Song Li; Qiaozhi Ma; Yuhe Liao; Xiangqian Wei; Xinghua Zhang; Lungang Chen; Jianguo Liu; Qi Zhang; Longlong Ma (Chemical Engineering Journal, 2025)

Activating V4+/V5+ redox couple in polyanion lattice engineered Na3.1V2(PO4)2.9(SiO4)0.1-CNT by synergistic ionotronic strategy - Anyang Yu; Qi Fan; Zilong Fang; Tian Jiang; Xinxin Wang; Xiedie Zhao; Xiaoshuang Ma; Pingping Sun; Gang Li; Shijun Yuan; Haiyang Zhang; Yining Wang; et al. (Chemical Engineering Journal, 2025)

Receptor affinity-selective differential dynamics of membrane fusion initiation govern deltacoronavirus cross-species transmission - Da An; Qi Peng; Yong-Hao Ma; Wenguang Hong; Yi Pei; Shiyu Liu; Yan Li; Jizong Li; Yanke Shan; Yulong Yin; Bin Li; Fei Liu (Science China Life Sciences, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

DPP4, a potential tumor biomarker, and tumor therapeutic target: review - Lu Sun; Yuhui Ma; Chenchen Geng; Xiaoqian Gao; Xinbing Li; Qi Ru; Shuzhen Zhu; Ping Zhang (Molecular Biology Reports, 2025)

Prevalence and molecular spectrum of thalassemia in infertile population among different ethnic groups in Hainan Province, China - Yongle Zhang; Jinyu Kang; Wenye Sun; Fei Sun; Ge Gao; Junhong Chen; Qi Li; Qiuling Jie; Yanlin Ma (Molecular Genetics and Genomics, 2025)

Different Intensities of Exercise Affect the Prognosis of Ventricular Aneurysm in Mice by Regulating the Progression of Cardiac Fibrosis - Rui-Qiang Qi; Juan Song; Hong-Bin Ma; Mei-Ling Nie; Liu-Hang Su; Cui-Lian Dai; Fa-Guang Zhou; Sui-Ji Li (Cardiovascular Toxicology, 2025)

Eucommia ulmoides Oliver (Duzhong) extract ameliorates cerebral ischemic stroke in mice by remodeling intestinal microbiota and metabolites - Xin Qi; Mengyuan Deng; Minhong Li; Wenjia Ma; Yangbo Zhou (Metabolic Brain Disease, 2025)

Analysis of APOD and FABP7 genes polymorphisms and their association with feed efficiency in Hu sheep - Ziyue Xiao; Deyin Zhang; YuKun Zhang; Dan Xu; Zongwu Ma; Kunchao Han; Lijuan He; Chengqi Yan; Qi Zhang; Lianjun Feng; Mengru Pu; Lei Gao; et al. (Small Ruminant Research, 2025)

Paleoclimatic evolution since the Late Pleistocene in western Central Asia and its response to mid-latitude westerlies and low-latitude high pressure: insights from aeolian loess-paleosol sections in the Surkhandarya River Basin - Yuzhu Zhang; Jinpeng Zhou; Jian Ma; Shuheng Li; Ninglian Wang; Ulugbek Kholtojiyevich Shapulatov; Yan Zhu; Xinwen Xu; Abdusamad Meligalievich Kurbonov; Qi Liu; Yao Jin; Shukhratjon Boboismoilovich Abdulloev; et al. (Quaternary Science Reviews, 2025)

Selective interaction of BmNPV Bm65 with host proteins before and after ultraviolet radiation - Yutong Liu; Jiayin Huang; Guohui Li; Feifei Zhu; Qian Yu; Lindan Sun; Huiqing Chen; Liang Chen; Qi Ge; Shangshang Ma; Xiaoyong Liu; Keping Chen; et al. (Pesticide Biochemistry and Physiology, 2025)

Prediction of shoreline wave setup on beaches using artificial neural networks - Chao Ji; Qi Jiang; Dianguang Ma; Kun Chen; Xuefang Li; Jianmin Xiao; Jing Lu; Qinghe Zhang (Ocean Engineering, 2025)

Evaluation of multimodel averaging approaches for ensembling evapotranspiration and yield simulations from maize models - Viveka Nand; Zhiming Qi; Liwang Ma; Matthew J. Helmers; Chandra A. Madramootoo; Ward N. Smith; Tiequan Zhang; Tobias K.D. Weber; Elizabeth Pattey; Ziwei Li; Jiaxin Wang; Virginia L. Jin; et al. (Journal of Hydrology, 2025)

Machine learning-enhanced prediction of size-resolved gas-particle partitioning quotient: Implication for health risk assessment of polycyclic aromatic hydrocarbons - De-Qi Wang; Wan-Li Ma; Ru-Peng Wang; Pu-Fei Yang; Peng-Tuan Hu; Shi-Ming Jia; Meng Qin (Journal of Hazardous Materials, 2025)

One fell swoop strategy to detect and degrade malathion by an ALP-sensitive and Pt-Co-N-C nanozyme-enhanced chemiluminescent 3D μPAD - Yang Chen; Qi Zhang; Ruiqing Ke; Tianyi Ma; Kunlun Huang; Yunbo Luo; Jin-Cheng Li; Nan Cheng (Food Chemistry, 2025)

Limosilactobacillus fermentum MQ10 reduces decay of sweet cherry during storage by altering surface microbiome and enhancing phenylpropane metabolism - Runtong Chen; MingQing Zhang; Diyan Wu; Xiao Ma; Qi Zhao; Xin Li; Di Gong; Ying Zhang (Food Control, 2025)

A Gastrodia elata green tea pulsed light sterilization model based on cost-benefit and GA-SVR algorithm - Mei Li; Xindi Jin; Wanlu Ma; Sining Du; Yunhui Wang; Zhifan Ji; Henglin Qi; Xubo Zhao (Food Control, 2025)

The impact of combining differentiated carbon tax and emissions trading system on the construction sector: Based on the industry linkage perspective - Qiang Du; Qi Li; Cheng Lu; Meixin Ma; Libiao Bai (Energy and Buildings, 2025)

Railway geohazards: global perspectives on modes, risks, and mitigation strategies - Dengfei Zhang; Jiading Wang; Tianfeng Gu; Qi Gu; Zexin Yang; Shixiong Li; Hanjiang Chen; Zhijia Li; Weiqian Ma; Chenxing Wang (Engineering Geology, 2025)

Synergistic Mn-doping and MXene coupling in sulfur-deficient In2S3 nanosheets for high-performance sodium-ion batteries - Manman Zhang; Qi An; Haocun Ba; Boxi Wang; Beibei Li; Chengjiang Deng; Liuyuan Ma; Yinghong Lan; Xiaoyan Han; Shaozhuan Huang (Chemical Engineering Journal, 2025)

Stimuli-responsive polymeric nanoplatform-mediating immune microenvironment remodeling and noggin silencing for osteogenic regeneration - Yongcan Li; Kaiyuan Cheng; Xinyang Yu; Kai Yang; Jiaqi Lei; Wenjie Zhang; Yangfan Wang; Yunxuan Feng; Shaolong Qi; Jinqun Gan; Zhengwei Mao; Xieyuan Jiang; et al. (Chemical Engineering Journal, 2025)

Machine learning-guided discovery and stabilization of anomalous Ni4+ oxides with superior electrocatalysis for flow batteries - Jia-Qi Liu; Deng-Hua Zhang; Li-Xin Yang; Fang Liu; Tong-Tong Shi; Yu-Jia Wang; Yun-Long Tang; Yin-Lian Zhu; Xiu-Liang Ma (Chemical Engineering Journal, 2025)

Ethylene-responsive factor HvERF72 regulates starch synthesis and B-type starch granules initiation in barley - Gaozong Zhou; Jinjin Ding; Yulong Li; Qiang Xu; Yazhou Zhang; Huaping Tang; Pengfei Qi; Mei Deng; Jian Ma; Guoyue Chen; Jirui Wang; Na Lin; et al. (Carbohydrate Polymers, 2025)

Pollution characteristic and temporal trend of PM2.5-bound heavy metals in a megacity of Northeast China: Implication for the effect of air pollution control policy - Jin-Wen He; Li-Yan Liu; Chang-Yu Weng; De-Qi Wang; Shi-Ming Jia; Wan-Li Ma (Atmospheric Pollution Research, 2025)

Expression of LGALS3 and XPNPEP2 genes and their association with growth traits in sheep - Guoxing Jia; Weimin Wang; Huibing Tian; Xiaojuan Wang; Yukun Zhang; Yuan Zhao; Lijuan He; Zongwu Ma; Xioabing Yang; Dan Xu; Kunchao Han; Peiliang Cao; et al. (Tropical Animal Health and Production, 2025)

Effects of organic fertilizers on apple growth and drought resistance, soil properties and microbial diversity: a comparison of mature organic fertilizers and weathered coal organic fertilizers - Qian Li; Suixia Lang; Xiaobing Ma; Lizhi Liu; Qi Zhao; Chunzhen Cheng; Lei Li (Plant and Soil, 2025)

Suitable ridge width and straw length for alfalfa production under ridge-furrow rainwater harvesting compacted with chopped straw-soil crust in semiarid regions - Rizwan Azim; Qi Wang; Xuchun Li; Abdul Qadeer; Xiaole Zhao; Ibrahim Awuku; Wen Ma; Qinglin Liu; Yanping Liu; Bing Liu (Plant and Soil, 2025)

Understanding the role of GhRCC1.61 in flowering time in upland cotton through integrated analyses of gene family, RNA-seq, VIGS and allelic variation - Junning Yang; Xufeng Guo; Wenmin Yuan; Ying Li; Dandan Li; Xueli Zhang; Qi Ma; Tingting Zhang; Caixiang Wang; Junji Su (Plant Cell Reports, 2025)

SnRNA-seq Interprets Mechanisms by which Three Glial Cell Types Influence Myelin Regeneration in Adult Drug-Resistant Epilepsy-Related Cognitive Impairment - Lu Wang; Jia-Qi Ma; Yong-Qian Bian; Xiao-Peng Qu; Yue Zhang; Chao Wang; Guo-Dong Gao; Long-Long Zheng; Qi-Xing Fang; Li-Jia Song; Liang-Liang Shen; Bei Liu (Molecular Neurobiology, 2025)
Myelin regeneration has been shown in previous studies to ameliorate varying degrees of cognitive impairment in patients with neurodegenerative disorders such as epilepsy. The problem of myelin regeneration in adults with drug-resistant status epilepticus is a major key to the difficulty of treating cognitive impairment in adults with drug-resistant epilepsy (DRE). The purpose of this study is to provide a molecular map of myelin-related molecules under the cognitive deficits seen in DRE. We used a lamotrigine-pentylenetetrazol-resistant epilepsy mouse model and verified the cognitive problems and myelin changes using a water maze and conventional molecular biology techniques. We then analyzed the OLs in the hippocampus of the mice and the effect on myelin using sn RNA-seq technology. We found that the problem of cognitive impairment in drug-resistant epileptic mice is due to altered myelin plasticity. OL maturation induces pathological myelin regeneration which ultimately leads to cognitive impairment. The three glial cell types are closely related to the occurrence of myelin regeneration and jointly promote pathological myelin regeneration. Our study revealed the presence of myelin regeneration in DRE. All of this evidence suggests that normal myelin regeneration contributes to cognitive impairment improvement, but pathological myelin regeneration impairs cognition. Graphical Abstract Schematic representation of myelin regeneration in cognitive impairment in adult drug-resistant epilepsy. Boxed are pathways or molecules related to the promotion of myelin regeneration in which a subpopulation is involved. Red font indicates promotion, blue font indicates inhibition, and gray font indicates unknown but relevant.

Role of gene PA2798 on biofilm formation and virulence factors production of Pseudomonas aeruginosa - Hai-Lin Li; Li Chen; Zhi-Wen Ma; Jing Yan; Xiao-Ling Lu; Hao Nie; Qi Yin; Ying-Li Li (Folia Microbiologica, 2025)

High-throughput processing of microplastics based on Z-type radial flow separator: Fluid flow characteristics - Qi Wei; Hongpeng Ma; Wanting Feng; Jun Ding; Peng Yang; Ao Li; Danhui Yang; Wenjie Lv; Hualin Wang (Journal of Hazardous Materials, 2025)

Deciphering intrakingdom synergism in 17β-estradiol degradation through DNA-SIP coupled metagenomics: Metabolic cooperation and niche partitioning in bioaugmented soil microbiomes - Lei Miao; Tian Ma; Jiaxi Qi; Yaohui Deng; Yaqi Hong; Xiaoxiao Gong; Hailian Zang; Yi Cheng; Chunyan Li (Journal of Hazardous Materials, 2025)

Sustainable nutrients removal from low-strength wastewater: A comprehensive review of biofiltration for resource recovery and carbon neutrality - Chengde Sun; Guangyi Ma; Bin Qi; Kun Wu; Tao Zhang; Yong Hu; Chao Rong; Dapeng Li; Yu-You Li; Zhe Kong (Journal of Environmental Chemical Engineering, 2025)

Synergistic nitrogen removal through sulfate reduction and sulfur autotrophic denitrification driven by sustained-release carbon source in sulfate-rich wastewater - Zaixing Li; Sijie Yin; Qi Liu; Yanfang Liu; Xiaoshuai Liu; Xuejiao Ma; Nannan Wang; Yanhe Han (Journal of Environmental Chemical Engineering, 2025)

Synergistic regulatory mechanisms of plant hormone combinations on the growth and lipid accumulation of Chlorella pyrenoidosa in saline wastewater - Qiao-Ling Zhao; Kai-Yuan Li; Jia-Qi Xi; Jin-Long Zhou; Dan-Ni Miao; Zeng-Ling Ma; Ying Zhang; Hai-Jun Luo; Feng Gao (Journal of Environmental Chemical Engineering, 2025)

Enhancing biomass productivity and parabens degradation in microalgae using organic carbon sources: Co-metabolism mechanisms and transcriptomic insights - Jing Yang; Zhihong Yin; Yuhong Li; Lei Tian; Qi Wang; Hanglong Ma; Juan Zhou; Mingshi Zhu; Shaoqi Zhou (Journal of Environmental Chemical Engineering, 2025)

Nitrogen addition decouples the microbial necro-mass from soil organic carbon formation in a temperate grassland - Huanhuan Cheng; Yingbin Li; Shuo Li; Tianran Sun; Guoxiang Niu; Qi Li; Junjie Yang; Yanxia Ma; Yingzhi Gao; Qiang Yu; Haitao Zhao; Qiushi Ning; et al. (Journal of Environmental Sciences, 2025)

Exploring oleosin allergenicity: Structural insights, diagnostic challenges, and advances in purification and solubilization - Yi Liao; Yu Gao; Lewei Ma; Yukun Pei; Baokun Qi; Yang Li (Food Chemistry, 2025)

Cosolvent-modulated polyamide nanostructures enable precise Mg2+/Li+ separation for lithium recovery from brines - Ping Li; Yuan Zhou; Chunxi Hai; Ying Cheng; Yu Tang; Yanxia Sun; Shengde Dong; Luxiang Ma; Xin He; Qi Xu (Desalination, 2025)

Heat conduction and fracture mechanism of jointed granite: Insight from a fully coupled Thermo-Mechanical DEM model - Jian Ma; Zheng-Wei Li; Hai-Xi Wang; Jia-Qi Song; Ming-Yu Zhang (Computers and Geotechnics, 2025)

Synergistic catalysis of CuxFey/CeO2 bimetallic catalysts for oxidative dehydrogenation of C2H6 with CO2 - Dan Guo; Zouxuan Qi; Zelong Fu; Zhenli Lv; Li Kang; Feigang Zhao; Tongrui Wan; Shengping Wang; Xinbin Ma (Chemical Engineering Journal, 2025)

Cellulose nanofiber/boron nitride/MXene ternary composite films with excellent thermal conductivity for high output triboelectric nanogenerators under high temperature - Jia-Qi Lang; Ce Li; Lei Chen; Qi Liu; Wei Wan; Hai-Yan Yang; Ming-Guo Ma (Chemical Engineering Journal, 2025)

One-pot synthesis of injectable freeze-dried platelet lysate functionalized peptides hydrogel for pressure ulcers repair - Kun Liu; Lei Wang; Dongdong Li; Fengying Qi; Shaoduo Yan; Xiaoyang Yi; Yanhong Li; Yuyuan Ma; Xian Su; Yuxin Zhang; Xunuo Li; Ruotong Zhang; et al. (Chemical Engineering Journal, 2025)

Enhanced CO2 capture efficiency via catalytic Fe2O3-modified multi-walled carbon nanotubes in monoethanolamine - Lingling Li; Xin He; Pan Li; Xiaoqin Li; Yanxia Sun; Qi Xu; Shengde Dong; Luxiang Ma; Chunxi Hai; Maohong Fan; Yuan Zhou (Chemical Engineering Journal, 2025)

Divergent drivers of litter decomposition in karst and non-karst tropical rainforests: a comparison - Qi Liu; Xinli Chen; Fuzhao Huang; Jianxing Li; Ting Chen; Fang Lu; Xiankun Li; Dongxing Li; Wusheng Xiang; Bin Wang; Hongming Zhao; Ruixia Ma; et al. (CATENA, 2025)

Biological Functions of Growth Differentiation Factor 9 in Early Ovarian Development of Japanese Eel (Anguilla japonica) - Chenpeng Zuo; Xulei Wang; Xuanhan Zhang; Xiaojie Wang; Likang Lyu; Teng Ma; Lingming Chen; Weimin Yu; Yun Li; Haishen Wen; Xin Qi (Marine Biotechnology, 2025)

Molecular characterization of porcine reproductive and respiratory syndrome virus in Henan and Shanxi, China, during 2023–2024 - Tao Wang; Xuan-Ang Wang; Jia-Qi Zhang; Lan-Lan Zheng; Ping-Li Wang; Hong-Ying Chen; Shi-Jie Ma (Archives of Virology, 2025)

Eucommia ulmoides (Duzhong) extract alleviates cerebral stroke by inhibiting ferroptosis-related gene DNA Damage-Inducible Transcript 4 (DDIT4) expression - Xin Qi; Mengyuan Deng; Minhong Li; Wenjia Ma; Yangbo Zhou (Human Cell, 2025)

San-Huang-San reduces the effects of enteritis infection caused by Aeromonas sobria in common carp by modulating oxidative stress and the inflammatory response - Huawei Feng; Yuying Zhang; Shan Zhao; Yongzhen Wang; Yu Hu; Sai Zhang; Xiang Qi; Sixu Luo; Jian Zhao; Xiangming Ma; Hui Zhang; Li Zhang; et al. (Aquaculture, 2025)

Study on the antioxidant defense of Pacific oysters (Crassostrea gigas) against sulfonamide antibiotics - Hao Chen; Liping You; Jing Sun; Hao Yu; Wei Sun; Changlin Song; Bo Su; Chenglong Ji; Lin Ye; Shujun Li; Yanmin Qi; Yuanqing Ma (Aquaculture, 2025)

A multi-posture adaptive method for measuring goat bodies dimensions using 3D point clouds in real-world applications - Yi Sun; Qifeng Li; Weihong Ma; Daniel Morris; Hao Guo; Xiangyu Qi; Mingyu Li; Chunjiang Zhao (Biosystems Engineering, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Pre-spraying nitrogen-doped carbon dots prior to stress enhance rice tolerance by improving metabolism, antioxidant, and cell wall - Yadong Li; Ronghua Xu; Jingyi Qi; Shang Lei; Qianying Han; Congli Ma; Hongjie Wang (Pesticide Biochemistry and Physiology, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Characteristics of high-purity quartz raw materials for crucibles and exploration of key purification technologies - Yameng Ma; Jianguo Li; Zhichao Wu; Haiqi Zhang; Xiumin Tan; Yuejun Yi; Qi Tan; Lei Liu (Minerals Engineering, 2025)

Human exposure to organophosphate esters (OPEs): A meta-analytic review of levels and distribution - Wenjun Li; Yunyan Liu; Qi Song; Qiao Zeng; Junlong Chen; Ruotong Ma; Xianggui Chen; Bing Shao; Lijun Wang; Zhongfan Wang (Journal of Hazardous Materials, 2025)

Enrofloxacin drives the ultra-selective enrichment of Ca. Kuenenia stuttgartiensis under microaerobic conditions - Jiaqi Zhang; Hao Zhang; Zhenyi Ma; Lin Zhou; Qi Zhang; Quan Zhang; Chuan Chen; Rong Li; Xiao-Ming Ji (Journal of Hazardous Materials, 2025)

Identifying nitrate pollution of groundwater based on aquifer vulnerability and surface nitrogen loads in the Northern Foot of the Qinling Mountains, China - Yixin Liu; Hui Qian; Yanyan Gao; Siqi Li; Xiaoxin Shi; Zhiming Cao; Qi Long; Yi He; Yandong Ma; Puxia Wu; Yanjun Shen (Journal of Hazardous Materials, 2025)

Using ventilation hood during cooking reduced household air pollution exposure and brought cardiometabolic and pulmonary health benefits: A community-based, cluster-randomized controlled intervention study - Yueru Yang; Kuai Yu; Wending Li; Xuedan Xu; Chengyong Jia; Qi Yan; Xingxing Li; Hao Cai; Denghuan Hu; Hui Gao; Xuanwen Mu; Yuhui Lin; et al. (Journal of Hazardous Materials, 2025)

Effects of Fe2O3 nanoparticles on lignocellulose bio-oxidation and heat production during aerobic fermentation of corn stover - Yongna Cao; Wei He; Hongru Shang; Yinxue Li; Yuhang Zhu; Qi Shen; Shiguang Jin; Zenghui Ma; Yanling Yu (Journal of Environmental Management, 2025)

Application of ground-airborne transient electromagnetic method with layered Green's function born approximation imaging in the Huang-ling coal mine goaf - Jie Ma; Ziyuan Li; Xiu Li; Zhipeng Qi; Qiding Wang (Journal of Applied Geophysics, 2025)

Machine learning-based retrieval of chlorophyll-a and total suspended matter from HY-3A CZI: Model development, validation, and application - Lan Zhang; Chen Zhang; Chaofei Ma; Xi Chen; Qi Li; Xiaomin Ye; Zhifeng Yu; Liqiao Tian (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Influence of the strain rate on the deformation and failure of rocks with multiscale cracks - Yan-jie Feng; Cheng-zhi Qi; Fa Zhao; Tao Li; An-sen Gao; Xiao-yu Ma (Geomechanics for Energy and the Environment, 2025)

Recent progress in two-dimensional materials: From emerging structures and synthesis approaches to electronic and sensing applications - Jing Hao Zhuang; Zhong Li; Yi Liang; Tao Tang; Xin Yi Hu; Rui Ou; Qi Jie Ma; Bao Yue Zhang; Yin Fen Cheng; Wen Lin Feng; Jian Zhen Ou (Chemical Engineering Journal, 2025)

Nature-Inspired cell membrane-coated artificial biocatalysts with Os-single-atom sites and multienzyme-Mimetic activities for targeted tumor therapy - Jiawei Wang; Jing Wu; Zijun Ma; Xin Xie; Lu Zhao; Xiao Luo; Wenjun Liu; Bo Ren; Qi Li; Ling Li; Shengdong Mu (Chemical Engineering Journal, 2025)

Unraveling the role of phosphorus on V2O5-WO3-CeO2/TiO2 catalysts: Mechanisms for enhanced NH3-SCR and water resistance - Hongbo Qi; Jianwen Lai; Qiong Yuan; Yunfeng Ma; Yichao Qian; Zhongkang Han; Xiaoqing Lin; Xiaodong Li (Chemical Engineering Journal, 2025)

Unlocking bio-H2 production potential from straw–sludge co-substrates: The role of Fe/Mn-biochar in alleviating carbon catabolite repression - Ji-wen Wu; Shi-jie You; Chun-shuang Zhou; Qi Xi; Jia-ning Fan; Jun Ma; Guang-li Cao (Chemical Engineering Journal, 2025)

Genome-wide association study reveals novel SNP loci and candidate genes linked to flowering time in upland cotton - Xuefeng Guo; Junning Yang; Dandan Li; Xueli Zhang; Wenmin Yuan; Ying Li; Fuxiang Wang; Qi Ma; Caixiang Wang; Junji Su (Theoretical and Applied Genetics, 2025)

Insight into the rutin biosynthesis in the unique flavonol synthesis pathway of Tartary buckwheat based on the enzymatic functions of FLSs - Chenglei Li; Jiayi Sun; Guanlan Shi; Xuerong Zhao; Jun Gu; Jiaqi Shi; Qihan Ma; Daoping Zeng; Tao Wang; Zizhong Tang; Tongliang Bu; Hui Chen; et al. (Theoretical and Applied Genetics, 2025)

Protective effects of berberine on MASLD: regulation of glucose and lipid metabolism through PI3K/Akt and STING pathways - Jing Ji; Ying Li; Tian Xu; Qi Shao; Zijin Sun; Simin Chen; Di Zhang; Qingguo Wang; Xueqian Wang; Chongyang Ma; Fafeng Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

IQGAP1 participates in bone marrow-derived macrophage recruitment and involves in liver inflammation/fibrosis - Na Chang; Yuehan Ma; Jing Liu; Weiyang Li; Jing Zhao; Yuran Liu; Fuquan Liu; Chengbin Dong; Chang Liu; Changbo Qi; Lin Yang; Liying Li (Journal of Molecular Medicine, 2025)

Seismic response analysis of the Yellow River terrace based on the spectral ratio method - Xingyu Ma; Lanmin Wang; Rong Xu; Qi Li (Earth Science Informatics, 2025)

Chronic Anatabine Administration Attenuates Cardiovascular Activity by Targeting NF-κB/NLRP3/Caspase-1-Dependent Pyroptosis and Oxidative Stress in Paraventricular Nucleus of Hypertensive Rat - Qing Su; Shao-Jun Li; Jun-Yu Zhou; Jin-Bao Yang; Fang Zhao; Guo-Quan Zou; Jia-Xuan Ma; Qi Liu; Yuan-Yuan Feng; Cui-Ling Yang; Ying Li; Hong-Bao Li; et al. (Cardiovascular Toxicology, 2025)

Enhancing crop yield forecasting performance through integration of process-based crop model and remote sensing data assimilation techniques - Dianchen Han; Peijuan Wang; Junxian Tang; Yang Li; Qi Wang; Yuping Ma (Agricultural and Forest Meteorology, 2025)

Oil and gas basin analysis based on airborne gravity and magnetic data - Yan-Xu Liu; Wen-Yong Li; Guo-Qing Ma; An-Qi Cao; Shan Gao; Ning Wang; Wen-Fen Lu; Li-Jie Wang; Cheng Yang (Applied Geophysics, 2025)

Butenolide synergises with vancomycin to eradicate pre-formed biofilm of Staphylococcus aureus by interfering with energy-associated metabolism - Dai-Xin Hu; Jinyou Liang; Jing Yan; Zhi-Wen Ma; Hai-Lin Li; Ying Xu; Yu Zhang; Qi Yin (Biofouling, 2025)

The impact of water-sediment regulation scheme (WSRS) on the chemistry of dissolved organic matter in the Yellow River estuary and adjacent waters - Donglei Niu; Yanfang Li; Yang Tan; Chao Ma; Yulin Qi; Yanan Li; Jianhui Tang (Water Research, 2025)

Competitive ion-molecule-coordinated interactions for high-voltage and high-rate lithium batteries under ultra-wide temperature - Weihao Wang; Qiao Luo; Liangjun Zhou; Xuanyuan Liao; Hao Yu; Li Ma; Yaowen Xu; Qingfei Meng; Yuyang Qi; Yuejiao Chen; Libao Chen; Weifeng Wei (Science Bulletin, 2025)

Stable isotope evidence for the moisture sources and runoff components in the southwestern Loess Plateau, China - Cong Xie; Liangju Zhao; Hang Liu; Haichen Zhao; Keke Ma; Ninglian Wang; Yuye Qin; Xingru Li; Xiaosheng Qi (Journal of Hydrology, 2025)

Auxin inhibited colonization of antibiotic resistant bacteria in soybean sprouts and spread of resistance genes to endophytic bacteria: Highlighting energy metabolism and immunity mechanism - Hu Li; Wenhui Xia; He Guo; Yanjie Wang; Qi Wang; Guodong Zhang; Qiuling Ma; Jian Zhou; Tiecheng Wang (Journal of Hazardous Materials, 2025)

Enhanced low-temperature simultaneous removal of nitrogen oxides and polychlorinated dibenzodioxins and dibenzofurans over vanadium-cerium-tungsten oxide supported on titanium dioxide catalyst: A pilot-scale evaluation - Jianwen Lai; Hongbo Qi; Yunfeng Ma; Xiaoqing Lin; Zhongkang Han; Heidelore Fiedler; Xiaodong Li (Journal of Environmental Chemical Engineering, 2025)

Seawater intrusion causes substantial release of dissolved organic carbon in coastal paddy soils - Wenting Chi; Yang Yang; Pei Wang; Chao Guo; Zebin Hong; Shiwen Hu; Kuan Cheng; Shan Wang; Han Li; Qi Wang; Ying Li; Yang Wu; et al. (Geochimica et Cosmochimica Acta, 2025)

Investigation of methanol steam reforming reactors with different catalyst support structures on hydrogen production efficiency and methanol conversion - Yuan Li; Ze-yu Ma; Zi-yan Qi; Zhi-an Xue; Xiao-long Zhou; Hao Guo (Fuel, 2025)

Multi-mode probe based on dual colorimetric and photothermal later flow immunoassay for the ultrasensitive determination of benzo[a]pyrene in vegetable oils - Yuting Yuan; Xiaoqian Tang; Liangxiao Zhang; Qi Zhang; Fei Ma; Peiwu Li (Food Chemistry, 2025)

Macrophages-derived exosomal non-coding RNA circ_0055194 regulating miR-665/YAP1/Twist axis is involved in pulmonary fibrosis induced by Nd2O3 - Yuanqi He; Yuhang Zhao; Kai Wu; Danyan Qi; Yupeng Ma; Wenjie Li; Xiangyu Chang; Suhua Wang; Yanrong Gao (Environmental Pollution, 2025)

Estimation of all-sky downwelling longwave radiation over the Tibetan Plateau using an improved parameterization scheme - Peizhen Li; Lei Zhong; Yaoming Ma; Yuting Qi; Zixin Wang (Atmospheric Research, 2025)

High-quality reference genome and population analysis of allotetraploid Elymus sibiricus provide insight into genome origin and environmental adaptations to the Qinghai-Tibetan Plateau - Xinrui Li; Changbing Zhang; Lili Wang; Gai Huang; Daxu Li; Changmian Ji; Zujun Yang; Minghong You; Lijun Yan; Lili Chen; Wenlong Gou; Xiong Lei; et al. (Science China Life Sciences, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Acute arsenic exposure induces CD4+ T cell subpopulations differentiation in spleen and thymus with the involvement of DAMPs-TLR4/NF-κB signaling pathway - Yan Qi; Xiaoxiao Peng; Nanxin Ma; Xiaodie Lan; Ying Wang; Bingxue Zheng; Yifan Xie; Xiujuan Yang; Qian Zhao; Ben Li; Xiaoyan Yan; Li Zhang; et al. (Environmental Geochemistry and Health, 2025)

Integrated Transcriptome and Microbiome Analyses Reveal Growth- and Stress-Response-Related Genes and Microbes in Mandarin Fish (Siniperca chuatsi) - Fan Zhou; Wei Liu; Ming Qi; Qianrong Liang; Gaohua Yao; Cheng Ma; Xueyan Ding; Zaihang Yu; Xinyu Li; Zhanqi Wang (Fishes, 2025)
Mandarin fish (Siniperca chuatsi) are known to exhibit distinct physiological and immunological adaptations to environmental stressors, but the underlying molecular and microbial mechanisms remain unclear. In this study, we integrated transcriptome and microbiome analyses to investigate adaptations across three geographically distinct mandarin fish groups: Guangdong (G), Qiupu (Q), and native Taihu (T). Liver RNA sequencing revealed 5339 differentially expressed genes (DEGs) between T and G and 1531 DEGs between T and Q. Functional enrichment analysis revealed group-specific responses. Specifically, DEGs from T vs. G were linked to small-molecule metabolism and innate immunity whereas the DEGs from T vs. Q were related to immune regulation and chromatin organization. The concurrent 16S rRNA sequencing of the intestinal microbiota identified 2680 amplicon sequence variants, with principal coordinate analysis showing distinct clustering (31.77% variance). Group T had higher Firmicutes abundance whereas groups G and Q had a higher relative abundance of Fusobacteriota. Correlation networks revealed key microbe–gene interactions, including positive links between Lactobacillus and immune genes in group T and negative associations with Romboutsia. These findings suggest that enhanced immune homeostasis and metabolic flexibility in group T may result from coordinated host gene expression and Lactobacillus-driven microbiome modulation. We provide new insights into the mechanisms of adaptation in mandarin fish and identify potential biomarkers for enhancing aquaculture resilience.

An integrated algorithm to estimate chlorophyll-a concentration in various optical waters using HY-3A CZI - Lan Zhang; Chaofei Ma; Xi Chen; Chen Zhang; Qi Li; Xiaomin Ye; Liqiao Tian (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Myofibrillar proteins protect paprika red while suffering gel disruption via pigment-induced disulfide bond cleavage - Yan Li; Wei Gao; Pan Li; Lijun Qi; Ruijia Zhang; Jia Hao; Zhiyong Ma; Ikram Alouk; Duoxia Xu (Food Chemistry, 2025)

Sr0.6Ba0.4NbO6 superparaelectrics with simple composition and high-efficiency capacitive energy storage - Jianhong Duan; Kun Wei; He Qi; Honglei Zhou; Linzhao Ma; Qianbiao Du; Tian Liu; Hao Li (Chemical Engineering Journal, 2025)

Extracellular polymeric substance-intercalated MXene membrane for osmotic power generation - Da-Qi Cao; Kai Tang; Guri Yihuo; Yan Jin; Yi-Xuan Song; Yun-Feng Wu; Wen-Yu Zhang; Zhongguo Zhang; Ming-Guo Ma; Li Song; Xiao-Di Hao (Chemical Engineering Journal, 2025)

Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia-bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2025)

Environmental risks and morphological transformation of heavy metals in copper smelting slag during rainfall events - Wanquan Yu; Chenchen Li; Jin Yan; Hanjing Yu; Xinyu Zhou; Huiying Kan; Yaoqiang Ma; Yuyun Li; Qi Meng; Peng Dong (Water, Air, & Soil Pollution, 2025)

Geotrichum candidum IBB69: a high-yield microbial protein producer with superior nutritional profile and industrial potential - Mengjia Lu; Longxue Ma; Yufeng Guo; Wuxi Chen; Yang Yang; Yu Duan; Xianni Qi; Hongxing He; Pengbao Shi; Qinhong Wang; Demao Li (Systems Microbiology and Biomanufacturing, 2025)

Characterizing the clustered landslides triggered by extreme rainfall during the 2024 typhoon Gaemi in Zixing City, Hunan Province, China - Hao Ma; Fawu Wang; Zijin Fu; Youqian Feng; Qi You; Sen Li (Landslides, 2025)

Debris flow forecasting: disastrous rainfall threshold matters - Yajun Li; Jun Zhang; Kristine Thorkildsen Jarsve; Fukang Ma; Yunfei Huang; Wenxin Zhao; Yan Zhao; Xingmin Meng; Mengyu Wang; Guowei Li; Guan Chen; Tianjun Qi; et al. (Landslides, 2025)

Impacts of preparation technologies on biological activities of edible mushroom polysaccharides – novel insights for personalized nutrition achievement - Gaoxing Ma; Xinyi Li; Qi Tao; Sai Ma; Hengjun Du; Qiuhui Hu; Hang Xiao (Critical Reviews in Food Science and Nutrition, 2025)

The microbiome, metabolome, and correlation analysis reveal the beneficial role of the commensal Shewanella sp. MR-7 in foodborne enteritis in turbot (Scophthalmus maximus L.) - Chao-Qun Li; Wen-Yi Wang; Xin Wen; Si-Yu Qi; Jia-Ning Xu; Dan-Yu Wu; Kang-Di Tian; Chun-Yang Zhang; Bei-Li Zhang; Qin-Yuan Ma (Aquaculture, 2025)

Differences in chemotherapeutic drug sensitivity before and after patient-derived tumor organoid construction - Fang Shao; Xin Huang; Zhihong Ma; Liqin Li; Chunjian Qi (Toxicology and Applied Pharmacology, 2025)

Comparative proteomic and transcriptomic analysis of testicular tissue of yaks with or without cryptorchidism - Dapeng Yang; Ligang Yuan; Jianlin Zeng; Yumei Qi; Long Ma; Haijun Li; Jinhan Lv; Yulu Chen (Theriogenology, 2025)

Algae-driven bacterial production of extracellular reactive oxygen species for emerging contaminants degradation - Xi Wang; Rong Ni; Lusen Li; Hongwei Yu; Jing Qi; Baiwen Ma; Chengzhi Hu; Jiuhui Qu (Science of The Total Environment, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Association analysis of single nucleotide polymorphisms of LMOD3 gene and feed efficiency in sheep - Lijuan He; Weimin Wang; Xiaojuan Wang; Deyin Zhang; Yukun Zhang; Yuan Zhao; Xiaolong Li; Liming Zhao; Dan Xu; Xiaobin Yang; Zongwu Ma; Dewen Kong; et al. (Small Ruminant Research, 2025)

Life cycle assessment-guided development of iron-based biomass catalyst for sustainable tetracycline degradation - Yu-Qi Li; Yu-Han Fan; Jun Ma; Ming Chen (Process Safety and Environmental Protection, 2025)

Daphnicalycinones A and B, Daphniphyllum alkaloids from the roots of Daphniphyllum calycinum with anti-inflammatory activity - Jiaqi Guo; Wenlong Li; Runchao Ma; Lizhu Han; Jiani Ying; Xiongyu Meng; Huaqiang Li; Qi Shi; Luping Qin (Phytochemistry Letters, 2025)

Occurrence, spatial-seasonal variation and air-soil exchange of traditional and novel organochlorine pesticides across 30° latitude in Eastern China: Old tales and new realities - Liang Wang; Wan-Li Ma; Pu-Fei Yang; Chun-Yan Huo; Peng-Tuan Hu; Wen-Long Li; Meng-Qi Fu (Journal of Hazardous Materials, 2025)

Study on enhanced heavy metal immobilisation in medical waste incineration bottom ash using calcium carbide residue with nanowire-like calcium carbonate regulation - Mei Yang; Qi Wang; Ning Fen; Xiongxiong Zhang; Wenxin Ji; Yonggang Sun; Yuanyuan Li; Yulong Ma (Journal of Environmental Chemical Engineering, 2025)

Co@Al2O3/C3N4 micro-nano catalysts with photothermal confinement effect for enhanced full-spectrum-solar-light-driven CO2 conversion - Yanan Wang; Qi Yin; Rui Zhang; Jie Ma; Song Xu; Qian Liang; Man Zhou; Zhongyu Li (Journal of Environmental Chemical Engineering, 2025)

Effects of exogenous and endogenous Mn on litter decomposition at different stages under continuous N addition in a subtropical forest - Shijia Wang; Qi Zhong; Wei Ma; Xueru Li; Liting Zhang; Shixing Zhou; Junxi Hu; Xinglei Cui; Congde Huang; Yang Liu; Lin Xu; Hongling Hu; et al. (Forest Ecology and Management, 2025)

High-cis astaxanthin nano lipid carrier: Preparation and bioavailability analysis - Chunran Han; Xintong Zhang; Chenchen Li; Jiaqi Sui; Xin Wang; Diaomei Ma; Jingyang Wang; Qi An (Food Bioscience, 2025)

Bridging the mercury exposure threshold: Development and application of whole-cell biosensors incorporating biotransformation pathways - Xue-ying Liu; Yan Guo; Wen-qi Zhang; Jiao Bai; Bing-chan Ma; Li-ting Zhou; Chang-ye Hui (Environmental Research, 2025)

Construction of a toxicity pathway from activation of the TLR4/NF-κB/NLRP3 axis to Parkinson's disease-like non-motor symptoms in mice - Kaidong Wang; Ge Shi; Yonghang Li; Qi Liu; Qianrong Zhang; Chenyang Wu; Yuxuan Jiao; Yuan Ma; Ai Qi; Min Huang (Environmental Toxicology and Pharmacology, 2025)

Laboratory investigation of sandstone joints and strata on TBM performance using a tunnelling test platform - Wei-Qiang Xie; Xiao-Li Liu; Shao-Hui Tang; Qi Zhang; Da-Rui Ren; Qing Ma (Engineering Geology, 2025)

Tailored PVDF ultrafiltration membranes with quaternary ammonium salt for enhancing antibacterial efficacy - Ao Ma; Yan Bai; Jie Han; Qi Qi; Chengbing Ma; Yujuan Zhang; Tao Xie; Guohui Zhang; Huiquan Li; Yunkun Wang (Desalination, 2025)

Schistosoma japonicum cystatin attenuated CLP-induced sepsis in mice though inducing tolerogenic dendritic cells and regulatory T cells - Yi-Xiang Wang; Yi-Dan Ma; Hui-Hui Li; Wen-Juan Duo; Qi-Wang Jin; Kai-Jun Zhou; Yan-Ran Gao; Jun-Nan He; Yu-Jie Xie; Liang Chu; Xiao-Di Yang (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

Corrigendum to “4-acetamidobutanoic acid, a γ-aminobutyric acid derivative, inhibits Streptococcus mutans growth, adhesion and biofilm formation” [Chem. Eng. J. 512 (2025) 162426] - Shanshan Liu; Lisong Ding; Zhenzhen Li; Qi Wang; Li Xu; Qian Ma; Bao Zhao; Hongsheng Liu; Junchang Guan; Kai Zhang (Chemical Engineering Journal, 2025)

Peptide-photosensitizer conjugates: From molecular design to function and antibacterial applications - Guanghui Zhao; Peng Tan; Qi Tang; Chenlong Zhou; Shuaikang Yang; Yucheng Zhang; Zhenduo Chen; Feng Li; Xi Ma (Chemical Engineering Journal, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

Molecular characterization and validation of adult-plant stripe rust resistance genes in Yunnan hulled wheat (Triticum aestivum ssp. yunnanense King) - Linyu Huang; Xinyu Wang; Yan Yan; Li Long; Qiushuo Li; Yuexue Wang; Yongjing Liu; Hao Li; Zhien Pu; Wei Li; Qiantao Jiang; Jian Ma; et al. (Theoretical and Applied Genetics, 2025)

Applicability assessment of six drought indices in different maize producing regions of China - Jie Ma; Peijuan Wang; Rui Feng; Yuanda Zhang; Yang Li; Qi Wang; Dingrong Wu; Yuping Ma (Natural Hazards, 2025)

The Application of MicroRNAs in Traumatic Brain Injury: Mechanism Elucidation and Clinical Translation - Hong Wang; Xiaolin Fan; Yuhao Zhang; Ning Ma; Liang Li; Qing Lu; Qi Wang; Boya Yu; Xiao Li; Junhong Gao (Molecular Neurobiology, 2025)

Latitudinal patterns of reproduction in the intertidal mussel Mytilisepta virgata along the coast of China - Xiao-Ning Zhang; Xiao-Xu Li; Lin-Xuan Ma; Xin Qi; Ming-Ling Liao; Yun-Wei Dong (Marine Biology, 2025)

Coexistence Patterns of Biocrust-Vascular Plant in the Loess Plateau - Yali Ma; Li Ma; Liping Yang; Hongyu Jiang; Siqing Wang; Yuhan Qi; Qianhai Ye; Weiqi Yao; Yafeng Zhang; Defei Liang; Changming Zhao; Ning Chen (Ecosystems, 2025)

Detrital Zircon U-Pb Dating and Hf Isotopes of the Crocker Fan Sandstones in Sabah, North Borneo: Constraints on Their Provenance and the Tectonic Evolution of Borneo - Aimei Zhang; Liyan Ma; Haidong Li; Junaidi Asis; Xudong Fang; Qi Fang; Min Chen; Min Ren; Xiaoying Dong (Journal of Earth Science, 2025)

Hydrochar-nanocomposite membrane combined hydrothermal pretreatment for nutrient upcycling from anaerobic digestate - Runhao Zhang; Chujie Qi; Jiaxin Bai; Li Gao; Stephen Gray; Chenhao Ma; Qiao Zhou; Bo Bian (Water Research, 2025)

Construction of the relationship between phytochemicals and gene expression in different Chaenomeles speciosa (Sweet) Nakai cultivars - Ya-Fang Shang; Jun-Hao Miao; Jia Zeng; Si-Qi Sun; Xiao-Long Ni; Zhao-Jun Wei; Yi-Long Ma; Hong-Xing Su; Wen-Bo Bai; Xiang-Li Niu; Wan Zhang (South African Journal of Botany, 2025)

Bombyx mori nuclear polyhedrosis virus infection regulated by host glycosphingolipids - Feifei Zhu; Jindie Hong; Tingting Xue; Qi Tang; Qian Yu; Guohui Li; Shangshang Ma; Xiaoyong Liu; Shuhao Huo; Keping Chen (Pesticide Biochemistry and Physiology, 2025)

Artemyriantholidimers A-G, undescribed guaiane-type sesquiterpenoid dimers from Artemisia myriantha and their antihepatoma activities - Meng-Fei Wang; Tian-Ze Li; Yun-Bao Ma; Yong-Cui Wang; Qi-Hao Li; Feng-Jiao Li; Ji-Jun Chen (Phytochemistry, 2025)

A polyethyleneimine-functionalized cellulose nanofiber/MXene composite aerogel: Towards highly efficient adsorption of crude oil, organic solvents, and dyes - Jia-Qi Lang; Ce Li; Lei Chen; Tian Mai; Zhong-Hui Guo; Ming-Guo Ma (Journal of Water Process Engineering, 2025)

Comparative study of the toxicity responses of Vallisneria natans and Pistia stratiotes to sulfadiazine under different planting methods - Qihui Li; Weizhen Zhang; Jian Su; Dayang Yang; Shuo Ma; Yi Liu; Xusong Yao; Li Gong; Qianchao Wang; Qi Li (Journal of Hazardous Materials, 2025)

Molecular mechanisms based on peripheral level of vanillin recognition in Orthaga achatina (Lepidoptera: Pyralidae) - Ting-Ting Yang; Yu Ma; Zheng Dai; Ying Li; Ji-Xiang Wang; Teng-Fei Bai; Merid Negash Getahun; George F.O. Obiero; Shuang-Lin Dong; Jin Zhang; Qi Yan (Insect Biochemistry and Molecular Biology, 2025)

Characterization of the soybean oil body interface: Revealing the mechanism of changes in the interfacial protein composition, structure, and function of oil bodies extracted under different denaturation conditions - Yi Liao; Yu Gao; Yukun Pei; Lewei Ma; Shizhang Yan; Baokun Qi; Yang Li (Food Hydrocolloids, 2025)

Adsorption of polyphenolic compounds by sodium alginate-modified starch nanoparticles in a multiphase system: Kinetic, thermodynamic and release characteristics studies - Wenzhi Lei; Maodong Qi; Jiangling Song; Hongcai Li; Xingnan Wang; Yue Ma; Zhenpeng Gao (Food Hydrocolloids, 2025)

A fluorescence biosensor with a dual-function DNA probe targeting the activated estrogen receptor for estrogenic activity evaluation - Qi Zhang; Yuewei Li; Jiali Li; Jiateng Ma; Minjie Li; Liang-Hong Guo (Environmental Research, 2025)

Size-dependent internalization of gold nanoparticles in individual Tetrahymena thermophila characterized by single-cell mass cytometry - Junjie Ma; Yaquan Liu; Liu Zhang; Linlin Yao; Yun Ding; Hua Qin; Ziniu Wang; Xuehan Zheng; Xinyue Yang; Haijiang Tian; Li Zeng; Liqun Chen; et al. (Environmental Pollution, 2025)

Nb2CTx modulated glycine film with multi-orientational piezoelectricity and photothermal functions designed for biomedical applications - Weiying Zheng; Tong Li; Lili Qian; Juan Ma; Zhibo Liu; Fei Jin; Zhidong Wei; Ting Wang; Zhang-Qi Feng (Chemical Engineering Journal, 2025)

4-acetamidobutanoic acid, a γ-aminobutyric acid derivative, inhibits Streptococcus mutans growth, adhesion, and biofilm formation - Shanshan Liu; Lisong Ding; Zhenzhen Li; Qi Wang; Li Xu; Qian Ma; Bao Zhao; Hongsheng Liu; Junchang Guan; Kai Zhang (Chemical Engineering Journal, 2025)

Preparation and bioactivities of low-molecular weight fucoidans and fuco-oligosaccharides: A review - Hai-Di Liu; Dong-Yue Ma; Shan-Rui Shi; Shi-Lin Song; Wen-Lan Li; Xiao-Hui Qi; Shou-Dong Guo (Carbohydrate Polymers, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Ecological risk assessment of emerging contaminants on soil and terrestrial ecosystems (2005–2024): a bibliometric and scientometric review - Wen Ma; Qi Wang; Erastus Mak-Mensah; Xiaole Zhao; Wenjia Qi; Jinhui Zhu; Rizwan Azim; Xujiao Zhou; Dengkui Zhang; Bing Liu; Qinglin Liu; Xuchun Li (Environmental Geochemistry and Health, 2025)

Choline-based ionic liquids enhance the dermal delivery of cyclosporine a for potential treatment of psoriasis - Yang Li; Qin Yu; Yi Lu; Yanyun Ma; Jianping Qi; Zhongjian Chen; Quangang Zhu; Wei Wu (Drug Delivery and Translational Research, 2025)

Root exudates of Salix cupularis orchestrate the accumulation of soil carbon and nitrogen in the rhizosphere during the restoration of a desertified alpine meadow - Qi Li; Fei Yan; Dongming Chen; Jiqiong Zhou; Zhouwen Ma; Yanfu Bai; Xingpeng Hu; Congyu Ma; Abeer S. Aloufi; Feida Sun; Anna Gunina; Jian Zhang; et al. (Applied Soil Ecology, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

A Salt-Tolerance evaluation system for Chinese cabbage using multispectral image data fusion and Fine-Tuned, pruned convolutional-LSTM-ResNet networks - Jun Zhang; Yikun Ai; Hao Liang; Dongfang Zhang; Yuxi Liu; Lu Li; Sijiao Qi; Hongda Ma; Siqi Zhao; Jingyi Xue; Yifan Zhao; Xiaofei Fan; et al. (Computers and Electronics in Agriculture, 2025)

Adsorption and immobilization of phosphorus in eutrophic lake water and sediments by a novel red soil based porous aerogel - Mengting Wu; Xinlong Hua; Zhifei Ma; Yalan Zhang; Wei Liu; Qi Li; Yanyan Zhong; Wenrong Xiong; Yankai Zhou; Xiaohao Guo; Yondong Zhang; Jianjun Dai; et al. (Water Research, 2025)

Collagen-based hydrogel derived from amniotic membrane loaded with quercetin accelerates wound healing by improving stereological parameters and reducing inflammation in a diabetic rat model - Xin Xiang; Weijun Peng; Qi Lu; Shiqi Ma; Jinfeng Wang; Jinling Ma; Xiaokai Wei; Mengmeng Li; Hongfeng Wang (Tissue and Cell, 2025)

Fullerenols hijack lysosomes to disrupt inter-organellar crosstalk and block autophagy pre-activated by mTOR inhibitors for cancer cell PANoptosis - Hedong Qi; Xue Li; Jing Ma; Jiacheng Sun; Yating Liu; Xin Wang; Kelong Fan; Chunying Shu; Chunru Wang (Science Bulletin, 2025)

Piperidine and bis-piperidine alkaloids from the peels of Areca catechu and their monoamine oxidases inhibitory activity - Song Wang; De-Zhi Wang; Xia Zhang; Zi-Wei Li; Dong-Hao Lu; Zheng-Jin Jiang; Min Ma; Min Song; Xiao-Qi Zhang (Phytochemistry, 2025)

Mantle metasomatism by subducted Indian continental crust: Evidence from post-collisional basaltic ultrapotassic rocks in southern Tibetan plateau - Miao-Yan Zhang; Lu-Lu Hao; Yue Qi; Qiang Wang; Andrew C. Kerr; Lin Ma; Cheng-Cheng Huang; Gang-Jian Wei; Jie Li; Jin-Long Ma; Qi-Wei Li; Zi-Long Wang; et al. (Lithos, 2025)

Impacts and mechanisms of emerging contaminants on biological manganese oxidation in algal-bacterial interaction system - Jing Qi; Changlu Zhang; Baiwen Ma; Lusen Li; Rashmi Koju; Hongwei Yu; Chengzhi Hu; Jiuhui Qu (Journal of Environmental Chemical Engineering, 2025)

Exceptional visible-light photocatalytic activity induced by lattice distortion in medium-entropy perovskite oxide La0.5Sr0.5Fe0.5Ti0.5O3 - Hongfang SHEN; Congcong MA; Zhihong QI; Jiaqi DING; Dong LI; Bo MA; Xiao ZHANG; Guozhong CAO; Youjun LU (Journal of Environmental Chemical Engineering, 2025)

Dynamic performance of TEPA-impregnated carbon nanofibers composites for direct air carbon capture in fixed bed columns - Si Chen; Xin He; Pan Li; Lingling Li; Meng Wang; Yulin Li; Qi Xu; Yanxia Sun; Chunxi Hai; Shengde Dong; Luxiang Ma; Yuan Zhou (Journal of Environmental Chemical Engineering, 2025)

Photocatalysis and peroxymonosulfate activation by dual Z-scheme g-C3N4/PDI/Co-Fe Prussian blue analogue for doxycycline hydrochloride removal - Di Li; Yuan Zhang; Chunyan Gao; Qi Wen; Xinguo Ma; Fang Song; Jun Zhou (Journal of Environmental Chemical Engineering, 2025)

Low-cost diatomite-loaded ZrO(OH)2 as an efficient green catalyst for amine-based carbon capture - Pan Li; Xingdong Qiu; Lingling Li; Si Chen; Chunxi Hai; Yanxia Sun; Qi Xu; Shengde Dong; Luxiang Ma; Xin He; Yuan Zhou (Fuel, 2025)

Efficient carbon dioxide capture and reduced desorption energy consumption with bifunctional aluminium-modified MWCNTs catalyst - Lingling Li; Xin He; Pan Li; Si Chen; Chunxi Hai; Yanxia Sun; Qi Xu; Shengde Dong; Luxiang Ma; Yuan Zhou (Fuel, 2025)

Resource utilization of microcrystalline magnesite: Synthesis of magnesium oxide by malic acid steam-assisted decomposition method for the synergetic adsorption of Congo red dye and Cu(II) ion - Jun Li; Ziyu Zhang; Rongzheng Gao; Xiaohui Li; Guoheng Sun; Ziye Zhou; Runtang Feng; Heqi Qi; Dong Zhang; Zihan Zhao; Shichen Xing; Dongmo Wu; et al. (Environmental Research, 2025)

Apatinib-Induced Hypertension Correlates with Improved Prognosis in Solid Tumor Patients - Caie Li; Jie Ma; Qiongying Wang; Liping Ma; Juncheng Han; Yali Qi; Xiaxia Pei; Jing Yu (Cardiovascular Toxicology, 2025)

Identification and characterization of rock discontinuities under complex terrain conditions based on UAV photogrammetry and ANN algorithm - Xiandong Ma; Shengwen Qi; Weiwei Zhu; Yongchao Li; Zan Wang (Bulletin of Engineering Geology and the Environment, 2025)

The Effect of Cuproptosis-Related Proteins on Macrophage Polarization in Mesothelioma is Revealed by scRNA-seq - Jia-Xin Xu; Li-Jing Ma; Li-Ying Tu; Qi-Sheng Tang; Bian Wu; Li-Hong Jiang (Biological Trace Element Research, 2025)

Estimating reference evapotranspiration using hybrid models optimized by bio-inspired algorithms combined with key meteorological factors - Hanmi Zhou; Linshuang Ma; Youzhen Xiang; Yumin Su; Jichen Li; Jiageng Chen; Sibo Lu; Cheng Chen; Qi Wu (Computers and Electronics in Agriculture, 2025)

Molecular identification of three cytochrome P450 genes and their potential roles in insecticides tolerance in Grapholita molesta (Busck) - Hui Han; Ming-Gao Li; Kai-Yang Xing; Qi Wang; Jun Hu; Zhi-Guo Zhao; Qin Yu; Rui-Yan Ma; Ling-Ling Gao; Yan-Qiong Guo (Pesticide Biochemistry and Physiology, 2025)

Occurrences of heavy metal in breast milk in China: Results of the third national breast milk survey - Rui Wang; Jiangkun Yu; Dawei Chen; Jingguang Li; Kemin Qi; Lan Ma; Bing Lyu; Xiaohong Shang; Yunfeng Zhao (Journal of Hazardous Materials, 2025)

A comparison study on compounding oat β-glucan onto Pleurotus eryngii protein by using different methods: In vitro digestion and fermentation characteristics - Qi Tao; Xinyi Li; Sai Ma; Qiuhui Hu; Gaoxing Ma (Food Hydrocolloids, 2025)

Trade-offs of organic amendment input on soil quality and crop productivity in saline-alkali land globally: A meta-analysis - Tong Li; Shengnan Wang; Shengli Liu; Xianliang Zhang; Helin Dong; Shuai Dai; Liying Chai; Hui Li; Yulong Lv; Tianwei Li; Qi Gao; Guorui Li; et al. (European Journal of Agronomy, 2025)

Epigenetic nanoplatform for synergistic immune activation and immunogenicity restoration enhancing cancer radio-immunotherapy - Zhenhu He; Xiaopei Peng; Jiong Li; Yaning Zhu; Xuan Zhang; Junhong Duan; Jing Ni; Mengtian Ma; Juan Wang; Zhenguo Liu; Bin Feng; Wenbin Zeng; et al. (Chemical Engineering Journal, 2025)

Achieving the ‘Golden Mean’ in ionic liquid-based electrolytes through ether functionalization: Enhanced lithium-ion conductivity and robust interphases - Taohong He; Bofang Shi; Xiangming Cui; Yushan Han; Hang Ma; Shiyi Sun; Jingchun Hou; Xiaofei Wang; Mingtao Li; Mingbo Ma; Qi Yu; Jianan Wang; et al. (Chemical Engineering Journal, 2025)

Recyclable and low-content deep eutectic solvent pretreatment at room temperature for fractionating uncondensed lignin and enhancing enzymatic saccharification - Cheng-Ye Ma; Qian Sun; Ling-Hua Xu; Haozhi Zhang; Jia-Long Wen; Zhenglong Li; Tong-Qi Yuan (Chemical Engineering Journal, 2025)

Photo-driven cycling electro-Fenton catalysis via the synergistic effect of dual cathodes for energy-efficient water decontamination: Insights into performance, reaction mechanism and toxicity - Qi Wang; Yuxin Hui; Xin Ma; Aoxiang Liu; Bo Shen; Xiaojia Jiang; Xiujuan Tang; Chunjuan Li; Yanling Wu; Jun Li; Huayue Zhu; Zhe Zhang; et al. (Chemical Engineering Journal, 2025)

PEO flocculation of kaolinite – Molecular weight effect - Chao Deng; Daowei Wang; Gen Huang; Jihui Li; Xiaoke Cui; Zeyang Xu; Liqiang Ma; Qi Liu (Applied Clay Science, 2025)

A new oviraptorosaur from the Lower Cretaceous Miaogou Formation of western Inner Mongolia, China - Mingze Hao; Zhiyu Li; Zhili Wang; Shuqiong Wang; Feimin Ma; Qinggele; J. Logan King; Rui Pei; Qi Zhao; Xing Xu (Cretaceous Research, 2025)

Therapeutic Potential of TUBB6 Inhibition for Hematoma Reduction, Microtubule Stabilization, and Neurological Recovery in an In Vivo Model of Intracerebral Hemorrhage - Jun-Yao Huang; Qiang Ma; Ya-Jie Qi; Zhi-Yao Wang; Xiao-Guang Liu; Yi-Ming Zhu; Yu-Ping Li (NeuroMolecular Medicine, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Depositional sequence and detrital zircon age spectra from Ediacaran to Early Cambrian at the northwestern Yangtze craton: Implication for the basin dynamics - Qiyu Wang; Zhengjiang Wang; Jiahong Liu; Qi Deng; Hao Liu; Zhiwu Li; Gang Zhou; Shuangjian Li; Guoqing Xiong; Yu Xia; Long Ma (Precambrian Research, 2025)

Light iron isotopes in high-silica granites record fluid evolution in magmatic-hydrothermal systems - Qi-Wei Li; Qiang Wang; Lin Ma; Andrew C. Kerr; Jing-Jing Fan; Jun-Hong Zhao; Hai-Ou Gu; Wei Wang; Zhi-Kun Su (Geochimica et Cosmochimica Acta, 2025)

Explosive characteristics of premixed hydrogen-air subjected to various concentration gradients - Yi Li; Guokai Zhang; Tianming Ma; Long Zhou; Xianfeng Chen; Chuncheng Zhang; Chuyuan Huang; Qi Zhao (Fuel, 2025)

Enhancing electrochemical performance in sodium-ion batteries: Strategic modification of oxygen-containing functional groups in hard carbon - Yulong Li; Yin Yang; Rundan Lin; Chen Zhang; Ting Xiao; Zhuang Ma; Qi Zhang; Xinlong Ma (Fuel, 2025)

Foxtail millet bran dietary fibres foster in vitro beneficial gut microbes and metabolites while suppressing pathobionts - Qi Li; Xiaowen Wang; Chuanlong Ma; Stanley Onyango; Weijie Wu; Haiyan Gao; Qiqiong Li (Food Chemistry, 2025)

Engineered S. cerevisiae-pYD1-ScFv-AFB1 mitigates aflatoxin B1 toxicity via bio-binding and intestinal microenvironment repair - Hong Huang; Ziyan Li; Zhanghua Qi; Linxi Ma; Gang Hu; Changwei Zou; Tingtao Chen (Food and Chemical Toxicology, 2025)

Li+ substitution induced O3/O′3 biphasic tailoring strategies enhancing anion/cation synergetic redox of Na-rich manganese-based cathode for sodium-ion batteries - Zhijie Zhang; Yilin Zhou; Xiaodong Zhang; Jixian Ma; Miaoning Yao; Jie Sun; Tong He; Xuexia He; Zhibin Lei; Ruibin Jiang; Zong-huai Liu; Qi Li (Chemical Engineering Journal, 2025)

Effects of intranasal administration with a symbiotic strain of Bacillus velezensis NSV2 on nasal cavity mucosal barrier in lambs - Jian Zheng; Hui Zeng; Qi Zhang; Yichao Ma; Yuchen Li; Jian Lin; Qian Yang (Veterinary Research Communications, 2025)

Hydrochemistry Predominantly Shapes the Unique Nitrogen-Fixing Bacterial Communities in Tibetan Hot Springs - Zhao-Qi Song; Li Wang; Yaru Ma; Dandan Deng; Yang Song; Feng Liang; Xiangyu Guan; Wen-Jun Li; Hongchen Jiang (Journal of Earth Science, 2025)

Determination of alkali metal elements in solid biomass fuel by laser-induced breakdown spectroscopy: Analysis and reduction of chemical matrix effects - Chengjun Li; Zhimin Lu; Jinzheng Chen; Ziyu Yu; Qi Yang; Huaiqing Qin; Xiwen Xing; Qingxiang Ma; Shunchun Yao (Analytica Chimica Acta, 2025)

Seasonal variations and comparative nutritional composition of hatchery-reared, hatchery-released, and wild black rockfish (Sebastes schlegelii) - Liu Wang; Yunhai He; Xu Wei; Xinyan Liang; Ruonan Zhang; Qi Liu; Chenqi Wang; Jinfeng Chen; Meiyuan Li; Zhi Ma; Shaodong Qu (Frontiers in Marine Science, 2025)
The black rockfish ( Sebastes schlegelii ) is a commercially important marine species in the Northwest Pacific Ocean. Its population has significantly declined due to overfishing and environmental changes. Stock enhancement has been launched in response to wild populations decline. However, limited evidence is available to confirm the ecological effects after release. Empirically, if the hatchery-released individuals are well-adapted to the wild environment, they should show good or similar nutritional conditions as well as their wild counterparts. Therefore, nutritional analysis was essential and conducted in the present study, by using 146 S. schlegelii individuals in order to compare the differences among hatchery-reared (before-release), hatchery-released, and wild conspecifics (post-release) groups in consideration of different environments during a whole stock enhancement practice. Our results exhibited that hatchery-reared S. schlegelii exhibited significantly lower levels of crude protein and amino acid content than that of hatchery-released and wild ones ( P < 0.05). Specifically, both the hatchery-released and wild S. schlegelii generally showed similar trends of nutrition profiling compared with their hatchery-reared counterparts, such as moisture, crude ash, crude lipid, crude protein, and amino acid profiles ( P > 0.05), indicating homogeneity in their nutritional contents. Our research suggested that S. schlegelii exhibited extensive ecological plasticity, and the variations in nutrition of a population was mainly influenced by environmental factors rather than the origin. However, several differences in fatty acid composition between hatchery-released and wild S. schlegelii indicated that hatchery-released fish might not have fully adapt to the food supply in the wild. This study provided insights into promoting responsible stock enhancement of this species in the future.

On the contribution of atmospheric reactive nitrogen deposition to nitrogen burden in a eutrophic Lake in eastern China - Weikun Li; Xia Wang; Wei Song; Zhongyi Zhang; Xueying Wang; Xiaodong Liu; Tianming Ma; Qi Wang; Yanli Zhang; Xinming Wang; Lei Geng (Water Research, 2025)

Selenium absorption, translocation and biotransformation in pak choi (Brassica chinensis L.) after foliar application of selenium nanoparticles - Wenchao Li; Lan Ma; Yixing Ye; Qi Tang; Yue Shen; Zidan Zou; Hongjian Zhou; Changhao Liang; Guozhong Wang (Food Chemistry, 2025)

Simple and efficient geotechnical reliability-based design based on transformed limit state functions by target reliability-oriented sampling - Bin Li; Yong-kai Shen; Zi-Jun Cao; Qi Wan; Chen-Zhe Ma (Computers and Geotechnics, 2025)

Intelligent electric energy driven ultrathin Graphene-Based Janus Films: Pioneering design for dynamic Electrochromism and superior microwave absorption - Tian Li; Jiatong Li; Zhengkang Xu; Jinzhe Li; Tinghao Liao; Jiani Du; Shanshan Wang; Qing Qi; Li Ma; Fanbin Meng (Chemical Engineering Journal, 2025)

Sustainable dual-cathode photoelectro-Fenton system enabling oxidative and reductive removal of pollutants via visible light driving Fe sites conversion - Aoxiang Liu; Xin Ma; Bo Shen; Hao Du; Xiaojia Jiang; Yanling Wu; Yanxian Jin; Jun Li; Huayue Zhu; Qi Wang (Chemical Engineering Journal, 2025)

Simultaneously enhancing efficiency and thermo-/UV-stability of organic solar cells by regulating the nanomorphology of the polymer blend by an acrylated fullerene derivative - Haitao Song; Yaqian Dong; Zesheng Zhang; Jin Fang; Chao Yue; Yongzhen Yang; Chao Liu; Qing Guo; Hua Wang; Qun Luo; Wei-Shi Li; Lingpeng Yan; et al. (Chemical Engineering Journal, 2025)

Bismuth/manganese-doped carbon dots in calcium phosphate matrix: Dynamic conformational nanoparticles enhancing tumor accumulation, deep penetration, and radiosensitivity - Jiahao Liu; Qingnian Li; Hanyu Tu; Jie Feng; Xiaofei Fan; Ze Mi; Hongpei Han; Xiaoqian Ma; Qi Liang; Zheng Zhang; Hongshuai Hou; Pengfei Rong; et al. (Chemical Engineering Journal, 2025)

Increasing the electron density of Cu sites via donor doping of Nb5+ to improve preferential CO oxidation performance of CuO/CeO2 - Taotao Huang; Liping Li; Qi Wang; Junfang Ding; Xinbo Li; Zhibin Geng; Mingwei Ma; Haozhe Liu; Guangshe Li (Chemical Engineering Journal, 2025)

Zero-strain high entropy spinel oxide (FeNiCuCrMn)3O4@rGO as high-performance anode for sodium ion battery - Bin Xiao; Xiaoyang Liu; Zelin Xie; Duyu Zheng; Juxing Zha; Jiqiu Qi; Fuxiang Wei; Qingkun Meng; Xiaolan Xue; Danyang Zhao; Yongzhi Li; Qing Yin; et al. (Chemical Engineering Journal, 2025)

Kv3.1 Interaction with UBR5 Is Required for Chronic Inflammatory Pain - Ying Zeng; Meng-Lan Sun; Di Liu; Yue Huang; Shan Xie; Ya-Xuan Zhao; Zi-Xuan Wu; Ya Liu; Gan Ma; Ling Xie; Yu-Tao Dang; Ling-Yun Hao; et al. (Molecular Neurobiology, 2025)

Integrative analysis of transcriptome and proteome wide association studies prioritized functional genes for obesity - Qi-Gang Zhao; Xin-Ling Ma; Qian Xu; Zi-Tong Song; Fan Bu; Kuan Li; Bai-Xue Han; Shan-Shan Yan; Lei Zhang; Yuan Luo; Yu-Fang Pei (Human Genetics, 2025)

Integrative transcriptomics and metabolomics analysis provide insight into the formation of skin pigmentation diversity in Chinese soft-shelled turtle (Pelodiscus sinensis) - Ming Qi; Wei Liu; Wei Li; Guangmei Chen; Wenrui Shi; Gaohua Yao; Yijiang Bei; Fan Yuan; Qinghui Meng; Fan Zhou; Wenjun Ma; Xueyan Ding; et al. (Aquaculture, 2024)

Combining rotary and deep tillage increases crop yields by improving the soil physical structure and accumulating organic carbon of subsoil - Jingwang Li; Lin Chen; Congzhi Zhang; Donghao Ma; Guixiang Zhou; Qi Ning; Jiabao Zhang (Soil and Tillage Research, 2024)

Evaluating the role of recalcitrant dissolved organic matter in bacterial community dynamics in urbanized freshwater ecosystems - Yang Liu; Xiding Wang; Huimin Li; Ruikai Zhang; Xudong Liu; Fangru Nan; Qi Liu; Junping Lv; Jia Feng; Chao Ma; Shulian Xie (Science of The Total Environment, 2024)

Foliar spraying of carbon dots reduces cadmium accumulation in rice by regulating rhizosphere immobilization, root development, and subcellular distribution - Yadong Li; Ronghua Xu; Jingyi Qi; Shang Lei; Qianying Han; Congli Ma; Hongjie Wang (Science of The Total Environment, 2024)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

Improving the simulation accuracy of summer maize growth and yield by pixel-based parameterization based on assimilating upscaled MODIS LAI - Dianchen Han; Peijuan Wang; Yihui Ding; Junxian Tang; Yang Li; Qi Wang; Yuping Ma; Dingrong Wu (Science of The Total Environment, 2024)

Temperature variability and influenza incidence in China: Effect modification by ambient fine particulate matter - Wen Li; Xin Wang; Yao Wu; Wenzhong Huang; Wenhao Yu; Pei Yu; Yuming Guo; Qi Zhao; Mengjie Geng; Haitao Wang; Wei Ma (Journal of Hazardous Materials, 2024)

Long-term exposure to third-hand smoke could accelerate biological aging via mitochondrial dysfunction: Evidence from population and animal studies - Wenbo Jiang; Xin Liu; Qianqian Lei; Mengjie Xiao; Mengyao Li; Yifan Ma; Cong Hu; Xinmiao Kong; Leyao Qi; Huanyu Wu; Changhao Sun (Journal of Hazardous Materials, 2024)

Sulfonic-acid-functionalized lignin-derived LC900@SO3H: A promising catalyst for the efficient production of biodiesel via the esterification of oleic acid - Peng Zheng; Wenqin Hu; Zhiyuan Tang; Qi Zhang; Song Li; Xinghua Zhang; Longlong Ma; Jianguo Liu (Journal of Environmental Chemical Engineering, 2024)

Bifunctional reduced graphene oxide/polyelectrolytes/MoS2-AuNPs hybrids with Vis/NIR photocatalytic and photothermal activities for biosafe and efficient antibacterial applications - Meng Fu; Chang Luo; Qi Yuan; Zequn Ma; Quansheng Long; Baihui Liu; Dang Wu; Jingshui Xu; Xiangming Li (Journal of Environmental Chemical Engineering, 2024)

1T/2H-MoS2/CdS heterojunction for the co-production of lactic acid photoreforming to hydrogen and value-added chemicals - Ermiao Liang; Xue Liu; Zheng Yang; Jifang Zhang; Yabo Qi; Rui Teng; Wenbo Cui; Mingcong Xu; Sha Luo; Chunhui Ma; Shouxin Liu; Wei Li (Journal of Environmental Chemical Engineering, 2024)

Comprehensive comparison of water quality risk and microbial ecology between new and old cast iron pipe distribution systems - Youyi Chen; Huishan Zhou; Hui Gao; Ziliang Su; Xinjun Li; Peng Qi; Tong Li; Chun Hu; Zesong Li; Zhihao Bi; Xueci Xing; Jingxin Yang; et al. (Journal of Environmental Sciences, 2024)

MoS2 coupled with ball milling co-modified sludge biochar to efficiently activate peroxymonosulfate for neonicotinoids degradation: Dominant roles of SO4•-, 1O2 and surface-bound radicals - Yifan Liu; Yongfei Ma; Zhikang Deng; Ping Li; Song Cui; Chenyu Zeng; Rui Mu; Yusheng Zhou; Xuebin Qi; Zulin Zhang (Environmental Research, 2024)

MoS2/ZnS heterostructure cathode with intralayer regulation for eco-friendly, degradable zinc-ion batteries - Fengfeng Li; Hongwei Sheng; Yifeng Qi; Wenxiang Wang; Zhaopeng Wang; Huasheng Bi; Lingxiao Ma; Daicao Wan; Haoshuo Zhang; Yuqi Ma; Jiao Yuan; Wenquan Li; et al. (Chemical Engineering Journal, 2024)

Sustainable dual-cathode photoelectro-Fenton-like system at a wide pH range for rapid degradation of emerging pollutants - Qi Wang; Aoxiang Liu; Bo Shen; Xin Ma; Yanling Wu; Xiaojia jiang; Jun Li; Chunjuan Li; Xiujuan Tang; Derek Hao; Huayue Zhu; Hao Du (Chemical Engineering Journal, 2024)

Insight into the mechanism of alkyl polyglucose biosurfactants enhancing antibiotics resistance genes removal during biotransformation of waste activated sludge into medium-chain fatty acids - Chun-shuang Zhou; Guang-li Cao; Bing-feng Liu; Sheng-qiang Fan; Wan-li Ma; Nan-qi Ren (Chemical Engineering Journal, 2024)

Numerical simulation of circulation characteristics of orographic precipitation in Qilian Mountains, Northeastern Tibetan Plateau - Linbo Wei; Lin Zhao; Zongyue Li; Yan Li; Qi Wen; Yuxia Ma (Atmospheric Research, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Temperature Reduction Characteristics of Coal with Different Moisture Contents During Cryogenic Treatment - Siqi Zhang; Zhaofeng Wang; Xingying Ma; Lingling Qi; Shijie Li; Yanqi Chen (Natural Resources Research, 2024)

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

White matter lesions contribute to motor and non-motor disorders in Parkinson’s disease: a critical review - Yue-Qi Jiang; Qiu-Zhu Chen; Yang Yang; Cai-Xia Zang; Jing-Wei Ma; Jin-Rong Wang; Yi-Rong Dong; Ning Zhou; Xing Yang; Fang-Fang Li; Xiu-Qi Bao; Dan Zhang (GeroScience, 2024)

A new removal method of yellow-rotten leaf for hydroponic lettuce with the flipping-tearing-twisting trajectory and its parameters optimisation - Yidong Ma; Chong Qi; Liming Zhou; Xin Jin; Bo Zhao; Xinping Li (Biosystems Engineering, 2024)

Neurotoxicity induced by aged microplastics from plastic bowls: Abnormal neurotransmission in Caenorhabditis elegans - Liangzhong Li; Ruixue Ma; Yuan Yuan; Qian Yao; Yajing Han; Hanlin Cao; Jianying Qi (Science of The Total Environment, 2024)

Recent selection and introgression facilitated high-altitude adaptation in cattle - Yang Lyu; Fuwen Wang; Haijian Cheng; Jing Han; Ruihua Dang; Xiaoting Xia; Hui Wang; Jincheng Zhong; Johannes A. Lenstra; Hucai Zhang; Jianlin Han; David E. MacHugh; et al. (Science Bulletin, 2024)

Polymorphisms of PRKAA1 and FABP4 genes and their association with feed efficiency in Hu sheep - Mengru Pu; Deyin Zhang; Liming Zhao; Dan Xu; Zongwu Ma; Kunchao Han; Lijuan He; Chengqi Yan; Qi Zhang; Lianjun Feng; Ziyue Xiao; Lei Gao; et al. (Small Ruminant Research, 2024)

Size-resolved gas-particle partitioning of polycyclic aromatic hydrocarbons in a large temperature range of 50 ℃ - De-Qi Wang; Shi-Ming Jia; Pu-Fei Yang; Fu-Jie Zhu; Wan-Li Ma (Journal of Hazardous Materials, 2024)

Comparative analysis of forest soil carbon sink and source based on bibliometrics: Development, hotspots, and trends - Qi Liu; Shengqiang Wang; Ruixia Ma; Fuzhao Huang; Jianxing Li; Shaoming Ye; Yili Guo (Journal of Cleaner Production, 2024)

Metabolomics study of dietary Pleurotus eryngii β-type glycosidic polysaccharide on colitis induced by dextran sodium sulfate in mice – Exploration for the potential metabolic indicators in urine and serum - Gaoxing Ma; Qi Tao; Xinyi Li; Yanhui Han; Hengjun Du; Qiuhui Hu; Hang Xiao (Food Chemistry, 2024)

Corrigendum to ‘Calcium oxide adsorption of gas phase PCDD/Fs and its impact on the adsorption properties of activated carbon’ [Environ. Pollut., Volume 361, 15 November 2024, 124750 - Jianwen Lai; Peiyue Wang; Hongbo Qi; Yunfeng Ma; Zhongkang Han; Heidelore Fiedler; Xiaodong Li; Xiaoqing Lin (Environmental Pollution, 2024)

Calcium oxide adsorption of gas phase PCDD/Fs and its impact on the adsorption properties of activated carbon - Jianwen Lai; Peiyue Wang; Hongbo Qi; Yunfeng Ma; Zhongkang Han; Fiedler Heidelore; Xiaodong Li; Xiaoqing Lin (Environmental Pollution, 2024)

Caprock sealing integrity and key indicators of CO2 geological storage considering the effect of hydraulic-mechanical coupling: X field in the Bohai Bay Basin, China - Bowen Chen; Qi Li; Yongsheng Tan; Yao Zhang; Tao Yu; Jiyuan Ma; Yiyan Zhong; Xiaying Li (Engineering Geology, 2024)

Capture and in-situ conversion of low-concentration CO2 over robust poly(ionic liquid)@porous carbon nanocomposites under green, co-catalyst- and solvent-free conditions - Mengshuai Liu; Chi Ma; Qi Wang; Ranyue Li; Shengze Yu; Hui Chen; Fusheng Liu (Chemical Engineering Journal, 2024)

Synergistic implementation of efficient adsorption-diffusion-conversion in lithium-sulfur batteries via built-in electric field constructed by transition metal selenides - Jun Wang; Kai Huang; Qi Li; Guo Cheng; Yongzheng Zhang; Na Teng; Cheng Lian; Cheng Ma; Jitong Wang; Wenming Qiao; Licheng Ling (Chemical Engineering Journal, 2024)

Multifunctional 3D pristine graphene with tunable electromagnetic properties via self-assembly strategy - Yuan Ma; Lingjun Guo; Lehua Qi; Yuchen Cao; Hejun Li (Chemical Engineering Journal, 2024)

Enhancing medium-chain fatty acids production via alkyl polyglucose modulation of electron acceptor generation, microbial community and metabolic traits in anaerobic fermentation of waste activated sludge - Chun-shuang Zhou; Guang-li Cao; Bing-feng Liu; Guo-jun Xie; Wan-li Ma; Sheng-qiang Fan; Nan-qi Ren (Chemical Engineering Journal, 2024)

Sialylation in the gut: From mucosal protection to disease pathogenesis - Xueni Ma; Muyang Li; Xiaochun Wang; Guoqing Qi; Lina Wei; Dekui Zhang (Carbohydrate Polymers, 2024)

Magnitude and hotspots of soil erosion types during heavy rainstorm events on the Loess Plateau: Implications for watershed management - Bo Yang; Xiaowu Ma; Juying Jiao; Wenting Zhao; Qi Ling; Jianjun Li; Xinhan Zhang (CATENA, 2024)

Assessment of Chinese Medicinal Herbal Wastes Compost Inoculated with Antagonistic Fungi: Nitrogen Retention and Microbial Community in Phytopathogenic Soil - Long Cao; Linshan Wang; Yanjiao Qi; Zhen Li; Mingyang Wang; Hong Zhang; Zifan Wang; Huining Lu; Shengfu Kang; Li Song; Zhongren Ma (Water, Air, & Soil Pollution, 2024)

A novel variable selection algorithm based on neural network for near-infrared spectral modeling - Pengfei Zhang; Zhuopin Xu; Huimin Ma; Lei Zheng; Xiaohong Li; Zhiyi Zhang; Yuejin Wu; Qi Wang (Analytica Chimica Acta, 2024)

Single-atom oxide-decorated AuNPs for universal enhancement in SERS detection of pesticide residues - Qi Zhang; Binbin Chen; Qingbian Ma; Zunlong Fang; Shu Li; Xiaoyu He; Yufeng Wang; Xiaohua Qi; Qian Chen; Ting Cai; Lin Zhang; Mingqiang Zou; et al. (Analytica Chimica Acta, 2024)

Insights into the uptake, accumulation, and metabolism of UV-328 in lettuce (Lactuca sativa L.) and radish (Raphanus sativus L.) - Bingru Li; Zhenzhen Yao; Qi Liu; Linlin Guo; Zhihong Ma; Cheng Li (Chemosphere, 2024)

Corrigendum to “CLAUDIN7 modulates trophectoderm barrier function to maintain blastocyst development in pigs” [Theriogenology 158 (2020) 346–357 10.1016/j.theriogenology.2020.09.038] - Di Gao; Tengteng Xu; Xin Qi; Wei Ning; Shang Ren; Zhenyuan Ru; Kaiyuan Ji; Yangyang Ma; Tong Yu; Yunsheng Li; Zubing Cao; Yunhai Zhang (Theriogenology, 2024)

Spatial heterogeneity, sediment-water exchange, and diffusion mechanisms of organophosphate esters from river to coastal aquatic system in a typical economic circle of northern China - Chengfeng Wang; Xindong Ma; Ziwei Yao; Dongfei Han; Guoliang Dai; Minghao Li; Yanjie Qi (Science of The Total Environment, 2024)

Developing a low-carbon, scalable strategy for the conversion of spent batteries into metal-organic framework-74 for CO2 capture - Shengshou Ma; Jiacheng Min; Chao Yang; Changzhong Liao; Yisong Zhu; Xiaolong Zhao; Ying Zhou; Xiao-yan Li; Qi Zhao; Kaimin Shih (Resources, Conservation and Recycling, 2024)

The nicotine demethylase CYP82E4 is essential for the formation of red dapples on flue-cured leaves of cherry-red tobacco - Fei Liu; Xueyi Sui; Yong Li; Yihan Zhang; Lu Zhao; Jiahong Liu; Shuanglü Shan; Feng Li; Xiaolong Chen; Long Zhang; Kun Huang; Yuping Ma; et al. (Plant Science, 2024)

Poly(dimethyldiallylammonium chloride)-modified magnetic bentonite for removal of polystyrene nanoplastics - Feng Han; Ye Wang; Shu-yu An; Lei Liu; Li-qi Ma; Liu Yang; Si-yu Liu (Journal of Environmental Chemical Engineering, 2024)

Performance study of activated multi-walled carbon nanotubes on catalyzing amine-based carbon capture - Lingling Li; Xin He; Pan Li; Si Chen; Tongtong Wang; Chunxi Hai; Yanxia Sun; Qi Xu; Shengde Dong; Luxiang Ma; Yuan Zhou (Fuel, 2024)

Preparation and characterization of DOPO-MMT co-stabilized gel foam for inhibiting coal spontaneous combustion - Li Ma; Jiamin Zhang; Xixi Liu; Yanpeng He; Shikui Jin; Fang Lou; Yongyong Jia; Xinli Fan; Qi Wang; Ruizhi Guo (Fuel, 2024)

Discovery of Momordin Ic that selectively reduces PD-L1 expression in multiple myeloma cells by recruiting SYVN1 - Sizhi Wu; Wen Yan; Wei Ma; Guangchao Li; Zhi Liu; Ruiming Ou; Jing Huang; Huijuan Shen; Qi Zhong; Yangmin Zhu; Qing Zhang; Zhao Yin; et al. (Food Bioscience, 2024)

Corrigendum to “Aflatoxin B1 disrupts testicular development via the cell cycle-related Ras/PI3K/Akt signaling in mice and pig” [Environ. Pollut. 329 (2023) 121729] - Fa-Li Zhang; Hao-Hai Ma; Pei-Yu Dong; Zheng-Ning Yuan; Shu-Er Zhang; Ai-Hong Zhao; Huan-Qi Liu; Massimo De Felici; Wei Shen; Xi-Feng Zhang (Environmental Pollution, 2024)

Rational reduction of planting density and enhancement of NUE were effective methods to mitigate maize yield loss due to excessive rainfall - Ruiqi Ma; Ning Cao; Yuanyang Li; Yilong Hou; Yujian Wang; Qi Zhang; Tianli Wang; Jinhu Cui; Bin Li; Wuliang Shi; Yubin Zhang (European Journal of Agronomy, 2024)

Configuring a structure self-curable lithium aluminum layered double hydroxide chloride type lithium adsorbents via a facile one-pot synergistical modification way - Junjie Huo; Chunxi Hai; Yanle Li; Yanxia Sun; Shengde Dong; Luxiang Ma; Xin He; Qi Xu; Yuan Zhou (Chemical Engineering Journal, 2024)

Heterointerface engineering of yolk-shell-structured Mn2O3/RuO2 for boosting oxygen electrocatalysis in rechargeable liquid and flexible zinc-air batteries - Xuena Ma; Mingyang Liu; ZhangXin Xu; Panzhe Qiao; Qi Li; Ruihong Wang; Shuting Zhang; Jinlong Zou; Baojiang Jiang (Chemical Engineering Journal, 2024)

Exceptional thermoelectric and mechanical performance in (Bi, Sb)2Te3 matrix facilitated by AgInSe2 alloying - Ruiheng Li; Wenxin Ou; Jianglong Zhu; Qian Deng; Xiaobo Tan; Qi Zhao; Tianbo Lu; Shaojingya Gao; Huangshui Ma; Hao Wu; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

Highly matched electrode for all-solid-state sodium-ion fiber hybrid supercapacitor with wide temperature and high energy density - Fuquan Ma; Ling Li; Xiumei Chen; Xuexia He; Qi Li; Jie Sun; Ruibin Jiang; Zhibin Lei; Zong-Huai Liu (Chemical Engineering Journal, 2024)

Enhanced Photocatalytic Performance of 2D/1D NiO/ZnO Heterostructures Towards Tetracycline Degradation - Qiang Gao; Fang Ma; Juan Qi; Junxi Li; Yuchen Cui; Naicai Xu; Mingjin Zhang (Water, Air, & Soil Pollution, 2024)

Identification and characterization of QSFS.sau-MC-5A for sterile florets genetically independent of fertile ones per spike in wheat - Jieguang Zhou; Yuanjiang He; Wei Li; Bin Chen; Longxing Su; Yuxin Lan; Lei Yan; Ying Wang; Md Nahibuzzaman Lohani; Yanlin Liu; Huaping Tang; Qiang Xu; et al. (Theoretical and Applied Genetics, 2024)

Meta-analysis of the Selected Genetic Variants in Immune-Related Genes and Multiple Sclerosis Risk - Weiguang Zhou; Weiqiong Hu; Lingyu Tang; Xiaorui Ma; Jiaxi Liao; Zhiyan Yu; Meifang Qi; Bifeng Chen; Jing Li (Molecular Neurobiology, 2024)

Benefit and risk: Keystone biomes in maize rhizosphere associated with crop yield under different fertilizations - Xiyuan Xu; Kunkun Fan; Qi Li; Teng Yang; Gui-Feng Gao; Yuying Ma; Li Nie; Wenju Liang; Jiabao Zhang; Haiyan Chu (Applied Soil Ecology, 2024)

Rhizosphere microorganisms from the soil around the roots of Lycium barbarum L. - Zhi-bo Jiang; Ya-fei Ren; Yun-qi Hu; Jing-ling Yang; Ji-yuan Wei; Xiao-li Ma (Acta Physiologiae Plantarum, 2024)

Manganese mineralization constrained by redox conditions in the Cryogenian Nanhua Basin, South China and its implications for nitrogen and carbon cycling - Ping Wang; Jian Wang; Yuansheng Du; Wenchao Yu; Qi Zhou; Li Tian; Liangjun Yuan; Wen Pan; Wei Wei; Yongjun Qin; Zhixin Ma (Frontiers in Marine Science, 2024)
The Nanhua Basin of South China recorded complete Cryogenian stratigraphic sequence from the Sturtian Glaciation (~717–660 Ma) to the Marinoan Glaciation (~654–635 Ma). The interglacial Datangpo Fm in the Nanhua Basin is divided into two members, and the first member consists of the Mn-carbonate unit and the overlying black shale unit, containing a series of large and superlarge manganese deposits. The metallogenic process of manganese deposits is not clear, and the Mn-carbonates formed through the precursor of Mn-oxide/oxyhydroxide reduction or directly precipitated from an anoxic water column. Moreover, the redox conditions in the deep Nanhua Basin during the precipitation of manganese deposits are also controversial. In this study, the high-resolution nitrogen contents (TN), isotope compositions, carbon isotope compositions of organic and inorganic matter from the first member of the Datangpo Fm are analyzed. The δ 15 N values of the Mn-carbonate unit (+1.53‰ to +5.26‰, mean +3.36‰) are higher than those of the overlying black shale unit (−3.74‰ to +3.54‰, mean +0.89‰). The Mn contents show a negative relationship with TN but a positive relationship with δ 15 N in the Mn-carbonate unit, implying that the formation of Mn-carbonates is related to redox variations. The relatively higher δ 15 N values in the Mn-carbonate unit indicated oxic conditions, and NH 4 + can be released and partially oxidized during the mineralization of organic matter, resulting in the residual 15 N-enriched NH 4 + being transferred into clay minerals. Meanwhile, the lower δ 15 N values in the black shale unit indicated anoxic conditions, which recorded primary N isotope signals. The Mn-carbonate unit is characterized by negative δ 13 C carb values (−11.17‰ to −5.22‰, mean −8.30‰), which show a positive relationship with δ 13 C org , but a negative relationship with Mn contents, implying that the negative δ 13 C carb excursions were related to the organic matter degradation during Mn-carbonate formation. The findings of this study indicated that the metallogenesis of manganese deposits in the Cryogenian Nanhua Basin was constrained mainly by the oxic interval in the deep basin. The nitrogen and carbon cycling process can provide new insights into geochemical cycling after the Sturtian Glaciation.

Improved classification of soil As contamination at continental scale: Resolving class imbalances using machine learning approach - Tao Hu; Kechao Li; Chundi Ma; Nana Zhou; Qiusong Chen; Chongchong Qi (Chemosphere, 2024)

A global assessment of glyphosate and AMPA inputs into rivers: Over half of the pollutants are from corn and soybean production - Qi Zhang; Yanan Li; Carolien Kroeze; Wen Xu; Lingtong Gai; Miltiadis Vitsas; Lin Ma; Fusuo Zhang; Maryna Strokal (Water Research, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Whale optimization algorithm-based multi-task convolutional neural network for predicting quality traits of multi-variety pears using near-infrared spectroscopy - Qi Shi; Yanlei Li; Fan Zhang; Qianyun Ma; Jianfeng Sun; Yaqiong Liu; Jianlou Mu; Wenxiu Wang; Yiwei Tang (Postharvest Biology and Technology, 2024)

AlphaFold-guided redesign of a plant pectin methylesterase inhibitor for broad-spectrum disease resistance - Yeqiang Xia; Guangzheng Sun; Junhua Xiao; Xinyi He; Haibin Jiang; Zhichao Zhang; Qi Zhang; Kainan Li; Sicong Zhang; Xuechao Shi; Zhaoyun Wang; Lin Liu; et al. (Molecular Plant, 2024)

Insight into the influence mechanism of chloride ions towards in-situ electric-induced uranium incorporation into magnetite - Mi Li; Xin Ma; Xiao-yan Wu; Yi-long Hua; Xiao-wen Zhang; Qi Fang; Tao Cai (Journal of Cleaner Production, 2024)

Grazing period management affects the accumulation of plant functional groups, and soil nutrient pools and regulates stoichiometry in the desert steppe of Northwest China - Zhuo Liu; Hongbin Ma; Guohui Wang; Yan Shen; Jingli Ma; Wen Li; Yao Zhou; Qi Lu (Journal of Environmental Management, 2024)

Key indicators of caprock sealing assessment with consideration of faults in potential CO2 geological storage sites in Subei Basin, China - Bowen Chen; Qi Li; Yongsheng Tan; Yao Zhang; Tao Yu; Yiyan Zhong; Jiyuan Ma; Xiaochun Li (Gas Science and Engineering, 2024)

Construction of large-aperture mesoporous silica spheres supported polyoxometalate heterogeneous catalysts and their high-efficiency for the ultra-deep desulfurization - Jia-Qi Wu; Lu-lu Ma; Zhuang-Zhuang Li; Xin Li; Si-Wen Li; Chang Li; Rong-Xi Li; Jian-She Zhao (Fuel, 2024)

Fermentation of Soy-based dairy substitutes by lactic acid bacteria: Focus on the process of soy protein hydrolysis - Zengbo Wang; Xiaodong Wang; Congrui Zhao; Hongwei Tang; Jiage Ma; Qi Qin; Kuangyu Zhao; Wei Yu; Bailiang Li (Food and Bioproducts Processing, 2024)

Efficient degradation of sulfadiazine by UV-triggered electron transfer on oxalic acid-functionalized corn straw biochar for activating peroxyacetic acid: Performance, mechanism, and theoretical calculation - Chenyu Zeng; Yongfei Ma; Ping Li; Xi Chen; Hongtao Liu; Zhikang Deng; Rui Mu; Xuebin Qi; Zulin Zhang (Bioresource Technology, 2024)

Long-term second-generation antipsychotics decreases bone formation and resorption in male patients with schizophrenia - Fan Wang; Hui Li; Kaijun Yi; Yan Wu; Qingtao Bian; Baoyan Guo; Xingguang Luo; Yimin Kang; Qi Wu; Qinghe Ma (Psychopharmacology, 2024)

Demineralization effects on physicochemical and combustion characteristics of biomass: Insights into distributed kinetics, flue gas evolution, and slag formation - Peiyong Ma; Bowen Li; Rui Diao; Xiaohao Liu; Zhusong Cheng; Fenglei Qi (Fuel, 2024)

Construction and examination of temperature master curve for asphalt with different aging extents - Wenhao Dong; Feng Ma; Zhen Fu; Wen Qin; Cong Qi; Jiahao He; Chen Li (Fuel, 2024)

Metabonomics analysis of the flavor characteristics of Wuyi Rock Tea (Rougui) with “rock flavor” and microbial contributions to the flavor - Wenmiao Wu; Xinyi Jiang; Qi Zhu; Yang Yuan; Rongping Chen; Wenzhen Wang; Anxing Liu; Chengjian Wu; Chunhua Ma; Jianghua Li; Juan Zhang; Zheng Peng (Food Chemistry, 2024)

Estimation of wheat protein content and wet gluten content based on fusion of hyperspectral and RGB sensors using machine learning algorithms - Shaohua Zhang; Xinghui Qi; Mengyuan Gao; Changjun Dai; Guihong Yin; Dongyun Ma; Wei Feng; Tiancai Guo; Li He (Food Chemistry, 2024)

Performance activation mechanism of aluminum-based layered double hydroxides adsorbents for recovering Li+ by pH modulating - Yanle Li; Chunxi Hai; Junjie Huo; Wencheng Pan; Tiandong Chen; Xiang Li; Xin He; Yanxia Sun; Shengde Dong; Luxiang Ma; Qi Xu; Yuan Zhou (Chemical Engineering Journal, 2024)

Multifunctional wood-derived cellulose/Ti3C2Tx composite films enhanced by densification strategy for electromagnetic shielding, Joule/solar heating, and thermal camouflage - Qi Liu; Pei-Lin Wang; Wei Zhang; Tian Mai; Meng-Yu Qi; Lei Chen; Junfeng Li; Ming-Guo Ma (Chemical Engineering Journal, 2024)

Triptolide induced spermatogenesis dysfunction via ferroptosis activation by promoting K63-linked GPX4 polyubiquitination in spermatocytes - Jiaqi Li; Dezhi Chen; Jialiang Suo; Jiaqi Li; Yimu Zhang; Yu Wang; Zhewen Deng; Qi Zhang; Bo Ma (Chemico-Biological Interactions, 2024)

Microbial pollution assessment in semi-exposed relics: A case study of the K9901 pit of the mausoleum of emperor Qin Shihuang - Jing Xiong; Xuchen Qi; Dingmeng Wu; Ying Zhang; Changqing Yang; Yu Ma; Jian Yang; Huiying Wang; Jiarong Han; Angui Li (Building and Environment, 2024)

Research on density grading of hybrid rice machine-transplanted blanket-seedlings based on multi-source unmanned aerial vehicle data and mechanized transplanting test - Xicheng Wang; Zehua Li; Suiyan Tan; Hongwei Li; Long Qi; Yuwei Wang; Jiongtao Chen; Chuanyi Yang; Jiaying Chen; Yijuan Qin; Xu Ma (Computers and Electronics in Agriculture, 2024)

Quantum dots: next shift to combat plant diseases - Temoor Ahmed; Muhammad Noman; Jason C. White; Chuanxin Ma; Qi Wang; Bin Li (Trends in Plant Science, 2024)

An ontology-driven method for urban building energy modeling - Rui Ma; Qi Li; Botao Zhang; Hao Huang; Chendi Yang (Sustainable Cities and Society, 2024)

An efficient loop closure detection method for communication-constrained bathymetric cooperative SLAM - Chi Qi; Teng Ma; Ye Li; Luting Lv; Yu Ling (Ocean Engineering, 2024)

Coupling sedimentary records of anthropogenic metal(loid)s in urban waterscape parks with the “Coal to Gas” transition - Shen Yu; Tao Ma; Linlin Zhang; Qi Li; Min Zhou (Journal of Hazardous Materials, 2024)

Deciphering the reduction of antibiotic resistance genes (ARGs) during medium-chain fatty acids production from waste activated sludge: Driven by inhibition of ARGs transmission and shift of microbial community - Chun-shuang Zhou; Guang-li Cao; Bing-feng Liu; Wei Liu; Wan-li Ma; Nan-qi Ren (Journal of Hazardous Materials, 2024)

Pollution characteristics, source apportionment and absorption spectra of size-resolved PAHs in atmospheric particles in a cold megacity of China - De-Qi Wang; Shi-Ming Jia; Li-Yan Liu; Zi-Feng Zhang; Fu-Jie Zhu; Wan-Li Ma (Journal of Hazardous Materials, 2024)

GhGASA14 regulates the flowering time of upland cotton in response to GA3 - Ying Li; Wenmin Yuan; Jialuo Peng; Jisheng Ju; Pingjie Ling; Xuefeng Guo; Junning Yang; Qi Ma; Hai Lin; Jilian Li; Caixiang Wang; Junji Su (Plant Cell Reports, 2024)

Igniting lightning, wildfire occurrence, and precipitation in the boreal forest of northeast China - Cong Gao; Chunming Shi; Jinbao Li; Shangbo Yuan; Xinyan Huang; Qi Zhang; Qiming Ma; Guocan Wu (Agricultural and Forest Meteorology, 2024)

The growth and nutrient removal properties of heterotrophic microalgae Chlorella sorokiniana in simulated wastewater containing volatile fatty acids - Tianxiang Lu; Kunyang Su; Guangxiang Ma; Cong Jia; Jie Li; Qi Zhao; Mingming Song; Chongqing Xu; Xiaozhe Song (Chemosphere, 2024)

Identification critical host factors for Japanese encephalitis virus replication via CRISPR screening of human sgRNA library - Le-le Liu; You-qin Yin; Kai-xiong Ma; Jin-chao Xing; Xing-xing Ren; Jin-yu Huang; Ming Liao; Wen-bao Qi; Li-hong Huang (Veterinary Microbiology, 2024)

Toxic effect and mRNA mechanism of moon dust simulant induced pulmonary inflammation in rats - Jintao Wang; Yuan Xue; Bin Wu; Ming Lei; Honglei Ma; Xinxing He; Qi Tan; Jian Guan; Wei Song; Renfu Li; Xinguang Cui (Toxicology, 2024)

How many people can the Qinghai-Tibet Plateau hold, and how large cities can be built in recent hundred years? - Chuanglin Fang; Guangdong Li; Chao Bao; Zhenbo Wang; Wei Qi; Haitao Ma; Siao Sun; Yupeng Fan; Wanxu Chen (Science of The Total Environment, 2024)

Enhanced Sb(V) removal of sulfate-rich wastewater by anaerobic granular sludge assisted with Fe/C amendment - Qi Li; Yanping Zhu; Nan Jiang; Jun Li; Yanbiao Liu; Xiaoguang Chen; Xiaoyang Xu; Huangyingzi Wang; Yimeng Ma; Manhong Huang (Science of The Total Environment, 2024)

The future of Chinese rivers: Increasing plastics, nutrients and Cryptosporidium pollution in half of the basins - Yanan Li; Mengru Wang; Qi Zhang; Carolien Kroeze; Wen Xu; Lin Ma; Fusuo Zhang; Maryna Strokal (Resources, Conservation and Recycling, 2024)

Anti-pancreatic cancer activity of cassane diterpenoids isolated from the seeds of Caesalpinia sappan mediated by autophagy activation via ROS/AMPK/mTORC1 pathway - Jia Su; De-Sheng Wang; Guo-Xian Hu; Yu-Yao Liu; Ming Hu; Ya Chen; Qi-Qi Wang; Run-Cheng Yan; Yun Wu; Yong-Jiao Li; Ke Ma; Yan-Yan Qi; et al. (Phytochemistry, 2024)

New sauropod remains from the Middle Jurassic Dongdaqiao Formation of Qamdo, eastern Tibet - Xue-Fang Wei; Qi-Yu Wang; Xian-Yin An; Bao-Di Wang; Yu-Jie Zhang; Chuang-Long Mou; Yong Li; Dong-Bing Wang; Waisum Ma; Martin Kundrát (Palaeoworld, 2024)

Engineering porosity of MIL-101(Cr) using solvation effect - Jiawei Cao; Yunxia Li; Meng Qi; Xiubiao Ma; Fengting He; Yongqiang Wang; Dongfeng Zhao (Journal of Environmental Chemical Engineering, 2024)

Development and comprehensive SBSE-GC/Q-TOF-MS analysis optimization, comparison, and evaluation of different mulberry varieties volatile flavor - Di Ma; Tianbao Lin; Huiyu Zhao; Yougui Li; Xinquan Wang; Shanshan Di; Zhenzhen Liu; Mingqi Liu; Peipei Qi; Suling Zhang; Rui Jiao (Food Chemistry, 2024)

Stimulus-responsive room-temperature phosphorescence with tunable color for time-resolved advanced dynamic anti-counterfeiting - Li Yang; Qi Zhang; Yatuan Ma; Hongjuan Li; Shiguo Sun; Yongqian Xu (Chemical Engineering Journal, 2024)

Flexible human-machine interface touch system based on double-network solid-state ionic conductive elastomers - Wang Zhan; Qi Zhang; Zhilu Ye; Yuhao Wang; Zihao Yang; Yijing Wang; Cuiling Zhang; Zeying Zhang; Li Xue; Feng Ma; Zhiguang Wang; Niancai Peng; et al. (Chemical Engineering Journal, 2024)

High-level production of chitinase by multi-strategy combination optimization in Bacillus licheniformis - Zhimin Qi; Bo Lei; Min Xiong; Weijia Li; Yongqing Liao; Dongbo Cai; Xin Ma; Ruibin Zhang; Shouwen Chen (World Journal of Microbiology and Biotechnology, 2024)

Treatment of Syringomyelia Characterized by Focal Dilatation of the Central Canal Using Mesenchymal Stem Cells and Neural Stem Cells - Mo Li; Xinyu Wang; Boling Qi; Shengyu Cui; Tianqi Zheng; Yunqian Guan; Longbing Ma; Sumei Liu; Qian Li; Zhiguo Chen; Fengzeng Jian (Tissue Engineering and Regenerative Medicine, 2024)

Fractal characteristics of particle breakage on the coral sands–structure interface during ring shear tests - Houzhen Wei; Li Xin; Hang Ruan; Qi Yao; Xiaolong Ma; Rui Xu (Marine Geophysical Research, 2024)

Viperin inhibits interferon-γ production to promote Mycobacterium tuberculosis survival by disrupting TBK1-IKKε-IRF3-axis and JAK-STAT signaling - Yao Liang; Yun Liang; Qi Wang; Qianna Li; Yingqi Huang; Rong Li; Xiaoxin Pan; Linmiao Lie; Hui Xu; Zhenyu Han; Honglin Liu; Qian Wen; et al. (Inflammation Research, 2024)
Objectives and design As an interferon-inducible protein, Viperin has broad-spectrum antiviral effects and regulation of host immune responses. We aim to investigate how Viperin regulates interferon-γ (IFN-γ) production in macrophages to control Mycobacterium tuberculosis (Mtb) infection. Methods We use Viperin deficient bone-marrow-derived macrophage (BMDM) to investigate the effects and machines of Viperin on Mtb infection. Results Viperin inhibited IFN-γ production in macrophages and in the lung of mice to promote Mtb survival. Further insight into the mechanisms of Viperin-mediated regulation of IFN-γ production revealed the role of TANK-binding kinase 1 (TBK1), the TAK1-dependent inhibition of NF-kappa B kinase-epsilon (IKKε), and interferon regulatory factor 3 (IRF3). Inhibition of the TBK1-IKKε-IRF3 axis restored IFN-γ production reduced by Viperin knockout in BMDM and suppressed intracellular Mtb survival. Moreover, Viperin deficiency activated the Janus kinase (JAK)-signal transducer and activator of transcription (STAT) signaling pathway, which promoted IFN-γ production and inhibited Mtb infection in BMDM. Additionally, a combination of the anti-TB drug INH treatment in the absence of Viperin resulted in further IFN-γ production and anti-TB effect. Conclusions This study highlights the involvement of TBK1-IKKε-IRF3 axis and JAK-STAT signaling pathways in Viperin-suppressed IFN-γ production in Mtb infected macrophages, and identifies a novel mechanism of Viperin on negatively regulating host immune response to Mtb infection.

Repair of tendons treated with peracetic acid–ethanol and gamma irradiation by EDC combined with NHS: a morphological, biochemical and biomechanical study in vitro - Rong-xing Ma; Rui-feng Li; Xiao-qiang Deng; Rui-qi Qiao; Ji-kai Li; Kun-xiu Song; Shao-lin Ji; Yong-cheng Hu (Cell and Tissue Banking, 2024)

Application and mechanism of carbonate material in the treatment of heavy metal pollution: a review - Yaoqiang Ma; ChenChen Li; Jin Yan; Hanjing Yu; Huiying Kan; Wanquan Yu; Xinyu Zhou; Qi Meng; Peng Dong (Environmental Science and Pollution Research, 2024)

Atmospheric CO2 in the megacity Hangzhou, China: Urban-suburban differences, sources and impact factors - Yuanyuan Chen; Yanran Lu; Bing Qi; Qianli Ma; Kunpeng Zang; Yi Lin; Shuo Liu; Fengmei Pan; Shan Li; Peng Guo; Lihan Chen; Wengang Lan; et al. (Science of The Total Environment, 2024)

Quantum spin driven Yu-Shiba-Rusinov multiplets and fermion-parity-preserving phase transition in K3C60 - Shu-Ze Wang; Xue-Qing Yu; Li-Xuan Wei; Li Wang; Qiang-Jun Cheng; Kun Peng; Fang-Jun Cheng; Yu Liu; Fang-Sen Li; Xu-Cun Ma; Qi-Kun Xue; Can-Li Song (Science Bulletin, 2024)

Activation of RXRα exerts cardioprotection through transcriptional upregulation of Ndufs4 in heart failure - Mingyan Shao; Lingru Li; Lin Ma; Chao Song; Weili Li; Yawen Zhang; Wenkun Cheng; Yun Chen; Ye Yang; Qian Wang; Chun Li; Qi Wang; et al. (Science Bulletin, 2024)

Late Jurassic to early Cretaceous radiolarian faunas from Changku, Gyangze, southern Tibet: Implications for the evolution of the Neo-Tethys - Wenyuan Zhang; Guobiao Li; Xuesong Ma; Tiangyang Wang; Fuhao Xiong; Yuewei Li; Kezhantu Bao; Jingjing Wang; Qi Li; Wei Shi (Journal of Asian Earth Sciences, 2024)

Rural household nonagricultural income and energy transition: Evidence from central China - Xiaowei Ma; Chuandong Li; Qi Kang; Danni Chen; Qingyu Sun (Energy Policy, 2024)

Pressure-assisted hydrothermal pretreatment for biorefinery to enhance pulp production - Qian Sun; Bin Wang; Haijian Huang; Cheng-Ye Ma; Yanguang Ma; Xiaojun Shen; Xuefei Cao; Zhuohua Sun; Li Zhang; Tong-Qi Yuan (Chemical Engineering Journal, 2024)

Contact-electro-catalysis for degradation of trace antibiotics in wastewater - Da-Qi Cao; Rong-Kun Fang; Yi-Xuan Song; Ming-Guo Ma; Haiyan Li; Xiao-Di Hao; Rongling Wu; Xiangyu Chen (Chemical Engineering Journal, 2024)

Superabsorbent carboxymethyl cellulose–based hydrogel fabricated by liquid-metal-induced double crosslinking polymerisation - Qi Cao; Jing Chen; Miao Wang; Zhigang Wang; Wenjun Wang; Yanqin Shen; Ying Xue; Bo Li; Yanli Ma; Yijun Yao; Hailiang Wu (Carbohydrate Polymers, 2024)

A modified cultivation strategy to enhance biomass production and lipid accumulation of Tetradesmus obliquus FACHB-14 with copper stress and light quality induction - Yuanrong Jin; Yinting Li; Yingying Qi; Qun Wei; Gairen Yang; Xiangmeng Ma (Bioresource Technology, 2024)

Probing into the radiative mechanisms and drivers influencing urban heat-cold islands and urban pollution islands during heavy-haze events in a cold megacity of Northeast China - Stephen Dauda Yabo; Lu Lu; Lixin Ma; Bo Li; Donglei Fu; Fan Meng; Jinpan Jiang; Xie Shengjin; Wei Zhang; Hong Qi (Atmospheric Research, 2024)

Efficient biosynthesis of vanillylamine via biological transamination of lignin-derived vanillin in a β-cyclodextrin-water medium - Qi Li; Linghui Kong; Yu-Cai He; Cuiluan Ma (Sustainable Chemistry and Pharmacy, 2024)

Proteomics revealed composition- and size-related regulators for hepatic impairments induced by silica nanoparticles - Xinying Zhao; Ru Ma; Alimire Abulikemu; Yi Qi; Xiaoying Liu; Ji Wang; Kun Xu; Caixia Guo; Yanbo Li (Science of The Total Environment, 2024)

Large-scale quantum emulating simulations of biomolecules: A pilot exploration of parallel quantum computing - Honghui Shang; Fei Wang; Yi Fan; Huan Ma; Qi Liu; Chu Guo; Pengyu Zhou; Qi Chen; Qian Xiao; Tianyu Zheng; Bin Li; Fen Zuo; et al. (Science Bulletin, 2024)

Potential safety concerns of volatile constituents released from coffee-ground-blended single-use biodegradable drinking straws: A chemical space perspective - Hanke Li; Qi-zhi Su; Jinxin Liang; Hongjian Miao; Zhongming Jiang; Siliang Wu; Ben Dong; Canghao Xie; Dan Li; Tongmei Ma; Xiaoxia Mai; Sheng Chen; et al. (Journal of Hazardous Materials, 2024)

Designed synthesis N-doped sulfonated bifunctional catalyst for efficient 5-hydroxymethylfurfural production: A pyridinic N-triggered proton-shift mechanism at basic sites - Yu Yin; Yabo Qi; Chunhui Ma; Zhenwei Wu; Wei Li; Sha Luo; Shouxin Liu (Fuel, 2024)

A study of the pesticide residues in rapeseeds in China: Levels, distribution and health risk assessment - Qi Guo; Xiaofeng Yue; Xin Qi; Xinyao Feng; Xuefang Wang; Xiaofeng Hu; Fei Ma; Liangxiao Zhang; Peiwu Li; Li Yu (Environmental Research, 2024)

S-scheme towards interfacial charge transfer between POMs and MOFs for efficient visible-light photocatalytic Cr (VI) reduction - Qi Wang; Wanggang Ma; Jianying Qian; Ningyi Li; Chao Zhang; Man Deng; Hao Du (Environmental Pollution, 2024)

Fabrication of nanozyme-thixotropic anionic hydrogel coating with multi-enzyme-mimicking activity for the treatment of fungal keratitis - Depeng Shi; Xia Qi; Li Ma; Lihua Zhao; Shengqian Dou; Yao Wang; Qingjun Zhou; Yongfei Zhang; Chao Yang; Hongwei Wang; Lixin Xie (Chemical Engineering Journal, 2024)

CoTe2/NiTe2 heterojunction embedded in N-doped hollow carbon nanoboxes as high-efficient ORR/OER catalyst for rechargeable zinc-air battery - Mingyang Liu; Qi Li; Xudong Xiao; Xuena Ma; Xiaoqin Xu; Yihang Yin; Bin Zhang; Minghui Ding; Jinlong Zou; Baojiang Jiang (Chemical Engineering Journal, 2024)

Structure-induced interfacial activation convoying the CO-relayed conversion of CO2 to dimethyl carbonate - Shu-Guo Han; Shenghua Zhou; Xiaofang Li; Jianqiang Zhao; Wen-Bo Wei; Lirong Zheng; Dong-Dong Ma; Xin-Tao Wu; Qi-Long Zhu (Chemical Engineering Journal, 2024)

A green large-scale fabrication of cellulose-based multifunctional fluorescent fibers for versatile applications - Changjing Qiu; Fang Peng; Pingping Wu; Xijun Wang; Songnan Hu; Chuanlin Huang; Xingxing Li; Dingfeng Xu; Hui Li; Peng-Cheng Ma; Pan Chen; Haisong Qi (Chemical Engineering Journal, 2024)

Holistic investigation of structural evolution in corn stover lignin under pretreatment with varying γ-valerolactone concentrations - Xiaohong Hu; Ying Xia; Haiyong Wang; Xiuzheng Zhuang; Qiying Liu; Song Li; Qi Zhang; Longlong Ma (Biomass and Bioenergy, 2024)

Multi-dimensional evaluation of four monthly long-term and high-resolution gridded precipitation datasets on the Qinghai-Tibet Plateau - Nan Meng; Yanzheng Yang; Wenchao Qi; Jingyi Zhu; Xuhuan Dai; Ruonan Li; Jinfeng Ma; Hua Zheng (Atmospheric Research, 2024)

Deoxynivalenol Damages Corneal Epithelial Cells and Exacerbates Inflammatory Response in Fungal Keratitis - Qi Shi; QingQing Li; Changlin Wu; Shisi Ma; Chunlan Liang; Xiaoyi Fan; Jingxiang Zhong; Lian Liu (Mycopathologia, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

In-situ synthesis of ZIF-8 on magnetic pineapple leaf biochar as an efficient and reusable adsorbent for methylene blue removal from wastewater - Xiaoxiao Ma; Yutong Li; Yile Du; Shuangli Chen; Yunfan Bai; Lin Li; Chuhua Qi; Pingping Wu; Sijing Zhang (Environmental Science and Pollution Research, 2024)

Enhancing La(III) biosorption and biomineralization with Micromonospora saelicesensis: Involvement of phosphorus and formation of monazite nano-minerals - Ya Zhang; Lili Wang; Xiuming Liu; Chengliang Cao; Jiaqi Yao; Zhouai Ma; Qi Shen; Qiuyu Chen; Jinjuan Liu; Rongpeng Li; Jihong Jiang (Science of The Total Environment, 2024)

Mediation of the JNC/ILC2 pathway in DBP-exacerbated allergic asthma: A molecular toxicological study on neuroimmune positive feedback mechanism - Xiaomin Xie; Yan Li; Biao Yan; Qi Peng; Runming Yao; Qihong Deng; Jinquan Li; Yang Wu; Shaohui Chen; Xu Yang; Ping Ma (Journal of Hazardous Materials, 2024)

3D-printed MoS2/Ni electrodes with excellent electro-catalytic performance and long-term stability for dechlorination of florfenicol - Jianhui Xu; Pengxu Wang; Shenggui Chen; Lei Li; Dan Li; Yunfei Zhang; Qi Wu; Jinhong Fan; Luming Ma (Journal of Environmental Sciences, 2024)

Simultaneous determination of enantiomer residues of metalaxyl and its metabolite metalaxyl acid in animal muscle tissues by chiral liquid chromatography-tandem mass spectrometry - Hao Zhou; Qi Shan; Limin He; Meiyu Zhang; Cheng Zhao; Guangming Zheng; Lichun Li; Feng Xu; Lisha Ma; Yi Yin (Food Chemistry, 2024)

Genetic Composition of the High-Quality Winter Wheat Varieties ‘Xinmai 26’ and ‘Xinmai 45’ - Li-Juan Yang; Jian Ma; Da-Le Zhang; Hai-Feng Yang; Yan-Qi Dong; Zeng-Jun Qi; Meng-Jiao Li; Zhi-Kai Jiang; Hua-Ping Ma (Plant Molecular Biology Reporter, 2024)

PHLDA1 is a P53 target gene involved in P53-mediated cell apoptosis - Xuhong Song; Lulu Zhou; Wenrui Yang; Xinyan Li; Jiazi Ma; Kun Qi; Rui Liang; Meijing Li; Lingzhu Xie; Tin Su; Dongyang Huang; Bin Liang (Molecular and Cellular Biochemistry, 2024)

Lethality level analysis of secondary landslides based on field survey data: a case study of Luding earthquake - Lu Yao; Xia Chaoxu; Ma Siyuan; Qi Wenhua; Nie Gaozhong; Li Huayue (Landslides, 2024)

The trend of allogeneic tendon decellularization: literature review - Yangyang Jin; Qi Sun; Rongxing Ma; Ruifeng Li; Ruiqi Qiao; Jikai Li; Limin Wang; Yongcheng Hu (Cell and Tissue Banking, 2024)

MRPS9-Mediated Regulation of the PI3K/Akt/mTOR Pathway Inhibits Neuron Apoptosis and Protects Ischemic Stroke - Jina Jiang; Tingting Qi; Li Li; Yunzhi Pan; Lijuan Huang; Lijuan Zhu; Dongyang Zhang; Xiaoqing Ma; Yinghui Qin (Journal of Molecular Neuroscience, 2024)

Fluoride promotes the secretion of inflammatory factors in microglia through NLRP3/Caspase-1/GSDMD pathway - Qiuyi Zhang; Tao Li; Ruili Shi; Ruifang Qi; Xiaoqiong Hao; Baohui Ma (Environmental Science and Pollution Research, 2024)

Epidural administration of large dose of opioid μ receptor agonist may impair cardiac functions and myocardial viability via desensitizing transient receptor potential vanilloid 1 - Xiang Ma; Zheng Guo; Mu-Rong Li; Lu Chen; Xing Zhao; Tian-Qi Wang; Tao Sun (Toxicology and Applied Pharmacology, 2024)

The IL-31/TRPV1 pathway mediates allergic asthma exacerbated by DINP dermal exposure in OVA-sensitized Balb/c mice - Qi Peng; Yang Wu; Yan Li; Chan Lu; Runming Yao; Siyuan Hu; Ning Ma; Shaohui Chen; Xu Yang; Ping Ma (Science of The Total Environment, 2024)

Occurrence, seasonal variation and gas/particle partitioning of current used pesticides (CUPs) across 60 °C temperature and 30° latitudes in China - Liang Wang; Gang Cao; Zi-Feng Zhang; Li-Yan Liu; Shi-Ming Jia; Meng-Qi Fu; Wan-Li Ma (Journal of Hazardous Materials, 2024)

Study on optimization of energy consumption and surface quality of ultrasonic vibration-assisted polishing process based on entropy weight method - Chao Zhang; Qi Li; Zhelun Ma; Zixuan Wang; Tianbiao Yu (Journal of Cleaner Production, 2024)

Opportunities for converting waste plastics into petrochemicals: Process design, multi-objective optimization, and omnidirectional techno-economic-society-environment assessment - Xiaobo Chen; Jinqing Zhang; Zhibo Zhang; Zihao Zhang; Xin Zhou; Yaqi Zheng; Ting Wang; Guoliang Li; Ruzhen Ma; Qi Han; Hao Yan; Yibin Liu; et al. (Journal of Cleaner Production, 2024)

Investigation on the failure mechanism of a tunnel entrance high-steep slope with ultra-large wedge blocks based on discrete element method - Huai-sheng Xu; Shao-jun Li; Ding-ping Xu; Xiu-yang Liu; Yue-lin Xia; Guan-qi Wang; Xing-dong Ma; Zheng-jun Zhou (Computers and Geotechnics, 2024)

Crystal defect engineering to construct oxygen vacancies in MXene-derived TiO2 nanocomposites for boosting photocatalytic degradation of 2,4,6-trichlorophenol - Feihong Wang; Qi Zhao; Hongpeng Li; Qiangshun Wu; Luyan Zhang; Yan Li; Liang Qiao; Ye Yuan; Jun Ma; Panpan Wang; Tianming Chen (Chemical Engineering Journal, 2024)

Unravelling structure sensitivity in heterogeneous hydroformylation of aldehyde over Rh - Qi Yang; Pengfei Wang; Chen Li; Benlei Wang; Ying Zheng; Yi Feng; Zidi Miao; Maoshuai Li; Mei-Yan Wang; Shouying Huang; Xinbin Ma (Chemical Engineering Journal, 2024)

Fe/N co-doped magnetic porous hydrochar for chromium(VI) removal in water: Adsorption performance and mechanism investigation - Jianhua Qu; Shuai Shi; Yuhui Li; Ruixin Liu; Qi Hu; Yupeng Zhang; Yifan Wang; Yunqiao Ma; Xiaoyu Hao; Ying Zhang (Bioresource Technology, 2024)

The application of nanopore targeted sequencing for pathogen diagnosis in bronchoalveolar lavage fluid of patients with pneumonia: a prospective multicenter study - Qinqing Lin; Yake Yao; Xi Li; Shanshan Zhang; Huimin Guo; Xiaolong Ma; Wenyu Chen; Chuhui Ru; Limin Wang; Bin Wang; Qiang Ma; Junfei Zhu; et al. (Infectious Diseases, 2024)

Insidious transmission of Mycobacterium tuberculosis in Ordos, China: a molecular epidemiology study - Hailin Sun; Zichun Ma; Fuli Ai; Bing Han; Peng Li; Juan Liu; Yiheng Wu; Yufeng Wang; Bing Li; Dan Qi; Yu Pang (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Identification of pigeon mitochondrial antiviral signaling protein (MAVS) and its role in antiviral innate immunity - Qi Shao; Yawen Li; Feiyu Fu; Pei Zhu; Hengan Wang; Zhaofei Wang; Jingjiao Ma; Yaxian Yan; Yuqiang Cheng; Jianhe Sun (Archives of Virology, 2024)

Effects of VOC emissions from chemical industrial parks on regional O3-PM2.5 compound pollution in the Yangtze River Delta - Li He; Yusen Duan; Yan Zhang; Qi Yu; Juntao Huo; Jia Chen; Huxiong Cui; Yuewu Li; Weichun Ma (Science of The Total Environment, 2024)

Exploring the associations between phthalate exposure and cardiometabolic risk factors clustering among children: The potential mediating role of insulin-resistant-related genes DNA methylation - Jieyu Liu; Jieyun Song; Di Gao; Yanhui Li; Tongjun Guo; Wen Yuan; Manman Chen; Li Chen; Yi Zhang; Qi Ma; Mengjie Cui; Xinli Song; et al. (Journal of Hazardous Materials, 2024)

Laser-ablated acoustofluidics-driven paper devices for controllable chemical engineering in color display applications - Xiong Zhao; Chenyi Cui; Li Ma; Zihan Ding; Junsheng Hou; Yaxuan Xiao; Biwu Liu; Baojin Qi; Jinhua Zhang; Jinjia Wei; Nanjing Hao (Chemical Engineering Journal, 2024)

Symmetrical distribution of P sites on thorn assembled Graphite carbon nitride microtube for photocatalytic conversion of CO2 - Luoming Zhang; Xin Zhao; Mingyang Liu; Qi Li; Yihang Yin; Xuena Ma; Huiquan Gu; Baojiang Jiang (Chemical Engineering Journal, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Study on the Hydrodynamic Performance of the Beam Used in the Antarctic Krill Beam Trawl - Yuyan Li; Zheng Liu; Zhongqiu Wang; Xun Zhang; Lumin Wang; Yu Zhang; Shuo Ma; Guangrui Qi; Yongjin Wang (Fishes, 2023)
The beam trawl is one of the primary operational trawls for Antarctic krill, and its beam provides horizontal expansion support for the trawl net. The hydrodynamic performance of the beam significantly affects the vertical expansion and sinking performance of the trawl, as well as impacts the energy consumption of the fishing vessel. In this study, the beam of the Antarctic krill trawl used on the “Shen Lan” fishing vessel served as a prototype. Three types of beams, cylindrical, airfoil, and elliptical, were designed. The hydrodynamic performances of beams with different shapes at different angles of attack were studied using numerical simulation, and the accuracy of the numerical simulation was validated through the flume test. The results show that the cylindrical beam has a higher drag coefficient and a lower lift coefficient, compared to the airfoil beam and the elliptical beam. Under different angles of attack, the cylindrical beam’s drag coefficient is, on average, 49.54% higher than that of the airfoil beam and 59.74% higher than that of the elliptical beam. Its lift coefficient is 87.79% lower than that of the airfoil beam and 85.06% lower than that of the elliptical beam, respectively. At different angles of attack, the hydrodynamic coefficients of the airfoil beam and the elliptical beam are similar, and their trends, with respect to the angle of attack, are generally consistent. The drag coefficients increase with an increasing angle of attack, while the lift coefficients show a trend of initially increasing and then decreasing with an increasing angle of attack. The absolute values of the lift coefficients for the airfoil beam and the elliptical beam both reach their maximum values at an angle of attack of 45°, with values of 0.703 and 0.473, respectively. Compared to the cylindrical beam, the hydrodynamic performances of the airfoil beam and elliptical beam are superior.

A navigation method for paddy field management based on seedlings coordinate information - Shuanglong Wu; Zhaoguo Chen; Kemoh Bangura; Jun Jiang; Xingang Ma; Jiyu Li; Bin Peng; Xiangbao Meng; Long Qi (Computers and Electronics in Agriculture, 2023)

Occurrence of liquid crystal monomers in indoor and outdoor air particle matters (PM10): Implications for human exposure indoors - Li-Li Yao; Jun-Li Wang; Rong-Fa Xu; Ming Zhu; Yan Ma; Bin Tang; Qi-Yuan Lu; Feng-Shan Cai; Xiao Yan; Jing Zheng; Yun-Jiang Yu (Science of The Total Environment, 2023)

Molecular and optical signatures of photochemical transformation of dissolved organic matter: Nonnegligible role of suspended particulate matter in urban river - Jingyi Hou; Ruochun Zhang; Jinfeng Ge; Chao Ma; Yuanbi Yi; Yulin Qi; Si-Liang Li (Science of The Total Environment, 2023)

Cross-regional scale studies of organochlorine pesticides in air in China: Pollution characteristic, seasonal variation, and gas/particle partitioning - Liang Wang; Gang Cao; Li-Yan Liu; Zi-Feng Zhang; Shi-Ming Jia; Meng-Qi Fu; Wan-Li Ma (Science of The Total Environment, 2023)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

Two new eudesmane sesquiterpenoids with neuroprotective activity from Pogostemon cablin - Qi Zheng; Chuan Ma; Liang Xiong; Cheng Peng; Li Guo; Da-Le Guo; E Zhao; Qin-Mei Zhou; Ou Dai (Phytochemistry Letters, 2023)

Investigation on the catalytic performance of magnetic copper ferrite nanoparticles in the catalytic hydroconversion of Hanglaiwan long flame coal - Yong Gao; Wen-Xian Qin; Jin-Jun Bai; Qi-Yang Zhu; Xia-Long Li; Guang-Hui Liu; Xian-Yong Wei; Yu-Hong Kang; Yan-Jun Li; Xiang-Rong Ma; Zhi-Min Zong (Fuel, 2023)

Simultaneous removal of aflatoxin B1 and zearalenone in vegetable oils by hierarchical fungal mycelia@graphene oxide@Fe3O4 adsorbent - Fei Ma; Qi Guo; Zhaowei Zhang; Xiaoxia Ding; Liangxiao Zhang; Peiwu Li; Li Yu (Food Chemistry, 2023)

Integrated multifunctional nanoplatform for fluorescence detection and inactivation of Staphylococcus aureus - Jing-bo Jiao; Qing Kang; Jiang-li Cao; Shuai-qi Zhang; Chen-jing Ma; Tong Lin; Ze-hui Xiao; Chu-min Zhao; Ting Du; Xin-jun Du; Shuo Wang (Food Chemistry, 2023)

A novel active packaging film containing citronella oil: Preparation, characterization, antimicrobial activity and application in grape preservation - Weijie Zhao; Changcheng Li; Weijia Ma; Ruiwen He; Yan Rong; Shovra Sarker; Qi Liu; Fang Tian (Food Packaging and Shelf Life, 2023)

A quantitative exploration of the interactions and synergistic driving mechanisms between factors affecting regional air quality based on deep learning - Wanning Li; Daoming Ma; Juanlin Fu; Yi Qi; Haiyun Shi; Tianhua Ni (Atmospheric Environment, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Corrigendum: Identifying the wetlands of international importance in Beibu Gulf along the East Asian – Australasian Flyway, based on multiple citizen science datasets - Ningxin Tang; Yanju Ma; Sixin Li; Yizhu Yan; Cheng Cheng; Gang Lu; Fei Li; Liuxuan Lv; Peilin Qin; Hoai Bao Nguyen; Quang Hao Nguyen; Trong Trai Le; et al. (Frontiers in Marine Science, 2023)

Hemalin vaccination modulates the host immune response and reproductive cycle of Haemaphysalis longicornis - Hejia Ma; Jingkai Ai; Yansha La; Xinyuan Zhao; Ankang Zeng; Qi Qin; Shangjiali Feng; Ming Kang; Yali Sun; Jixu Li (Veterinary Parasitology, 2023)

Village clans and rural households' willingness to participate in domestic waste governance: Evidence from China - Li Sheng; Jun-qi Ma (Journal of Cleaner Production, 2023)

Simultaneous enhancement of soil properties along with water-holding and restriction of Pb–Cd mobility in a soil-plant system by the addition of a phosphorus-modified biochar to the soil - Feng Han; Shu-yu An; Lei Liu; Li-qi Ma; Ye Wang; Liu Yang (Journal of Environmental Management, 2023)

The role of primary amines in modified chitosan to enhance the aldol condensation of biomass-derived carbonyl compounds - Xuelai Zhao; Shan Feng; Song Li; Yuzhen Hu; Wuyu Wang; Xinghua Zhang; Qi Zhang; Yubao Chen; Jianguo Liu; Longlong Ma (Fuel, 2023)

Zebrafish nos2a benefits bacterial proliferation via suppressing ROS and inducing NO production to impair the expressions of inflammatory cytokines and antibacterial genes - Si Yao Zheng; Xinbin Shao; Zhitao Qi; Maocang Yan; Min Hui Tao; Xiao Man Wu; Lining Zhang; Jianzhong Ma; An Li; Ming Xian Chang (Fish & Shellfish Immunology, 2023)

A pH-responsive nanoplatform with aggregation-induced emission features for lipid droplet imaging in atherosclerosis - Di Ma; Weihua Zhuang; Qi Liu; Jingruo Chen; Chengming Li; Shufen Li; Mao Chen (Chemical Engineering Journal, 2023)

Effects of rainfall pattern and soil surface roughness on surface–subsurface hydrological response and particle size distribution of red soil slope - Yichun Ma; Yaojun Liu; Liang Tian; Yifan Yang; Yu Long; Ming Lei; Ziwei Zhang; Qi Li; Huade Zhu; Zhongwu Li (CATENA, 2023)

Targeted control of soil erosion through selective regulation of Eleocharis yokoscensis using mixed endophytes - Qifeng Gao; Xiao Xiao; Ting Liu; Zhong Ren; Wei Ren; Yunya Zhan; Wenqian Wang; Weiran Feng; Li Ma; Le Qi; Zixian Zhang; Xubiao Luo; et al. (CATENA, 2023)

Bacterial metabolism-triggered-chemiluminescence-based point-of-care testing platform for sensitive detection and photothermal inactivation of Staphylococcus aureus - Xinghui Yu; Yongqiang Ma; Siyuan Liu; Chunchun Qi; Weiqi Zhang; Wen Xiang; Zhaoxian Li; Kai Yang; Shaoxian Duan; Xinrao Du; Jian Yu; Yan Xie; et al. (Analytica Chimica Acta, 2023)

Spatial patterns and recent temporal trends in global transpiration modelled using eco-evolutionary optimality - Shijie Li; Guojie Wang; Chenxia Zhu; Marco Hannemann; Rafael Poyatos; Jiao Lu; Ji Li; Waheed Ullah; Daniel Fiifi Tawia Hagan; Almudena García-García; Yi Liu; Qi Liu; et al. (Agricultural and Forest Meteorology, 2023)

Novel insights into DNA damage repair defects in HPV-positive head and neck squamous cell carcinoma: from the molecular basis to therapeutic opportunities - Qi Liu; Nan Zuo; Xinghan Li; Yongqiang Deng; Lanlan Wei; Lin Ma (Genome Instability & Disease, 2023)

Gravity-driven membrane system treating heavy metals-containing secondary effluent: Improved removal of heavy metals and mechanism - Xiaobin Ma; Yanrui Wang; Le Tong; Jiaoying Luo; Rui Chen; Yuanxin Wang; Xishou Guo; Jinlong Wang; Zhiwei Zhou; Jingyao Qi; Guibai Li; Heng Liang; et al. (Chemosphere, 2023)

Multi-objective optimization of hydrogen production system based on the combined supercritical cycle and gas turbine plant - Z. Li; Xinrui Qi; Mingyang Huang; Zhenjun Ma; Orest Kochan; Chunsheng Yang; Patrick Siarry (Chemosphere, 2023)

HVT-vectored H7 vaccine protects chickens from lethal infection with the highly pathogenic H7N9 Avian inﬂuenza virus - Yi-qun Chen; Guan-ming Su; Jia-hao Zhang; Bo Li; Kai-xiong Ma; Xu Zhang; Li-hong Huang; Ming Liao; Wen-bao Qi (Veterinary Microbiology, 2023)

The associations of ambient fine particles with tuberculosis incidence and the modification effects of ambient temperature: A nationwide time-series study in China - Jia Wang; Wen Li; Wenzhong Huang; Yuan Gao; Yanming Liu; Qian Hui Teng; Qi Zhao; Mingting Chen; Yuming Guo; Wei Ma (Journal of Hazardous Materials, 2023)

Mediation of endoplasmic reticulum stress and NF-κB signaling pathway in DINP-exacerbated allergic asthma: A toxicological study with Balb/c mice - Fan Lei; Yang Wu; Chongyao Li; Biao Yan; Shaohui Chen; Qi Peng; Xu Yang; Ping Ma (Journal of Hazardous Materials, 2023)

Application of functionalized biochar for adsorption of organic pollutants from environmental media: Synthesis strategies, removal mechanisms and outlook - Jianhua Qu; Qingjuan Meng; Wei Peng; Jiajia Shi; Zonghao Dong; Zhuoran Li; Qi Hu; Guangshan Zhang; Lei Wang; Shouyi Ma; Ying Zhang (Journal of Cleaner Production, 2023)

Pyrolysis mechanisms of the main model compounds of enteromorpha prolifera to produce syngas - Hao Qi; Qirong Yang; Xinru Ma; Mengyu Wan; Zijun Zhang; Haoxi Ben; Lianghuan Wei; Zhaoying Li (Journal of Cleaner Production, 2023)

Improving the biological activity, functional properties, and emulsion stability of soybean meal hydrolysate via covalent conjugation with polyphenol - Xiaoying Zhang; Chengpeng Yin; Jiaqi Hao; Danhua Ma; Ziyu Li; Yang Li; Baokun Qi (Food Chemistry, 2023)

Antioxidant properties of lipid concomitants in edible oils: A review - Gaiqin Ma; Yuanyuan Wang; Yuefan Li; Lingyan Zhang; Yuan Gao; Qi Li; Xiuzhu Yu (Food Chemistry, 2023)

Chitosan/carbon dots modified cellulose nanofibrils/ZIF-8 gel bead: An effective and easily separable photocatalytic adsorbent for Cr(VI) removal - Xuefeng Zhang; Jiayu Ouyang; Xinmiao Qi; Ze Li; Qiang Ma; Xin Guo; Shanshan Jia (Chemical Engineering Journal, 2023)

Deterioration of fresh sandstone caused by experimental freeze-thaw weathering - Changqing Qi; Qingpeng Li; Xiaofan Ma; Weichao Guo (Cold Regions Science and Technology, 2023)

A major QTL simultaneously increases the number of spikelets per spike and thousand-kernel weight in a wheat line - Conghao Zhao; Jieguang Zhou; Cong Li; Jianing You; Yanling Liu; Huaping Tang; Mei Deng; Qiang Xu; Yazhou Zhang; Qiantao Jiang; Guoyue Chen; Pengfei Qi; et al. (Theoretical and Applied Genetics, 2023)

GABAergic Neurons in the Nucleus Accumbens are Involved in the General Anesthesia Effect of Propofol - Jing Yan; Bei-Ning Hang; Lin-Hui Ma; Jia-Tao Lin; Yue Zhou; Xin-Hao Jiao; Ying-Xuan Yuan; Ke-Jie Shao; Le-Meng Zhang; Qi Xue; Zi-Yi Li; Hong-Xing Zhang; et al. (Molecular Neurobiology, 2023)

Wuzi Yanzong Pill relieves MPTP-induced motor dysfunction and neuron loss by inhibiting NLRP3 inflammasome-mediated neuroinflammation - Tao Pan; Qi Xiao; Hui-Jie Fan; Lei Xu; Shao-Chen Qin; Li-Xia Yang; Xiao-ming Jin; Bao-Guo Xiao; Bo Zhang; Cun-Gen Ma; Zhi Chai (Metabolic Brain Disease, 2023)

Spatiotemporal distribution, sources apportionment and ecological risks of PAHs: a study in the Wuhan section of the Yangtze River - Yulin Chen; Ranran Song; Ping Li; Yile Wang; Yang Tan; Yongfei Ma; Lie Yang; Li Wu; Zhenjie Du; Xuebin Qi; Zulin Zhang (Environmental Geochemistry and Health, 2023)

Identifying the wetlands of international importance in Beibu Gulf along the East Asian – Australasian Flyway, based on multiple citizen science datasets - Ningxin Tang; Yanju Ma; Sixin Li; Yizhu Yan; Cheng Cheng; Gang Lu; Fei Li; Liuxuan Lv; Peilin Qin; Hoai Bao Nguyen; Quang Hao Nguyen; Trong Trai Le; et al. (Frontiers in Marine Science, 2023)
The Beibu Gulf (Gulf of Tonkin, Vinh Bac Bo in Vietnamese), located midway along the East Asian-Australasian Flyway (EAAF), is a critical stopover and wintering region for migratory waterbirds. This transboundary coastal region, spanning between China and Vietnam, harbors diverse wetland habitats that provide refuge to waterbird species, including highly threatened species such as the spoon-billed sandpiper (CR) and the black-faced spoonbill (EN). However, the scarcity of comprehensive assessments regarding waterbird abundances, distribution, key wetland habitats, and regional threats hinders our understanding of its conservation significance at the flyway level. Further research is needed to address these knowledge gaps and facilitate effective conservation efforts in the Beibu Gulf. By synthesizing accessible citizen science datasets and published records from wetland sites in south China and northeast Vietnam, we concluded that at least 97 waterbird species used the Gulf’s wetlands during their annual cycle. Among surveys conducted from 2014 to 2022, 5 and 11 waterbird species were considered as first and second class protected species under the National Key Protected Wild Animal List in China; 2 species were listed as Critically Endangered on the IUCN Red List, 4 as Endangered and 2 as Vulnerable, underlying the critical importance of the Beibu Gulf for the survival of these species. Our study identified 25 sites in the Beibu Gulf that met the criteria for designation as internationally important wetlands. Alarmingly, less than a quarter (n = 5, or 20%) of these sites benefit from national or international protection. Localized threats, including aquatic resource harvesting, hunting, and aquaculture/fisheries, were widespread in the region. This study provides a crucial scientific baseline for continued waterbird monitoring, site prioritization, and the development of effective habitat management plans to conserve vital coastal wetland habitats in the Beibu Gulf in China and Vietnam.

Transcriptome Sequencing Analysis of Sex-Related Genes in the Gonads of Mytilus unguiculatus - Yanwen Ma; Yingying Ye; Ronghui Yao; Pengzhi Qi; Jiji Li (Fishes, 2023)
In the cultivation of Mytilus unguiculatus, the broodstock are shade-dried to stimulate sperm and egg production. To identify the functional genes affecting gonad development in M. unguiculatus, the transcriptome of gonads in mussels stimulated by shade-drying and those not stimulated were compared. Differential gene expression analysis revealed that there were 22 differentially expressed genes (DEGs) in the testis and 70 DEGs in the ovary among the experimental groups. KEGG enrichment analysis identified a total of 11 pathways that might be related to environmental stimuli affecting gonadal development. Nicotinic acetylcholine receptors (AChRs), the cholecystokinin A receptor (CCKAR), hypocretin (orexin) receptor 2 (HCRTR2), and gamma-aminobutyric acid type B receptor (GABBR) were highly expressed in the neuroactive ligand-receptor interaction pathway, indicating that these genes might be involved in the transduction of environmental information that stimulates gonadal development. Meanwhile, nuclear receptor co-repressor 2 (NCoR2) was highly expressed in the notch signaling pathway, indicating that NCoR2 might be involved in the regulation of gonad development. To validate the transcriptome data, we selected five DEGs in the KEGG signaling pathway, including AChRs, CCKAR, HCRTR2, GABAB, and NCoR2, for real-time quantitative PCR (RT-qPCR), which produced results consistent with the RNA-Seq data. The transcriptome analysis and gene pathway identification in this study have enhanced our comprehension of the reproductive mechanisms in M. unguiculatus.

Irrigation leads to new Se-toxicity paddy fields in and around typical Se-toxicity area - Yuanzhe Ma; Fei Zhou; Dasong Yu; Nanchun Zhang; Mingxing Qi; Yanan Li; Fuyong Wu; Dongli Liang (Science of The Total Environment, 2023)

A small extent of seawater intrusion significantly enhanced Cd uptake by rice in coastal paddy fields - Wenting Chi; Guojun Chen; Shiwen Hu; Xiaomin Li; Kuan Cheng; Qi Wang; Bingqing Xia; Yang Yang; Yibing Ma; Tongxu Liu (Journal of Hazardous Materials, 2023)

A reliable ecological vulnerability approach based on the construction of optimal evaluation systems and evolutionary tracking models - Dan He; Kang Hou; Xu Xiang Li; Si Qi Wu; Li Xia Ma (Journal of Cleaner Production, 2023)

Ascorbic acid-mediated in situ growth of gold nanostars for photothermal immunoassay of ochratoxin A - Yiwen Wang; Longyingzi Xie; Lanrui Ma; Qi Wu; Zhixia Li; Yanlin Liu; Qiyang Zhao; Yaohai Zhang; Bining Jiao; Yue He (Food Chemistry, 2023)

Stabilizing formamidinium lead triiodide α-phase with diamine cations for perovskite solar cells - Xinxin Li; Changzeng Ding; Li Yin; Lianping Zhang; Yongzhen Yang; Lingpeng Yan; Chang-Qi Ma (Chemical Engineering Journal, 2023)

An anaerobic dynamic membrane bioreactor (AnDMBR) system enhanced the biogas conversion efficiency and stability of mesophilic codigestion with waste activated sludge and food waste - Bao-Shan Xing; Yi Zhang; Rui-Qi Zhang; Jing Ma; Xiang-Lin Chang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Chemical Engineering Journal, 2023)

Highly sensitive, wide-pressure and low-frequency characterized pressure sensor based on piezoresistive-piezoelectric coupling effects in porous wood - Jingjing Luo; Feihua Liu; Ao Yin; Xue Qi; Jiang Liu; Zhongqi Ren; Shiqiang Zhou; Yuxin Wang; Yang Ye; Qingzhi Ma; Junjun Zhu; Kang Li; et al. (Carbohydrate Polymers, 2023)

Improved biotransformation of lignin-valorized vanillin into vanillylamine in a sustainable bioreaction medium - Qi Li; Ruiying Gao; Yucheng Li; Bo Fan; Cuiluan Ma; Yu-Cai He (Bioresource Technology, 2023)

A promising QTL QSns.sau-MC-3D.1 likely superior to WAPO1 for the number of spikelets per spike of wheat shows no adverse effects on yield-related traits - Jieguang Zhou; Wei Li; Yaoyao Yang; Xinlin Xie; Jiajun Liu; Yanling Liu; Huaping Tang; Mei Deng; Qiang Xu; Qiantao Jiang; Guoyue Chen; Pengfei Qi; et al. (Theoretical and Applied Genetics, 2023)

DNA methylation age acceleration contributes to the development and prediction of non-alcoholic fatty liver disease - Mingfeng Xia; Wenran Li; Huandong Lin; Hailuan Zeng; Shuai Ma; Qi Wu; Hui Ma; Xiaoming Li; Baishen Pan; Jian Gao; Yu Hu; Yun Liu; et al. (GeroScience, 2023)
Non-alcoholic fatty liver disease (NAFLD) is prevalent in the aging society. Despite body weight reduction, the prevalence of NAFLD has been increasing with aging for unknown reasons. Here, we investigate the association of DNA methylation age acceleration, a hallmark of aging, with risk of NAFLD. Genome-wide DNA methylation profiles were measured in 95 participants who developed type 2 diabetes during 4-year follow-up, and 356 randomly sampled participants from Shanghai Changfeng Study. DNA methylation age was calculated using the Horvath’s method, and liver fat content (LFC) was measured using a quantitative ultrasound method. Subjects with highest tertile of DNA methylation age acceleration (≥ 9.5 years) had significantly higher LFC (7.2% vs 3.1%, P = 0.008) but lower body fat percentage (29.7% vs 33.0%, P = 0.032) than those with lowest tertile of DNA methylation age acceleration (< 4.0 years). After adjustment for age, sex, alcohol drinking, cigarette smoking, BMI, waist circumference, and different type blood cell counts, the risk of NAFLD was still significantly increased in the highest tertile group (OR, 4.55; 95% CI, 1.06–19.61). Even in subjects with similar LFC at baseline, DNA methylation age acceleration was associated with higher increase in LFC (4.0 ± 10.7% vs 0.9 ± 9.5%, P = 0.004) after a median of 4-year follow-up. Further analysis found that 6 CpGs of Horvath age predictors were associated with longitudinal changes in LFC after multivariate adjustment and located on genes that might lead to fat redistribution from peripheral adipose to liver. Combination of the key CpG methylation related to liver fat content with conventional risk factors improves the performance for NAFLD prediction. Graphical Abstract

Sulfoaluminate cement-modified straw biochar as a soil amendment to inhibit Pb-Cd mobility in the soil-romaine lettuce system - Feng Han; Shu-yu An; Lei Liu; Ye Wang; Li-qi Ma; Liu Yang (Chemosphere, 2023)

Syringin alleviates hepatic fibrosis by enhancing autophagic flux and attenuating ER stress-TRIB3/SMAD3 in diabetic mice - Zhewen Deng; Chaoxing Ren; Chenglun Tang; Shuang Chen; Jiaqi Li; Jingxun Wei; Qi Zhang; Bo Ma (Tissue and Cell, 2023)

The Tartary buckwheat bHLH gene ALCATRAZ contributes to silique dehiscence in Arabidopsis thaliana - Wenjun Sun; Ying Chen; Jing Zeng; Chenglei Li; Min Yao; Moyang Liu; Zhaotang Ma; Li Huang; Jun Yan; Junyi Zhan; Hui Chen; Tongliang Bu; et al. (Plant Science, 2023)

Internal exposure risk based on urinary metabolites of PAHs of occupation and non-occupation populations around a non-ferrous metal smelting plant - Bizhi Wu; Meiqing Lin; Hailing Li; Yingjun Wu; Mengdie Qi; Jian Tang; Shengtao Ma; Guiying Li; Taicheng An (Journal of Hazardous Materials, 2023)

Decoupling analysis to assess the impact of land use patterns on carbon emissions: A case study in the Yellow River Delta efficient eco-economic zone, China - Qian Wang; Chuan-hao Yang; Ma-li Wang; Lin Zhao; Yu-chen Zhao; Qi-peng Zhang; Chun-yan Zhang (Journal of Cleaner Production, 2023)

One-step leaching mechanism for total elemental recovery from spent lithium-ion batteries utilizing ethylene diamine tetraacetic acid - Fanyun Su; Qi Meng; Xiangyang Zhou; Xiaojian Liu; Juan Yang; Jingjing Tang; Wan Yang; Penghui Cao; Zhenxiao Li; Hui Wang; Yayun Ma (Journal of Environmental Chemical Engineering, 2023)

Analytical study on heavy metal output fluxes and source apportionment of a non-ferrous smelter in southwest China - Chenchen Li; Peng Dong; Jin Yan; Rui Gong; Qi Meng; Jun Yao; Hanjing Yu; Yaoqiang Ma; Bang Liu; Ruosong Xie (Environmental Pollution, 2023)

One-pot preparation of layered double oxides-engineered biochar for the sustained removal of tetracycline in water - Jiayi Tang; Yongfei Ma; Zhikang Deng; Ping Li; Xuebin Qi; Zulin Zhang (Bioresource Technology, 2023)

Significantly enhanced enzymatic hydrolysis of waste rice hull through a novel surfactant-based deep eutectic solvent pretreatment - Zheng-Yu Tang; Lei Li; Wei Tang; Jia-Wei Shen; Qi-Zhen Yang; Cuiluan Ma; Yu-Cai He (Bioresource Technology, 2023)

Linkage between spruce forest decline and cloud cover increase in the Qilian Mountains of the northeastern Tibetan Plateau - Jing Yang; Baowei Zhao; Jiacheng Zheng; Qi Zhang; Yan Li; Fuhai Ma; Ouya Fang (Trees, 2023)

Adaptation mechanisms of the soil microbial community under stoichiometric imbalances and nutrient-limiting conditions in a subtropical nitrogen-saturated forest - Lingjun Qiu; Yunjie Li; Qi Zhong; Wei Ma; Yuxiao Kuang; Shixing Zhou; Gang Chen; Jiulong Xie; Hongling Hu; Yuqin Chen; Lihua Tu (Plant and Soil, 2023)

Ground subsidence mechanism of a filling mine with a steeply inclined ore body - Guang Li; Shuai-qi Liu; Feng-shan Ma; Jie Guo; Xin Hui (Journal of Mountain Science, 2023)

Occurrence, distribution, and risk assessment of quinolone antibiotics in municipal sewage sludges throughout China - Fan Meng; Shaojing Sun; Jialu Geng; Lixin Ma; Jinpan Jiang; Bo Li; Stephen Dauda Yabo; Lu Lu; Donglei Fu; Jimin Shen; Hong Qi (Journal of Hazardous Materials, 2023)

Insights into the modulation of the multi-scale structure of glutelin on the textural properties of reconstituted rice - Li-Shuang Wang; Xiao-Shuai Yu; Ke-Xin Wang; Jin-Jie Huo; Xiao-Qi Ma; Yu-Min Duan; Zhi-Gang Xiao; Peng Wang (Innovative Food Science & Emerging Technologies, 2023)

The release analysis of As and Cr metals in lead-zinc smelting slag: Mineralogical analysis, bioavailability and leachability analysis - Yaoqiang Ma; ChenChen Li; Jin Yan; Hanjing Yu; Huiying Kan; Wanquan Yu; Xinyu Zhou; Qi Meng; Peng Dong (Environmental Research, 2023)

Aflatoxin B1 disrupts testicular development via the cell cycle-related Ras/PI3K/Akt signaling in mice and pig - Fa-Li Zhang; Hao-Hai Ma; Pei-Yu Dong; Zheng-Ning Yuan; Shu-Er Zhang; Ai-Hong Zhao; Huan-Qi Liu; Massimo De Felici; Wei Shen; Xi-Feng Zhang (Environmental Pollution, 2023)

Formaldehyde exacerbates asthma in mice through the potentiation of HIF-1α-mediated pro-inflammatory responses in pulmonary macrophages - Huijuan Ma; Qi Shu; Peiyao Wang; Ruilin Qin; Sijia Li; Huan Xu (Chemico-Biological Interactions, 2023)

Identification of quantitative trait loci and candidate genes for seed folate content in soybean - Kwadwo Gyapong Agyenim-Boateng; Shengrui Zhang; Rongzhe Gu; Shibi Zhang; Jie Qi; Muhammad Azam; Caiyou Ma; Yecheng Li; Yue Feng; Yitian Liu; Jing Li; Bin Li; et al. (Theoretical and Applied Genetics, 2023)

Analysis of signal-to-noise ratio retrieved from multi-GNSS satellite data of land surface reflections - Qi Liu; Weiqiang Li; Shuangcheng Zhang; Yang Nan; Jilun Peng; Zhongmin Ma (GPS Solutions, 2023)

Characteristics of antibiotic resistance genes and microbial community distribution in Wanfeng Lake, upper Pearl River, China - Yuntao Zhang; Jiang Li; Tianyu Wu; Kai Ma; Zhentao Cheng; Qianwen Yi; Yongheng Dai; Bin Wang; Yu Chen; Bin Wang; Xia Hu; Aijiang Yang; et al. (Environmental Science and Pollution Research, 2023)

Identification of metabolites from edible mushroom Morchella sextelata and their biological evaluation - De-Xian Li; Xia Cheng; Fo-Pei Ma; Jie-Yu Chen; Yi-Ping Chen; Xiao-Shan Zhao; Qi Luo (Natural Product Research, 2023)

Manganese indicates root decomposition rates across soil layer, root order, and tree species: Evidence from a subtropical forest - Guantao Chen; Yu Sun; Yuqin Chen; Wei Ma; Qi Zhong; Yunjie Li; Lingjun Qiu; Shixing Zhou; Gang Chen; Jiulong Xie; Lihua Tu (Soil Biology and Biochemistry, 2023)

Corrigendum to “Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China” [Sci. Total Environ. 857 (2023) 159337] - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Removal of antibiotic resistant bacteria and genes by nanoscale zero-valent iron activated persulfate: Implication for the contribution of pH decrease - Chun-shuang Zhou; Guang-li Cao; Xiu-Kun Wu; Bing-feng Liu; Qing-Yue Qi; Wan-Li Ma (Journal of Hazardous Materials, 2023)

Synthesis of novel adsorbent S-SiO2@Fe3O4 based on strong bonding of S-O-Se for selenium removal in water - Chang-Xian Zhao; Xin-Peng Ma; Xue-Lei Duan; Qi Guo; Sheng-Li Niu; Wen-Jing Zhou; Yuan-Ming Cao; Chun-Gang Yuan (Journal of Environmental Chemical Engineering, 2023)

Improved catalytic oxidation of propane over phosphate-modified Pd/Al2O3-TiO2 catalyst - Peiyuan Liang; Lina Wang; Qi Wang; Baogang Zhao; Yunhe Li; Yanming Ma; Yi Wei; Tianjun Sun (Journal of Environmental Chemical Engineering, 2023)

The effect of methanol atmosphere and/or H-ZSM-5 catalyst on the thermal upgrading of volatiles generated from Hami lignite pyrolysis - Yun-xin Ma; Yue-lun Wang; Xu Yan; Gui-gui Zhan; Wen-Qi Li; Xue-chun Zhang; Jing-pei Cao (Fuel, 2023)

Synthesized alkyl ferulates with different chain lengths inhibited the formation of lipid oxidation products in soybean oil during deep frying - Jia Chen; Lingyan Zhang; Peng Zhao; Gaiqin Ma; Qi Li; Xiuzhu Yu (Food Chemistry, 2023)

Degradation of aflatoxins in apple juice by pulsed light and the analysis of their degradation products - Lige Qi; Yali Ma; Rui Cai; Yu Li; Ruinan Wang; Tianli Yue; Yahong Yuan; Zhenpeng Gao; Zhouli Wang (Food Control, 2023)

Characterization of volatile organic compounds in food contact paperboards and elucidation of their potential origins from the perspective of the raw materials - Hanke Li; Lichang Chen; Xuefeng Wu; Siliang Wu; Qi-zhi Su; Ben Dong; Dan Li; Tongmei Ma; Huaining Zhong; Xiaohui Wang; Jianguo Zheng; Cristina Nerín (Food Packaging and Shelf Life, 2023)

Prediction of ground-borne vibration from random traffic flow and road roughness: Theoretical model and experimental validation - Zhe Li; Yanmei Cao; Meng Ma; Qi Xiang (Engineering Structures, 2023)

Two–dimensional metal–organic framework nanosheets: An efficient two–electron oxygen reduction reaction electrocatalyst for boosting cathodic luminol electrochemiluminescence - Chulei Zhao; Chaoyun Ma; Fuping Zhang; Wenjun Li; Chenglin Hong; Yu Qi (Chemical Engineering Journal, 2023)

Whole-genome sequencing enables molecular dissection and candidate gene identification of the rust resistance gene R12 in sunflower (Helianthus annuus L.) - G. J. Ma; Z. I. Talukder; Q. J. Song; X. H. Li; L. L. Qi (Theoretical and Applied Genetics, 2023)

Diets, Gut Microbiota and Metabolites - Yilian Liu; Wanglei Zhong; Xiao Li; Feng Shen; Xiaonan Ma; Qi Yang; Shangyu Hong; Yan Sun (Phenomics, 2023)

Dissecting SEPALLATA3 Splicing Variant Functions During Arabidopsis Vegetative Growth by amiRNA Technology - Yan-Qin Ma; Zuo-Qian Pu; Qi Meng; Xiao-Min Tan; Liu Yang; Kai-Li Zhang; Ye-Ye Ma; Xuan Huang; Zi-Qin Xu (Journal of Plant Growth Regulation, 2023)

Upregulation of glycolytic enzyme PFKFB3 by deubiquitinase OTUD4 promotes cardiac fibrosis post myocardial infarction - Feizuo Wang; Xiaojian Yin; Yuan-Ming Fan; Xinyao Zhang; Chao Ma; Keke Jia; Wei Zhou; Zongxiang Tang; Lian-Wen Qi; Jia Li (Journal of Molecular Medicine, 2023)
Metabolic dysregulations have emerged as a major mediator of cardiovascular disorders and fibrotic diseases. Metabolic reprogramming contributes a lot to cardiac fibroblast activation and cardiac fibrosis post-myocardial infarction (MI), yet the mechanism remains incompletely understood. Our work aimed to determine whether or not glycolytic reprogramming, regulated by phosphofructokinase-2/fructose-2,6-bisphosphatase 3 (PFKFB3), is a therapeutic target for alleviating post-MI cardiac fibrosis. Here, we showed that cardiac fibroblasts displayed cell energy phenotype toward augmented glycolysis in response to transforming growth factor-beta 1 (TGF-β1), evidenced by significant extracellular acidification rate (ECAR) increase and lactate accumulation. The expression of glycolytic enzyme PFKFB3, a master activator of glycolysis, was up-regulated in TGF-β1-treated cardiac fibroblasts and in cardiac fibroblasts of post-MI mice. Pharmacological inhibition of PFKFB3 by 3PO diminished TGF-β1-mediated profibrotic phenotypes, attenuated cardiac fibrosis, and preserved cardiac functions in post-MI mice. Meanwhile, the genetic inhibition of PFKFB3 decreased the cardiac fibroblast activation and reversed the differentiated phenotypes in vitro and in vivo. Mechanistically, we identified deubiquitinase OTUD4 as a new binding protein of PFKFB3, and their interaction blocked PFKFB3 degradation via OTUD4-mediated deubiquitylation. Taken together, this work characterized a key role for PFKFB3 in cardiac fibroblast activation and suggested that inhibiting PFKFB3-involved glycolysis is an alternative way to alleviate post-MI cardiac fibrosis. Key messages PFKFB3, a master activator of glycolysis, was highly expressed in ischemic cardiac fibroblasts to enhance cardiac fibrosis The deubiquitinase OTUD4 was identified as a new binding protein of PFKFB3 TGF-β1 blunted the ubiquitination-mediated degradation of PFKFB3 via OTUD4-mediated deubiquitylation Blockade of PFKFB3 contributed to ameliorating ischemia-induced cardiac fibrosis

Boundary-to-solution mapping for groundwater flows in a Toth basin - Jingwei Sun; Jun Li; Yonghong Hao; Cuiting Qi; Chunmei Ma; Huazhi Sun; Negash Begashaw; Gurcan Comert; Yi Sun; Qi Wang (Advances in Water Resources, 2023)

Tectonic and climate controls on river terrace formation on the northeastern Tibetan Plateau: Evidence from a terrace record of the Huangshui River - Zhenhua Ma; Tingjiang Peng; Zhantao Feng; Xiaomiao Li; Chunhui Song; Qi Wang; Wanxin Tian; Xiaoyan Zhao (Quaternary International, 2023)

Tannic acid exerts antifungal activity in vitro and in vivo against Alternaria alternata causing postharvest rot on apple fruit - Haixia Wang; Lin Fu; Chunli Li; Xinlu Zhang; Kpadonou Essedolo Narcisse; Haishi Qi; Chuanyu Han; Xiangyu Wang; Hongbin Ma; Chunyu Zhu; Fangliang Zheng (Physiological and Molecular Plant Pathology, 2023)

Remediation of atrazine contaminated soil by microwave activated persulfate system: Performance, mechanism and DFT calculation - Jianhua Qu; Ruixin Liu; Xuewei Bi; Zhuoran Li; Kaige Li; Qi Hu; Xinru Zhang; Guangshan Zhang; Shouyi Ma; Ying Zhang (Journal of Cleaner Production, 2023)

Mesoporous zeolite Beta supported Ni nanoparticles for the catalytic hydroconversion of extraction portion from Jinjitan subbituminous coal to cycloalkanes - Juan Gao; Xian-Yong Wei; Yu-Hong Kang; Xiao-Qi Zhang; Ai-Min Wang; Xia-Long Li; Yong Gao; Guang-Hui Liu; Tao Chen; Yan-Jun Li; Xiang-Rong Ma; Jin-Jun Bai; et al. (Fuel, 2023)

Measured and simulated effects of residue removal and amelioration practices in no-till irrigated corn (Zea mays L.) - Lidong Li; Liwang Ma; Zhiming Qi; Quanxiao Fang; R. Daren Harmel; Marty R. Schmer; Virginia L. Jin (European Journal of Agronomy, 2023)

Viscosity-triggered near-infrared fluorescence nanoprobe for in vivo non-invasive diagnosis of cancer - Wen-Juan Fu; Jian Ting Li; Wen Hui Qian; Xiang Ying Zhang; Dan Dan Ma; Yu Ting Wang; Qi Jia Zhang; Dong Zhu (Chemical Engineering Journal, 2023)

Decay function and damage strain model of fresh sandstone subjected to freeze–thaw cycles - Changqing Qi; Weichao Guo; Qingpeng Li; Xiaofan Ma (Bulletin of Engineering Geology and the Environment, 2023)

Accumulation of Intracellular Ferrous Iron in Inflammatory-Activated Macrophages - Huijuan Ma; Qi Shu; Dan Li; Tingqian Wang; Linyi Li; Xiaodong Song; Kaiyan Lou; Huan Xu (Biological Trace Element Research, 2023)

Contamination characteristics, spatial distribution and ecological-health risk assessment of legacy and current-use pesticides: a case study in the Beibu Gulf - Li Zhang; Jiaxin Ma; Peipei Liu; Anxiang Qi; Haiyan Jin; Renming Jia; Zhenming Zheng; Cheng Yan; Minghong Cai (Frontiers in Marine Science, 2023)
With the prohibition of conventional organochlorine pesticides (OCPs), the extensive use and continuous release of current-use pesticides (CUPs), such as organic amine pesticides (OAPs) and organophosphate pesticides (OPPs), in agriculture and mariculture activities have raised global attention. In this study, the occurrence and distribution of 36 pesticides from above 3 categories were investigated in seawater and sediment in Beibu Gulf, a typical subtropical agricultural and maricultrual zone. Results showed that pesticides were widely present in this region with the total concentration ranging from 0.36 to 21.07 ng/L in seawater and from 0.02 to 9.73 ng/g dw in sediment. OAPs and OPPs were the most abundant categories contributing 74% and 66% to the total pesticides burden in seawater and sediment, respectively, revealing the current-use pesticides as substitutes of legacy organochlorine pesticides (OCPs) were mainly used in surrounding areas. For both seawater and surface sediment, the spatial distribution of pesticides concentrations showed generally seaward decreasing trends, suggesting that anthropogenic activities at coastal areas have an important impact on pesticides pollution. Source identification indicated OCPs in some seawater samples might be from mixture of antifouling paint and dicofol usage, while history residues are main sources of OCPs in sediment. OAPs, especially for cyflufenamid and kresoxim-methyl, mainly come from agricultral and maricultural sewage input, and OPPs were speculated from currency transportation from surrounding areas. Ecological risk assessment showed that OPPs posed moderate to even high risks in most seawater sites. It appears that crustaceans are the most sensitive trophic species to OPPs among aquatic organisms, followed by fish. According to the results of health risks proposed by the major aquatic products in Beibu Gulf (fish and shrimp), the selected pesticides pose no health risk to humans. Nevertheless, OCPs made the highest contribution to the total HQ values. Comprehensively considering the evaluation results of both ecological and health risks, more attention should be given on OPPs and OCPs pollution in the Beibu Gulf.

Microplastics in household fecal sewage treatment facilities of rural China - Xuan Zhang; Qingge Feng; Xiaowei Li; Li Guo; Dachao Ma; Xiaodie Cheng; Yuan Qi (Journal of Hazardous Materials, 2023)

Understanding the inter-city causality and regional transport of atmospheric PM2.5 pollution in winter in the Harbin-Changchun megalopolis in China: A perspective from local and regional - Bo Li; Xiaofei Shi; Jinpan Jiang; Lu Lu; Li-xin Ma; Wei Zhang; Kun Wang; Hong Qi (Environmental Research, 2023)

Drivers of 2015–2021 trends in cold winter surface PM2.5 in the Harbin-Changchun megalopolis in China: Meteorology vs. anthropogenic emission - Bo Li; Lu Lu; Xiaofei Shi; Lixin Ma; Jin-Pan Jiang; Stephen Dauda Yabo; Kun Wang; Hong Qi (Atmospheric Research, 2023)

Identification of a suppressor for the wheat stripe rust resistance gene Yr81 in Chinese wheat landrace Dahongpao - Huiling Jin; Haipeng Zhang; Xuyang Zhao; Li Long; Fangnian Guan; Yunpeng Wang; Linyu Huang; Xiaoyue Zhang; Yuqi Wang; Hao Li; Wei Li; Zhien Pu; et al. (Theoretical and Applied Genetics, 2023)

Transcriptomics, metabolomics, antioxidant enzymes activities and respiration rate analysis reveal the molecular responses of rice to Cd stress and/or elevated CO2 concentration - Lanlan Wang; Ge Wang; Jinghui Cui; Xuhao Wang; Meng Li; Xiufen Qi; Xuemei Li; Yueying Li; Lianju Ma (Plant and Soil, 2023)

Correction to: D-beta-hydroxybutyrate protects against microglial activation in lipopolysaccharide-treated mice and BV-2 cells - Yuping Zhang; Kun Liu; Yunpeng Li; Yujie Ma; Yu Wang; Zihan Fan; Yanning Li; Jinsheng Qi (Metabolic Brain Disease, 2023)

Synergistic interactions of fine particles and radiative effects in modulating urban heat islands during winter haze event in a cold megacity of Northeast China - Stephen Dauda Yabo; Donglei Fu; Bo Li; Lixin Ma; Xiaofei Shi; Lu Lu; Xie Shengjin; Fan Meng; Jinpan Jiang; Wei Zhang; Hong Qi (Environmental Science and Pollution Research, 2023)

A Storage-Saving Quadtree-Based Multibeam Bathymetry Map Representation Method - Zheng Cong; Teng Ma; Ye Li; Mingxiao Yuan; Yu Ling; Haohan Du; Chi Qi; Ziyuan Li; Shuo Xu; Qiang Zhang (Journal of Marine Science and Engineering, 2023)
With the rapid advancement of the simultaneous localization and mapping (SLAM) technology, the collaboration of several autonomous underwater vehicles (AUVs) in large-scale seafloor imaging has become a trending topic. Electromagnetic waves are difficult to transfer underwater, the only viable method of communication is acoustic transmission, but its bandwidth is limited. Therefore, how to compress and process multibeam bathymetry maps so that AUVs can acquire maps gathered by other AUVs has become an important topic of study. This study presents a representation approach for multibeam bathymetry maps based on a quadtree structure. In comparison to the girding approach, the sparse pseudo-input Gaussian processes (SPGPs) method, and the octree-based method, the quadtree-based method suggested in this study preserves precision while compressing storage space. Experiments utilizing field data validate the performance of the proposed technique, and the method’s ability to compress storage space towards an AUV cooperative SLAM’s scenario.

In-field rice panicles detection and growth stages recognition based on RiceRes2Net - Suiyan Tan; Henghui Lu; Jie Yu; Maoyang Lan; Xihong Hu; Huiwen Zheng; Yingtong Peng; Yuwei Wang; Zehua Li; Long Qi; Xu Ma (Computers and Electronics in Agriculture, 2023)

Pharmacokinetics and residue elimination of metalaxyl enantiomers in snakehead (Channa argus) - Hao Zhou; Meiyu Zhang; Qi Shan; Heqing Huang; Meiling Zhang; Shugui Liu; Jiawei Lin; Lisha Ma; Guangming Zheng; Lichun Li; Cheng Zhao; Xiaoxin Dai; et al. (Aquaculture, 2023)

Predicting the minimum scale of urban ecological space based on socio-ecological systems analysis - Wuyang Hong; Chuangchang Liao; Renzhong Guo; Qi An; Xiaoming Li; Tao Ma (Science of The Total Environment, 2023)

The biodeterioration outbreak in Dunhuang Mogao Grottoes analyzed for the microbial communities and the occurrence time by C-14 dating - Wenxia Ma; Fasi Wu; Dongpeng He; Jie Li; Qi Zhang; Xiaoju Yang; Ji-Dong Gu; Wanfu Wang; Huyuan Feng (International Biodeterioration & Biodegradation, 2023)

Automatic detection of river capture based on planform pattern and χ-plot of the stream network - Qi-Yuan Ma; An-Bo Li; Ping Wang (Geomorphology, 2023)

Rapid and sensitive quantification of capsaicinoids for edible oil adulteration by immunomagnetic solid-phase extraction coupled with time-resolved fluorescent immunochromatographic assay - Di Yuan; Shaowei Li; Liangxiao Zhang; Fei Ma; Hong Wang; Qi Zhang; Peiwu Li (Food Chemistry, 2023)

Simple and sensitive electrochemical detection of sunset yellow and Sudan I in food based on AuNPs/Zr-MOF-Graphene - Ruimeng Sun; Ruijuan Lv; Yuhan Li; Ting Du; Lixia Chen; Yang Zhang; Xiaoyu Zhang; Lina Zhang; Hainan Ma; Haolin Sun; Yanfei Qi (Food Control, 2023)

Why did air quality experience little improvement during the COVID-19 lockdown in megacities, northeast China? - Donglei Fu; Xiaofei Shi; Jinxiang Zuo; Stephen Dauda Yabo; Jixiang Li; Bo Li; Haizhi Li; Lu Lu; Bo Tang; Hong Qi; Jianmin Ma (Environmental Research, 2023)

A tris(hydroxymethyl)aminomethane-modified polyimide membrane with efficient organic solvent resistant performance and high separation selectivity for dye/salt separation - Zitian Liu; Xuesong Deng; Ligang Lin; Rongrong Qiang; Qiying Wang; Qi Cheng; Jing Yang; Xu Yang; Wensong Ma; Xinyang Li; Meina Xu; Chunhong Wang; et al. (Desalination, 2023)

Enhanced interfacial charge transfer and photothermal effect via in-situ construction of atom co-sharing Bi plasmonic/Bi4O5Br2 nanosheet heterojunction towards improved full-spectrum photocatalysis - Xiaoyi Dong; Liang Xu; Junhao Ma; Yongjin Li; Zhaoyi Yin; Daomei Chen; Qi Wang; Jin Han; Jianbei Qiu; Zhengwen Yang; Zhiguo Song (Chemical Engineering Journal, 2023)

Pilot study on production of aviation fuel from catalytic conversion of corn stover - Yong Liu; Lungang Chen; Yubao Chen; Xinghua Zhang; Jianguo Liu; Qiying Liu; Yuping Li; Chenguang Wang; Qi Zhang; Longlong Ma (Bioresource Technology, 2023)

Statistical source analysis of recurring sulfur dioxide pollution events in a chemical industrial park - Yamei Xue; Xinlei Cui; Kexin Li; Qi Yu; Weichun Ma (Atmospheric Environment, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

D-beta-hydroxybutyrate protects against microglial activation in lipopolysaccharide-treated mice and BV-2 cells - Yuping Zhang; Kun Liu; Yunpeng Li; Yujie Ma; Yu Wang; Zihan Fan; Yanning Li; Jinsheng Qi (Metabolic Brain Disease, 2023)

No tillage outperforms conventional tillage under arid conditions and following fertilization - Stavros D. Veresoglou; Junjiang Chen; Xuheng Du; Qi Fu; QingLiu Geng; Chenyan Huang; Xilin Huang; Nan Hu; Yiming Hun; Guolin C. Li; Zhiman Lin; Zhiyu Ma; et al. (Soil Ecology Letters, 2023)

Glyphosate based-herbicide disrupts energy metabolism and activates inflammatory response through oxidative stress in mice liver - Lei Qi; Yan-Mei Dong; Hong Chao; Peng Zhao; Shu-Li Ma; Gang Li (Chemosphere, 2023)

Cobalt mediated perovskite as efficient Fenton-like catalysts for the tetracycline removal over a neutral condition: The importance of superoxide radical - Jinxin Li; Dan Zhong; Jianyang Huang; Wencheng Ma; Kefei Li; Menglin Li; Rui Wu; Congqiao Pu; Qi Wang; Yuzhe Zhou; Shaobo Zhang (Chemosphere, 2023)

PM2.5 source apportionment identified with total and soluble elements in positive matrix factorization - Wenshuai Li; Yuxuan Qi; Wen Qu; Wenjun Qu; Jinhui Shi; Daizhou Zhang; Yingchen Liu; Yanjing Zhang; Weihang Zhang; Danyang Ren; Yuanyuan Ma; Xinfeng Wang; et al. (Science of The Total Environment, 2023)

Inhibitory effect and possible mechanism of oregano and clove essential oils against Pectobacterium carotovorum subsp. carotovorum as onion soft rot in storage - Jinfeng Zhang; Yongqiang Tian; Jianglai Wang; Jinxiu Ma; Lu Liu; Rehmat Islam; Yonghong Qi; Jiajia Li; Tong Shen (Postharvest Biology and Technology, 2023)

Secondary resource utilization of exhausted copper slags (ECSs): Efficient removal of Cr (VI) from aqueous solutions and removal mechanism - Leqi Shi; Li Guo; Qi Deng; Dongyun Du; Mengyu Ma; Tian C. Zhang; Honghai Shen (Minerals Engineering, 2023)

The negative effect of the high pH of waste concrete in constructed wetlands on COD and N removal - Qiming Li; Yu Ma; Jing Chen; Ying Cai; Qianqian Lu; Qi Yu; Xiuting Duan; Dehua Zhao; Shuqing An (Journal of Water Process Engineering, 2023)

Roles of the stolon and erect grass species in surface–subsurface flow generation and red soil loss - Zhimin Yang; Chunhui Li; Yaojun Liu; Jian Duan; Lichao Zhang; Zhongwu Li; Xiangyu Zhou; Qi Li; Yichun Ma; Liang Tian (Journal of Hydrology, 2023)

Size-resolved environmentally persistent free radicals in cold region atmosphere: Implications for inhalation exposure risk - Shi-Ming Jia; De-Qi Wang; Li-Yan Liu; Zi-Feng Zhang; Wan-Li Ma (Journal of Hazardous Materials, 2023)

Using a human bronchial epithelial cell-based malignant transformation model to explore the function of hsa-miR-200 family in the progress of PM2.5-induced lung cancer development - Wanli Ma; Lin Xu; Xueying Sun; Yuan Qi; Shen Chen; Daochuan Li; Yuan Jin; Ningning Chen; Xiaoxiao Zhu; Jiao Luo; Chuanhai Li; Kunming Zhao; et al. (Environmental Pollution, 2023)

Mulch film: An overlooked diffuse source of organic ultraviolet absorbers in agricultural soil - Bingru Li; Qi Liu; Zhenzhen Yao; Zhihong Ma; Cheng Li (Environmental Pollution, 2023)

Experiment and numerical simulation study of dynamic mechanical behavior of granite specimen after high temperature treatment - Sheng-Qi Yang; Ye Li; Guo-Wei Ma; Bo-Wen Sun; Jing Yang; Jie Xu; Yong-Hao Dai (Computers and Geotechnics, 2023)

Facilitating both anionic and cationic redox processes in Na-rich layered cathode materials by heteroatomic doping - Ziwei Chen; Maolin Yang; Zhongyuan Huang; Yanda Fu; Zhefeng Chen; Simo Li; Minzhi zhan; Rui Wang; Mihai Chu; Rui Qi; Xing Cheng; Zhewen Ma; et al. (Chemical Engineering Journal, 2023)

Core-shell heterojunction engineering of Ni0.85Se-O/CN electrocatalyst for efficient OER - Cheng Zhang; Wei Xu; Site Li; Xuzhuo Wang; Ziyu Guan; Meilin Zhang; Jiang Wu; Xinxia Ma; Maoliang Wu; Yongfeng Qi (Chemical Engineering Journal, 2023)

Construction of covalent organic frameworks with alternating rigid and flexible units and their controlled release of active sites - Xiaofeng Li; Zhimin Jia; Jie Zhang; Ningning He; Honghan Long; Yue Qi; Jing Li; Ning Liu; Yang Li; Lijian Ma (Chemical Engineering Journal, 2023)

Sulfate and nitrate elevation in reverse-transport dust plumes over coastal areas of China - Wenshuai Li; Yuxuan Qi; Wen Qu; Wenjun Qu; Jinhui Shi; Daizhou Zhang; Yingchen Liu; Feng Wu; Yuanyuan Ma; Yanjing Zhang; Danyang Ren; Xueqing Du; et al. (Atmospheric Environment, 2023)

Synthetic Biology Technologies And Genetically Engineering Strategies For Enhanced Cell Therapeutics - Siyu Li; Hao Tang; Cheng Li; Jiajia Ma; Maqsood Ali; Qi Dong; Jiajia Wu; Yang Hui; Chongran Sun (Stem Cell Reviews and Reports, 2023)

Experimental Study of Vibration Reduction Effect of Barrier Holes Under Blasting - Jianbo Zhu; Rui Zhao; Yashi Li; Yankun Ma; Jianxin Wang; Qi Peng; Jun Guo (Rock Mechanics and Rock Engineering, 2023)

Co-application of biochar and microbial inoculants increases soil phosphorus and potassium fertility and improves soil health and tomato growth - Wei Yang; Yingnan Zhao; Yang Yang; Minshuo Zhang; Xiaoxi Mao; Yanjie Guo; Xiangyu Li; Bu Tao; Yongzhi Qi; Li Ma; Wenju Liu; Bowen Li; et al. (Journal of Soils and Sediments, 2023)

Porewater dissolved inorganic carbon released due to artificial sediment scouring in the Yellow River - Xing-yu Huang; Dong Zhang; Fu-shun Wang; Zhi-qi Zhao; Ai-chun Chen; Jun-wen Zhang; Cong Zhang; Li Wu; Yu-hong Li; Bing-juan Ma; Qi-yan Feng (Applied Geochemistry, 2023)

Precipitation consistently promotes, but temperature inversely drives, biomass production in temperate vs. alpine grasslands - Wenjuan Wu; Ruojun Sun; Leren Liu; Xiaodi Liu; Hongying Yu; Quanhui Ma; Miao Qi; Lang Li; Yibo Li; Guangsheng Zhou; Zhenzhu Xu (Agricultural and Forest Meteorology, 2023)

Thyroid hormone activities of neutral and anionic hydroxylated polybrominated diphenyl ethers to thyroid receptor β: A molecular dynamics study - Qi Xu; Jian Li; Shang Cao; Guangcai Ma; Xianglong Zhao; Qiuyi Wang; Xiaoxuan Wei; Haiying Yu; Zhiguo Wang (Chemosphere, 2023)

Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Proteomic profiling reveals dysregulated mitochondrial complex subunits responsible for myocardial toxicity induced by SiNPs - Xinying Zhao; Hailin Xu; Yan Li; Ru Ma; Yi Qi; Min Zhang; Caixia Guo; Zhiwei Sun; Yanbo Li (Science of The Total Environment, 2023)

Carbon sequestration from refractory dissolved organic carbon produced by biodegradation of Saccharina japonica - Mingliang Zhang; Huawei Qin; Yuanqing Ma; Yanmin Qi; Yuting Zhao; Zhidong Wang; Bin Li (Marine Environmental Research, 2023)

Overexpression of SmMYC2 enhances salt resistance in Arabidopsis thaliana and Salvia miltiorrhiza hairy roots - Huaiyu Deng; Qi Li; Ruizhi Cao; Yafei Ren; Guanfeng Wang; Hongbo Guo; Shuhai Bu; Jingying Liu; Pengda Ma (Journal of Plant Physiology, 2023)

Catalytic pyrolysis of spent bleaching clay for its regeneration and simultaneously producing aromatic hydrocarbons - Kai Li; Zhu-yu Li; Cheng-Bo Zhang; Jia-qi Zhao; Li Zhao; Ji Liu; Shan-wei Ma; Qiang Lu (Journal of Cleaner Production, 2023)

The source distribution and seasonal discrepancies of antibiotic resistance genes among multiple environment media in a cold megacity - Fan Meng; Shaojing Sun; Jialu Geng; Lixin Ma; Jinpan Jiang; Bo Li; Stephen Dauda Yabo; Lu Lu; Donglei Fu; Jimin Shen; Hong Qi (Journal of Cleaner Production, 2023)

Development of an extended STIRPAT model to assess the driving factors of household carbon dioxide emissions in China - Shiwang Yu; Qi Zhang; Jian Li Hao; Wenting Ma; Yao Sun; Xuechao Wang; Yu Song (Journal of Environmental Management, 2023)

Elemental composition and microbial community differences between wastewater treatment plant effluent and local natural surface water: A Zhengzhou city study - Qianqian Lu; Ran Zhao; Qiming Li; Yu Ma; Jing Chen; Qi Yu; Dehua Zhao; Shuqing An (Journal of Environmental Management, 2023)

Mechanism research on hydrogen production from catalytic pyrolysis of waste tire rubber - Zhaoying Li; Li Tao; Qirong Yang; Lei Chen; Hao Qi; Xinru Ma; Haoxi Ben (Fuel, 2023)

A novel UHPLC-MS/MS method for the determination of four α-dicarbonyl compounds in wine and dynamic monitoring in human urine after drinking - Chao Qi; Yueying Jin; Shengyu Cheng; Lei Di; Xin Wang; Minghui Zhang; Lingli Zhang; Xi-Ling Li; Yu Han; Qingkun Ma; Jun Zhe Min (Food Research International, 2023)

Investigations on combustion system optimization of a heavy-duty natural gas engine - Wei Li; Junfang Ma; Hongzhe Liu; Hui Wang; Hairui Zhang; Tonghui Qi; Dongyin Wu; Jiaying Pan (Fuel, 2023)

Detection of microplastics in domestic and fetal pigs’ lung tissue in natural environment: A preliminary study - Han Li; Zuosen Yang; Feng Jiang; Liang Li; Yansheng Li; Minmin Zhang; Zhenzhen Qi; Ruixue Ma; Yuanyuan Zhang; Jing Fang; Xi Chen; Yihang Geng; et al. (Environmental Research, 2023)

Superior photopiezocatalytic performance by enhancing spontaneous polarization through post-synthesis structure distortion in ultrathin Bi2WO6 nanosheet polar photocatalyst - Huiqin Ma; Weiyi Yang; Shuang Gao; Wanrong Geng; Yunli Lu; Chunliang Zhou; Jian Ku Shang; Tuo Shi; Qi Li (Chemical Engineering Journal, 2023)

Formation mechanism and metabolic pathways of photogranule in batch and continuous-flow mode under high salinity stress - Jing Zhu; Hong You; Zhipeng Li; Binghan Xie; Weirun Li; Shaojie Qi; Rui Wang; Hongying Chen; Binyu Ma; Yi Ding; Haili Tan; Feng Liu; et al. (Chemical Engineering Journal, 2023)

Iron-blocking antibacterial therapy with cationic heme-mimetic gallium porphyrin photosensitizer for combating antibiotic resistance and enhancing photodynamic antibacterial activity - Hao Zhang; Qingsi Li; Xiaoyu Qi; Yi Li; Hongyan Ma; Mariusz Grinholc; Joanna Nakonieczna; Bingran Yu; Xing Wang; Lei Zhang (Chemical Engineering Journal, 2023)

Estimation of hourly actual evapotranspiration over the Tibetan Plateau from multi-source data - Xian Wang; Lei Zhong; Yaoming Ma; Yunfei Fu; Cunbo Han; Peizhen Li; Zixin Wang; Yuting Qi (Atmospheric Research, 2023)

Viperin deficiency promotes dendritic cell activation and function via NF-kappaB activation during Mycobacterium tuberculosis infection - Xinying Zhou; Hui Xu; Qianna Li; Qi Wang; Honglin Liu; Yingqi Huang; Yao Liang; Linmiao Lie; Zhenyu Han; Yaoxin Chen; Yulan Huang; Wenle Zhou; et al. (Inflammation Research, 2023)
Objectives and design Dendritic cells (DCs) are one of the key immune cells in bridging innate and adaptive immune response against Mycobacterium tuberculosis (Mtb) infection. Interferons (IFNs) play important roles in regulating DC activation and function. Virus-inhibitory protein, endoplasmic reticulum-associated, interferon-inducible (Viperin) is one of the important IFN-stimulated genes (ISGs), and elicits host defense against infection. Methods We investigated the effects and mechanisms of Viperin on DC activation and function using Viperin deficient bone marrow-derived dendritic cells (BMDCs) during Mtb infection. Results Viperin deficiency enhanced phagocytic activity and increased clearance of Mtb in DCs, produced higher abundance of NO, cytokine including interleukin-12 (IL-12), Tumor necrosis factor-α (TNF- α ), IL-1 β , IL-6 and chemokine including CXCL1, CXCL2 and CXCL10, elevated MHC I, MHC II and co-stimulatory molecules expression, and enhanced CD4 + and CD8 + T cell responses. Mechanistically, Viperin deficiency promoted DC activation and function through NF-κB p65 activation. NF-κB p65 inhibitor prevented cytokine and chemokine production, and co-stimulatory molecules expression promoted by Viperin deficiency. Conclusions These results suggest that Mtb induced Viperin expression could impair the activation of host defense function of DCs and DC-T cell cross talk during Mtb infection. This research may provide a potential target for future HDT in TB therapy.

Exposure–response relationship between temperature, relative humidity, and varicella: a multicity study in South China - Yihan Li; Jialing Li; Zhihua Zhu; Weilin Zeng; Qi Zhu; Zuhua Rong; Jianxiong Hu; Xing Li; Guanhao He; Jianguo Zhao; Lihua Yin; Yi Quan; et al. (Environmental Science and Pollution Research, 2023)

High Concentration of CO2 Improve the Pb Resistance of Oryza sativa L. Seedlings by Enhancing Photosynthesis and Regulating Plant Endogenous Hormones - Xuhao Wang; Jiayi Zou; Xiufen Qi; Qi Li; Lianju Ma; Yueying Li; Xuemei Li; Lanlan Wang (Journal of Plant Growth Regulation, 2022)

First report of Claviceps purpurea causing ergot disease on wheat (Triticum aestivum) in southwestern China - Mingliang Ding; Zhiqin Wang; Qi Fan; Hefa Liao; Kun Liu; Mingju Li; Zhanhong Ma; Hong Yu; Yuanbing Wang (Journal of Plant Pathology, 2022)

Endosperm-specific accumulation of human α-lactalbumin increases seed lysine content in maize - Chenwanli Li; Wen Ma; Lifang Jin; Rentao Song; Weiwei Qi (Plant Cell Reports, 2022)

A comprehensive survey on deep learning techniques in CT image quality improvement - Disen Li; Limin Ma; Jining Li; Shouliang Qi; Yudong Yao; Yueyang Teng (Medical & Biological Engineering & Computing, 2022)

Genome-wide identification and expression analysis of JmjC domain–containing genes in grape under MTA treatment - Yi-Zhe Cheng; Guang-Qi He; Sheng-Di Yang; Shuai-Hui Ma; Jin-Ping Ma; Fang-Hui-Zi Shang; Xu-Fei Li; Hui-Ying Jin; Da-Long Guo (Functional & Integrative Genomics, 2022)

A Label-Free Colorimetric Aptasensor Containing DNA Triplex Molecular Switch and AuNP Nanozyme for Highly Sensitive Detection of Saxitoxin - Xiaoyan Qi; Ling Li; Xiaochen Yan; Yinglin Zhao; Lele Wang; Rui Ma; Sai Wang; Xiangzhao Mao (Journal of Ocean University of China, 2022)

AUV Path Planning Algorithm for Terrain Aided Navigation - Wenjun Zhang; Peng Shen; Haodong Qi; Qianyi Zhang; Teng Ma; Ye Li (Journal of Marine Science and Engineering, 2022)
Terrain aided navigation (TAN) technology can yield accurate navigation results in long-endurance underwater operation of autonomous underwater vehicles (AUVs). Most TAN research focus on the high-precision terrain matching algorithms. However, terrain matching algorithms estimate the position of the vehicle by observing a unique combination of features in the terrain, making it difficult to locate a vehicle with flat terrain. This paper presents a path planning method for AUV seabed TAN process to decrease positioning errors by avoiding flat areas. In this paper, a TAN path planning algorithm based on sector search is proposed. Parameters of the sector search algorithm are determined through theoretical analysis, which means the generated path can stably provide accurate TAN location results. Meanwhile, a control coefficient is proposed to maximize the terrain information contained in the sector searching area, bring out a high success rate of AUV positioning. The TAN performance of the paths generated using the proposed path planning method was verified in simulations, which show that the TAN can yield accurate positioning results stably on the path planned.

Human Adipose-Derived Stem Cells Delay Muscular Atrophy after Peripheral Nerve Injury in Rats - Siwei Qu; Ning Ma; Weixin Wang; Sen Chen; Qi Wu; Yangqun Li; Zhe Yang (Cell Biochemistry and Biophysics, 2022)

Development of an Escherichia coli whole cell biocatalyst for the production of hyperoside - Guo-Si Li; Fu-Cheng Zhu; Pei-Pei Wei; Fang-Li Gu; Qi-Ling Xu; Meng-Hua Ma (Biotechnology Letters, 2022)

Ship detection of optical remote sensing image in multiple scenes - Xungen Li; Zixuan Li; Shuaishuai Lv; Jing Cao; Mian Pan; Qi Ma; Haibin Yu (International Journal of Remote Sensing, 2022)

Quick mapping and characterization of a co-located kernel length and thousand-kernel weight-related QTL in wheat - Xiangru Qu; Cong Li; Hang Liu; Jiajun Liu; Wei Luo; Qiang Xu; Huaping Tang; Yang Mu; Mei Deng; Zhien Pu; Jun Ma; Qiantao Jiang; et al. (Theoretical and Applied Genetics, 2022)

Fbxw17 is dispensable for viability and fertility in mice - Zhen Chen; Dupeng Ma; Tingyu Jin; Ziqi Yu; Jiong Li; Qi Sun; Zejia Li; Ziye Du; Rong Liu; Yi Li; Mengcheng Luo (Molecular Biology Reports, 2022)

The Role of PpNAC187 in Pear Drought and Salt Stress - Chunhui Ma; Mingtong Li; Shaolan Yang; Xinfu Zhang; Yong Zhang; Qi Qi; Yu Zhang; Chenxia Cheng (Journal of Plant Growth Regulation, 2022)

Mental health conditions and academic burnout among medical and non-medical undergraduates during the mitigation of COVID-19 pandemic in China - Qian Yang; Yueheng Liu; Winson Fuzun Yang; Pu Peng; Shubao Chen; Yunfei Wang; Xin Wang; Manyun Li; Yingying Wang; Yuzhu Hao; Li He; Qianjin Wang; et al. (Environmental Science and Pollution Research, 2022)
The outbreak of the novel coronavirus disease 2019 (COVID-19) has posed a great impact on people’s mental health, especially for undergraduate students. This study aimed to compare the mental health conditions and academic burnout between medical and non-medical undergraduates in China when the COVID-19 pandemic is mitigating. A cross-sectional online survey was conducted among 4,972 undergraduates between October 2020 and April 2021, when the pandemic was basically under control. The survey included basic demographics information and standardized scales to evaluate depression, anxiety, perceived stress, daytime sleepiness, alcohol abuse/dependence, quality of life, fatigue, and academic burnout. Compared with medical undergraduates, non-medical undergraduates had higher rates of moderate to severe depression symptoms (29.1% vs. 17.9%, P < 0.001), moderate to severe anxiety symptoms (19.7% vs. 8.9%, P < 0.001), alcohol abuse/dependence (16.3% vs.10.3%, P < 0.001), excessive daytime sleepiness (47.4% vs. 43.4%, P = 0.018), high perceived stress (34.7% vs. 22.2%, P < 0.001), high level of fatigue (51.8% vs. 42.2%, P < 0.001), low QOL (35.8% vs. 21.4%, P < 0.001), and higher academic burnout score (59.4 vs. 57.5, P < 0.001). Being non-medical undergraduates, depression, alcohol abuse/dependence, excessive daytime sleepiness, and high perceived stress were positively associated with academic burnout, while high QOL was negatively associated with the burnout (all P < 0.001). Excessive daytime sleepiness was the strongest predictor for academic burnout.

Study on the operation performance and floc adhesion mechanism of dissolved air flotation equipment - Yonglei Wang; Huiyuan Ma; Xiaobo Wang; Ling Ju; Liping Tian; Hua Qi; Haiyang Yu; Guilin He; Jingjing Li (Environmental Science and Pollution Research, 2022)

Correction to: Sox10 Gene Is Required for the Survival of Saccular and Utricular Hair Cells in a Porcine Model - Jing-cui Qi; Qing-qing Jiang; Long Ma; Shuo-long Yuan; Wei Sun; Li-sheng Yu; Wei-wei Guo; Shi-ming Yang (Molecular Neurobiology, 2022)

Sox10 Gene Is Required for the Survival of Saccular and Utricular Hair Cells in a Porcine Model - Jing-cui Qi; Qing-qing Jiang; Long Ma; Shuo-long Yuan; Wei Sun; Li-sheng Yu; Wei-wei Guo; Shi-ming Yang (Molecular Neurobiology, 2022)

Wuzi Yanzong pill attenuates MPTP-induced Parkinson’s Disease via PI3K/Akt signaling pathway - Wei Hang; Hui-jie Fan; Yan-rong Li; Qi Xiao; Lu Jia; Li-juan Song; Yao Gao; Xiao-ming Jin; Bao-guo Xiao; Jie-zhong Yu; Cun-gen Ma; Zhi Chai (Metabolic Brain Disease, 2022)

The interplay of particle properties and solution chemistry on aggregation kinetics of soil nanoparticles - Ning Hu; Chen-yang Xu; Zeng-chao Geng; Fei-nan Hu; Qi-rui Li; Ren-tian Ma; Qiang Wang (Journal of Soils and Sediments, 2022)

Application of galactinol to tomato enhances tolerance to cold and heat stresses - Yudong Liu; Li Zhang; Jian Ma; Sida Meng; Chunpeng Pang; Xiaomeng Zhao; Huidong Zhang; Shou Wang; Tao Xu; Yi He; Yufeng Liu; Mingfang Qi (Horticulture, Environment, and Biotechnology, 2022)

Early-life educational attainment, APOE ε4 alleles, and incident dementia risk in late life - Hao Ma; Tao Zhou; Xiang Li; Demetrius Maraganore; Yoriko Heianza; Lu Qi (GeroScience, 2022)

The study of schizogenous formation of secretory ducts in Ferula ferulaeoides (Steud.) Korov. - Meng-meng Liu; Yuan-yuan Zhao; Ying Ma; Shuang-shuang Liu; Jia-qi Yao; Ya-ping Chi; Hui-fang Li; Kai Liao; Yun Zhu (Protoplasma, 2022)

Dissection of the practical soybean breeding pipeline by developing ZDX1, a high-throughput functional array - Rujian Sun; Bincheng Sun; Yu Tian; Shanshan Su; Yong Zhang; Wanhai Zhang; Jingshun Wang; Ping Yu; Bingfu Guo; Huihui Li; Yanfei Li; Huawei Gao; et al. (Theoretical and Applied Genetics, 2022)
Key message We developed the ZDX1 high-throughput functional soybean array for high accuracy evaluation and selection of both parents and progeny, which can greatly accelerate soybean breeding. Abstract Microarray technology facilitates rapid, accurate, and economical genotyping. Here, using resequencing data from 2214 representative soybean accessions, we developed the high-throughput functional array ZDX1, containing 158,959 SNPs, covering 90.92% of soybean genes and sites related to important traits. By application of the array, a total of 817 accessions were genotyped, including three subpopulations of candidate parental lines, parental lines and their progeny from practical breeding. The fixed SNPs were identified in progeny, indicating artificial selection during the breeding process. By identifying functional sites of target traits, novel soybean cyst nematode-resistant progeny and maturity-related novel sources were identified by allele combinations, demonstrating that functional sites provide an efficient method for the rapid screening of desirable traits or gene sources. Notably, we found that the breeding index (BI) was a good indicator for progeny selection. Superior progeny were derived from the combination of distantly related parents, with at least one parent having a higher BI. Furthermore, new combinations based on good performance were proposed for further breeding after excluding redundant and closely related parents. Genomic best linear unbiased prediction (GBLUP) analysis was the best analysis method and achieved the highest accuracy in predicting four traits when comparing SNPs in genic regions rather than whole genomic or intergenic SNPs. The prediction accuracy was improved by 32.1% by using progeny to expand the training population. Collectively, a versatile assay demonstrated that the functional ZDX1 array provided efficient information for the design and optimization of a breeding pipeline for accelerated soybean breeding.

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Applying rail transit construction waste to make building materials: using the theory of sustainable development - Jinming Jia; Fumin Ren; Xiao Wei; Yinghao Gao; Gao Qi; Fuan Li; Ma Li; Changan Guo (Environmental Science and Pollution Research, 2022)

Integrated comparison of growth and oxidative stress induced by tylosin in two freshwater algae Chlorella vulgaris and Raphidocelis subcapitata - Denglong Lu; Zhihua Ma; Jianglin Peng; Yibo Zhang; Shan Liu; Qi Li (Ecotoxicology, 2022)

Development of a Label-Free Colorimetric Aptasensor with Rationally Utilized Aptamer for Rapid Detection of Okadaic Acid - Xiaochen Yan; Xiaoyan Qi; Yinglin Zhao; Ling Li; Rui Ma; Lele Wang; Sai Wang; Xiangzhao Mao (Journal of Ocean University of China, 2022)

Circular RNA circ_0008934 promotes hepatocellular carcinoma growth and metastasis through modulating miR-1305/TMTC3 axis - Jia-Xi Li; Jin-Jiang Wang; Zhou-Feng Deng; Hao Zheng; Chun-Mei Yang; Ying Yuan; Cheng Yang; Fang-Fang Gu; Wei-Qi Wu; Guang-Lei Qiao; Li-Jun Ma (Human Cell, 2022)

Significant winter CO 2 uptake by saline lakes on the Qinghai‐Tibet Plateau - Xiao‐Yan Li; Fang‐Zhong Shi; Yu‐Jun Ma; Shao‐Jie Zhao; Jun‐Qi Wei (Global Change Biology, 2022)
Direct measuring of CO 2 flux remains challenging for global lakes. The traditional sampling and gas transfer models used to estimate lake CO 2 fluxes are variable and uncertain, and ice‐covered periods are often excluded from the annual carbon budget. Here, the first longtime (2013−2017) direct measurement of CO 2 flux by eddy covariance system over the largest saline lake (Qinghai lake) in the Qinghai‐Tibet Plateau (QTP) revealed that ice‐covered period draws large amounts of CO 2 from the atmosphere (−0.87 ± 0.38 g C m −2 d −1 ), a value more than twice the CO 2 flux rate during the ice‐free period (−0.41 ± 0.35 g C m −2 d −1 ). The total CO 2 uptake by all saline lakes on the QTP was estimated to −10.28 ± 1.65 Tg C yr −1 , an equivalent to approximately one third of the net terrestrial ecosystems carbon sink in QTP. Our results indicate large sink for CO 2 in winter is controlled by both seasonal hydrochemistry processes and lake ice absorption in saline lakes. This research also demonstrates decreasing CO 2 uptake from the atmosphere by saline lakes on the QTP, which may turn carbon sinks to carbon sources with future warming.

Characterization and fine mapping of a lesion mimic mutant (Lm5) with enhanced stripe rust and powdery mildew resistance in bread wheat (Triticum aestivum L.) - Cong Li; Hang Liu; Jian Wang; Qi Pan; Yue Wang; Kunyan Wu; Peiying Jia; Yang Mu; Huaping Tang; Qiang Xu; Qiantao Jiang; Yaxi Liu; et al. (Theoretical and Applied Genetics, 2022)

Development of molecular markers based on LTR retrotransposon in the Cleistogenes songorica genome - Tiantian Ma; Xingyi Wei; Yufei Zhang; Jie Li; Fan Wu; Qi Yan; Zhuanzhuan Yan; Zhengshe Zhang; Gisele Kanzana; Yufeng Zhao; Yingbo Yang; Jiyu Zhang (Journal of Applied Genetics, 2022)

Microbacterium sulfonylureivorans sp. nov., isolated from sulfonylurea herbicides degrading consortium - Qingyun Ma; Delong Kong; Qi Zhang; Miaomiao Li; Xiaoyan Han; Juan Che; Yiqing Zhou; Wei Zhang; Xu Jiang; Zhiyong Ruan (Archives of Microbiology, 2022)

Near-epicenter weather conditions several hours before strong earthquakes (Ms ≥ 6) - Tao Chen; Lei Li; Xiao-Xin Zhang; Qi-Ming Ma; Wen Li; Shuo Ti; Han Wu; Ren-Kang Li; Jing Luo; Jian-Feng Su (Natural Hazards, 2022)

Nitric Oxide Signaling Pathway in Ventral Tegmental Area is Involved in Regulation of 7,8-Dihydroxyflavone on Alcohol Consumption in Rats - Qing Gao; Tao Yang; Xin-Xin Li; Jun-Wei Xiong; Wei Ma; Yan-Min Xu; Yong Liu; Hong-Yan Zhang; Qi-Yu Wang; Hong-Xuan Wang; Ying Peng; Xiao-Feng Zhu; et al. (Molecular Neurobiology, 2022)

Effect of feed restriction on the intestinal microbial community structure of growing ducks - Jun-peng Li; Qi-fan Wu; Sheng-chao Ma; Jian-mei Wang; Bin Wei; Yang Xi; Chun-chun Han; Liang Li; Hua He; He-he Liu (Archives of Microbiology, 2022)

The spatiotemporal distribution and potential risk assessment of 19 phthalate acid esters in wastewater treatment plants in China - Shaojing Sun; Jimin Shen; Bo Li; Jialu Geng; Lixin Ma; Hong Qi; Anping Zhang; Zebin Zhao (Environmental Science and Pollution Research, 2021)

Analysis of the starch properties in tetraploid wheat–Aegilops sharonensis amphidiploid - Qing Li; Xuteng Zhang; Na Lin; Guzmán Carlos; Jingyu Lan; Huaping Tang; Pengfei Qi; Jian Ma; Jirui Wang; Guoyue Chen; Wei Li; Zhien Pu; et al. (Cereal Research Communications, 2021)

Mineralogical characteristics and sedimentary envrionment significance of water-insoluble minerals in potash deposits of Vientiane Basin of Laos - Tang Qi-liang; Zhang Xi-ying; Miao Wei-liang; Ma Hai-zhou; Li Yong-shou; Li Wen-xia; Yuan Xiao-long (Carbonates and Evaporites, 2021)

Geochemical characteristics and genesis of deep marine carbonate natural gas in China - Jianglong Shi; Jian Li; Jin Li; Aisheng Hao; Zhongsheng Shi; Bin Zhang; Bin Hao; Xuening Qi; Bintao Chen; Luo Xue; Lun Ma; Lei Wang; et al. (Carbonates and Evaporites, 2021)

Time-resolved Fluorescence Immunoassay (TRFIA) for the Simultaneous Detection of MMP-9 and Lp-PLA2 in Serum - Hong-yan Ma; Qian Mao; Yan-bin Zhu; Chun-li Cong; Shi-yu Zheng; Qi Zhang; Cui-cui Chen; Lai-qing Li (Journal of Fluorescence, 2021)

Microbiota Composition and Quality Changes of Tiger Puffer ( Takifugu rubripes ) Fillets during 4°C Refrigerated and Ice Storage - Yiming Liu; Jingyi Yang; Haoyuan Ma; Hang Qi; Shiliang Jia; Weidong Li; Jinlu Li; Shuai Zhuang; Yongkang Luo (Journal of Aquatic Food Product Technology, 2021)

A leucoanthocyanidin dioxygenase gene (RtLDOX2) from the feral forage plant Reaumuria trigyna promotes the accumulation of flavonoids and improves tolerance to abiotic stresses - Ningning Li; Xue Wang; Binjie Ma; Zhigang Wu; Linlin Zheng; Zhi Qi; Yingchun Wang (Journal of Plant Research, 2021)

Application of Plant Print Identification Technology in Salt-resistant Soybean Breeding - Yan Li; Xia Li; Zi-qi Chen; Ying Ma; Guang-yu Yang; Ying Zhang; Ming-chun Sun; Li-hong Zhang; Jin-meng Chu; Jing-mei Lu; Jun Zhu; Ji-hong You (Journal of Plant Growth Regulation, 2021)

Concurrent alterations of white matter microstructure and functional activities in medication-free major depressive disorder - Min Zeng; Min Yu; Guiqiang Qi; Shaojin Zhang; Jijian Ma; Qingmao Hu; Jinhuan Zhang; Hongxing Li; Huawang Wu; Jinping Xu (Brain Imaging and Behavior, 2021)

Discovery and mapping of two new rust resistance genes, R17 and R18, in sunflower using genotyping by sequencing - L. L. Qi; Z. I. Talukder; G. J. Ma; X. H. Li (Theoretical and Applied Genetics, 2021)

Comparison of Autogenous Tooth Materials and Other Bone Grafts - Shuxin Zhang; Xuehan Li; Yanxin Qi; Xiaoqian Ma; Shuzhan Qiao; HongXin Cai; Bing Cheng Zhao; Heng Bo Jiang; Eui-Seok Lee (Tissue Engineering and Regenerative Medicine, 2021)

Could α-Klotho Unlock the Key Between Depression and Dementia in the Elderly: from Animal to Human Studies - Xiang Gao; Yuhong Li; Zuoli Sun; Hong Xu; Guangwei Ma; Qi Deng; Claire X. Zhang; Rena Li (Molecular Neurobiology, 2021)

Effects of Shading on the Synthesis of Volatile Organic Compounds in ‘Marselan’ Grape Berries (Vitis vinifera L.) - Zonghuan Ma; Shijin Yang; Juan Mao; Wenfang Li; Wei Li; Cunwu Zuo; Mingyu Chu; Xin Zhao; Qi Zhou; Baihong Chen (Journal of Plant Growth Regulation, 2021)

Can Swimming Microalgal Cells be Vehicles for ZnO Nanoparticle Transportation and Thus Lead to Zn Diffusion? - Shuai Mao; Hongxia Liu; Jiji Li; Yahong Guo; Wei Ma; Peng zhi Qi; Chengkai Qu (Bulletin of Environmental Contamination and Toxicology, 2021)

Effects of poor plumage conditions on egg production, antioxidant status and gene expression in laying hens - Junying Li; Chengjie Zhang; Ruiyu Ma; Renrong Qi; Yi Wan; Wei Liu; Tao Zhao; Yan Li; Kai Zhan (Tropical Animal Health and Production, 2021)

EphA1 Activation Induces Neuropathological Changes in a Mouse Model of Parkinson’s Disease Through the CXCL12/CXCR4 Signaling Pathway - Jianjun Ma; Zhidong Wang; Siyuan Chen; Wenhua Sun; Qi Gu; Dongsheng Li; Jinhua Zheng; Hongqi Yang; Xue Li (Molecular Neurobiology, 2021)

Association of FMO3 rs1736557 polymorphism with clopidogrel response in Chinese patients with coronary artery disease - Kong-Xiang Zhu; Pei-Yuan Song; He-Li; Mu-Peng Li; Yin-xiao Du; Qi-lin Ma; Li-Ming Peng; Xiao-Ping Chen (European Journal of Clinical Pharmacology, 2021)

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

Spatial distribution of atmospheric bioaerosols in Beijing, Hangzhou and Wuhan, China - Xuezheng Ma; Qi Zhang; Keyang Liu; Liping Zhang; Manman Zhang; Xin Zhao; Chunya Zhou; Jinke Li; Ming Cheng; Lili Li; Kongxin Hu; Jinsong Li; et al. (Aerobiologia, 2021)

A single nucleotide polymorphism variant located in the cis ‐regulatory region of the ABCG2 gene is associated with mallard egg colour - Hehe Liu; Jian Hu; Zhanbao Guo; Wenlei Fan; Yaxi Xu; Suyun Liang; Dapeng Liu; Yunsheng Zhang; Ming Xie; Jing Tang; Wei Huang; Qi Zhang; et al. (Molecular Ecology, 2021)
Avian egg coloration is shaped by natural selection, but its genetic basis remains unclear. Here, we used genome‐wide association analysis and identity by descent to finely map green egg colour to a 179‐kb region of Chr4 based on the resequencing of 352 ducks ( Anas platyrhynchos ) from a segregating population resulting from the mating of Pekin ducks (white‐shelled eggs) and mallards (green‐shelled eggs). We further narrowed the candidate region to a 30‐kb interval by comparing genome divergence in seven indigenous duck populations. Among the genes located in the finely mapped region, only one transcript of the ABCG2 gene (XM_013093252.2) exhibited higher uterine expression in green‐shelled individuals than in white‐shelled individuals, as supported by transcriptome data from four populations. ABCG2 has been reported to encode a protein that functions as a membrane transporter for biliverdin. Sanger sequencing of the whole 30‐kb candidate region (Chr4: 47.41–47.44 Mb) and a plasmid reporter assay helped to identify a single nucleotide polymorphism (Chr4: 47,418,074 G>A) located in a conserved predicted promoter region whose variation may alter ABCG2 transcription activity. We provide a useful molecular marker for duck breeding and contribute data to the research on ecological evolution based on egg colour patterns among birds.

Modulation of evening complex activity enables north-to-south adaptation of soybean - Xiaolong Fang; Yapeng Han; Mengshi Liu; Jiacan Jiang; Xiang Li; Qichao Lian; Xianrong Xie; Yian Huang; Qibin Ma; Hai Nian; Ji Qi; Cunyi Yang; et al. (Science China Life Sciences, 2021)

Identification of Pythium species as pathogens of garlic root rot - Bo Zhang; Yueli Zhang; Liguo Ma; Kai Qi; Peng Wang; Changsong Li; Junshan Qi (Journal of Plant Pathology, 2021)

A novel, validated, and plant height-independent QTL for spike extension length is associated with yield-related traits in wheat - Cong Li; Huaping Tang; Wei Luo; Xuemei Zhang; Yang Mu; Mei Deng; Yaxi Liu; Qiantao Jiang; Guoyue Chen; Jirui Wang; Pengfei Qi; Zhien Pu; et al. (Theoretical and Applied Genetics, 2020)

Adakitic rocks at convergent plate boundaries: Compositions and petrogenesis - Qiang Wang; Lulu Hao; Xiuzheng Zhang; Jinsheng Zhou; Jun Wang; Qiwei Li; Lin Ma; Long Zhang; Yue Qi; Gongjian Tang; Wei Dan; Jingjing Fan (Science China Earth Sciences, 2020)

The origin of arc basalts: New advances and remaining questions - Yigang Xu; Qiang Wang; Gongjian Tang; Jun Wang; Hongyan Li; Jinsheng Zhou; Qiwei Li; Yue Qi; Pingping Liu; Lin Ma; Jingjing Fan (Science China Earth Sciences, 2020)

Magnesium decreases aluminum accumulation and plays a role in protecting maize from aluminum-induced oxidative stress - Xiangying Kong; Zhongping Peng; Dongxu Li; Wenna Ma; Ruidong An; Dawood Khan; Xinxun Wang; Yuan Liu; En Yang; Yuzhi He; Liqngquan Wu; Baige Zhang; et al. (Plant and Soil, 2020)

Magnesium promotes root growth and increases aluminum tolerance via modulation of nitric oxide production in Arabidopsis - Dongxu Li; Wenna Ma; Jian Wei; Yawen Mao; Zhongping Peng; Jiarong Zhang; Xiangying Kong; Qinqin Han; Wei Fan; Ye Yang; Jianghua Chen; Liangquan Wu; et al. (Plant and Soil, 2020)

Connexin 36 Mediates Orofacial Pain Hypersensitivity Through GluK2 and TRPA1 - Qian Li; Tian-Le Ma; You-Qi Qiu; Wen-Qiang Cui; Teng Chen; Wen-Wen Zhang; Jing Wang; Qi-Liang Mao-Ying; Wen-Li Mi; Yan-Qing Wang; Yu-Xia Chu (Neuroscience Bulletin, 2020)

Quantifying the Cloud Water Resource: Methods Based on Observational Diagnosis and Cloud Model Simulation - Miao Cai; Yuquan Zhou; Jianzhao Liu; Chao Tan; Yahui Tang; Qianrong Ma; Qi Li; Jietai Mao; Zhijin Hu (Journal of Meteorological Research, 2020)

Analysis of genetic architecture and favorable allele usage of agronomic traits in a large collection of Chinese rice accessions - Xiuxiu Li; Zhuo Chen; Guomin Zhang; Hongwei Lu; Peng Qin; Ming Qi; Ying Yu; Bingke Jiao; Xianfeng Zhao; Qiang Gao; Hao Wang; Yunyu Wu; et al. (Science China Life Sciences, 2020)

Occurrence and partitioning of brominated flame retardants (BFRs) in indoor air and dust: a 15-month case study in a test home - Jia-Qi Guo; Yong-feng Li; Li-Yan Liu; Chun-Yan Huo; Yu Sun; Wan-li Ma; Zi-feng Zhang; Yi-Fan Li (Environmental Science and Pollution Research, 2020)

The immune response to a recombinant Lactococcus lactis oral vaccine against foot-and-mouth disease virus in mice - Xinsheng Liu; Linlin Qi; Jianliang Lv; Zhongwang Zhang; Peng Zhou; Zhongyuan Ma; Yonglu Wang; Yongguang Zhang; Li Pan (Biotechnology Letters, 2020)

Internally controlled recombinase-aided amplification (IC-RAA) assays for the detection of human papillomavirus genotypes 16 and 18 using extracted DNA and samples treated with nucleic acid releasing agent - Jinrong Wang; Jianli Liu; Guowei Song; Zhi Cao; Jing Pan; Xinna Li; Yuan Gao; Juju Qi; Ziwei Chen; Guohao Fan; Xueding Bai; Ruiqing Zhang; et al. (Archives of Virology, 2020)

A novel sensitive electrochemical method for the detection of ractopamine in meat food via polycitrulline-modified electrode - Xinying Ma; Huiping Lv; Qi Zhu; Meifeng Chen; Yilei Wang; Fenghai Li (Food Additives & Contaminants: Part A, 2020)

Jacobian matrix for near-infrared remote sensing based on vector radiative transfer model - Wenguang Bai; Peng Zhang; Wenjian Zhang; Jun Li; Gang Ma; Chengli Qi; Hui Liu (Science China Earth Sciences, 2020)

Comparing GWAS and Brain Structure-Specific Gene Expression Profiles Identifies Psychiatric Disorder-Related Brain Structures at Different Developmental Stages - Xin Qi; Cuiyan Wu; Yanan Du; Shiqiang Cheng; Yan Wen; Mei Ma; Chujun Liang; Li Liu; Bolun Cheng; Lu Zhang; Ping Li; Feng Zhang (Neuroscience Bulletin, 2020)

Genome-wide development of miRNA-based SSR markers in Cleistogenes songorica and analysis of their transferability to Gramineae/non-Gramineae species - Gisele Kanzana; Yufei Zhang; Tiantian Ma; Wenxian Liu; Fan Wu; Qi Yan; Xueyang Min; Zhuanzhuan Yan; Blaise Pascal Muvunyi; Jie Li; Zhengshe Zhang; Yufeng Zhao; et al. (Journal of Applied Genetics, 2020)

Transfer of the ph1b gene of ‘Chinese Spring’ into a common wheat cultivar with excellent traits - Y. Li; Q. Li; Y. Li; J. Lan; H. Tang; P. Qi; J. Ma; J. Wang; G. Chen; Z. Pu; W. Li; Z. Li; et al. (Cereal Research Communications, 2020)

Changes of microbial functional capacities in the rhizosphere contribute to aluminum tolerance by genotype-specific soybeans in acid soils - Yongchun Li; Yongfu Li; Minkai Yang; Scott X. Chang; Jinliang Qi; Caixian Tang; Zhongling Wen; Zhi Hong; Tongyi Yang; Zilong Ma; Qun Gao; Jizhong Zhou; et al. (Biology and Fertility of Soils, 2020)

Identification of a novel genomic region associated with resistance to Fusarium crown rot in wheat - Jingjing Jin; Shuonan Duan; Yongzhi Qi; Suhong Yan; Wei Li; Baoyun Li; Chaojie Xie; Wenchao Zhen; Jun Ma (Theoretical and Applied Genetics, 2020)

Identification of drug resistance genes and drug resistance analysis of Salmonella in the duck farm environment of Zhanjiang, China - Jin-Li Niu; Jin-Ju Peng; Yue-Yue Ming; Qi-Chao Ma; Wen-Chao Liu; Yi Ma (Environmental Science and Pollution Research, 2020)

Crosstalk between PKC and MAPK pathway activation in cardiac fibroblasts in a rat model of atrial fibrillation - Wei-hua Guo; Xian Wang; Mei-sheng Shang; Zhe Chen; Qi Guo; Li Li; Hai-ying Wang; Rong-hui Yu; Chang-sheng Ma (Biotechnology Letters, 2020)

Gene transfer and nucleotide sequence evolution by Gossypium cytoplasmic genomes indicates novel evolutionary characteristics - Ting-Ting Zhang; Heng Liu; Qi-Yuan Gao; Ting Yang; Jian-Ni Liu; Xiong-Feng Ma; Zhong-Hu Li (Plant Cell Reports, 2020)

EMS induced SNP changes led to mutation of Wx protein in common wheat - J. Lan; Y. Li; K. Xu; X. Zhang; H. Tang; P. Qi; J. Ma; J. Wang; G. Chen; Z. Pu; W. Li; Z. Li; et al. (Cereal Research Communications, 2020)

Study on chemical constituents of an edible mushroom Volvariella volvacea and their antitumor activity in vitro - Ping Chen; Hui-Juan Qin; Yuan-Wei Li; Guo-Xu Ma; Jun-Shan Yang; Qi Wang (Natural Product Research, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Homeobox B8 Targets Sterile Alpha Motif Domain-Containing Protein 9 and Drives Glioma Progression - Wenping Ma; Hongze Jin; Wenjie Liu; Xiaojuan Li; Xingang Zhou; Xinwu Guo; Runfa Tian; Qi Cui; Junjie Luo; Yueying Jiao; Youtao Yu; Haifeng Yang; et al. (Neuroscience Bulletin, 2020)

Correction to: Limb Remote Ischemic Preconditioning Reduces Repeated Ketamine Exposure-Induced Adverse Effects in the Developing Brain of Rats - Ying Liu; An Qi Li; Wan Ma; Yu Bo Gao; Li Qin Deng; Chun Zhang; Jin Hai Meng (Journal of Molecular Neuroscience, 2020)

Evaluating the Genetic Correlations Between Left-Handedness and Mental Disorder Using Linkage Disequilibrium Score Regression and Transcriptome-Wide Association Study - Bolun Cheng; Chujun Liang; Ping Li; Li Liu; Shiqiang Cheng; Mei Ma; Lu Zhang; Xin Qi; Yan Wen; Feng Zhang (Biochemical Genetics, 2020)

α-Arbutin Protects Against Parkinson’s Disease-Associated Mitochondrial Dysfunction In Vitro and In Vivo - Yaqi Ding; Deqin Kong; Tong Zhou; Nai-di Yang; Chenqi Xin; Jiajia Xu; Qi Wang; Hang Zhang; Qiong Wu; Xiaomei Lu; Kahleong Lim; Bo Ma; et al. (NeuroMolecular Medicine, 2020)

Alternative complement pathway is activated in the brains of scrapie-infected rodents - Cao Chen; Yan Lv; Chao Hu; Xiao-Feng Xu; Ren-Qing Zhang; Kang Xiao; Yue Ma; Li-Ping Gao; Jian-Le Li; Qiang Shi; Jing Wang; Qi Shi; et al. (Medical Microbiology and Immunology, 2020)

Production of waxy tetraploid wheat (Triticum turgidum durum L.) by EMS mutagenesis - Siyu Li; Xiaojuan Zhong; Xuteng Zhang; Md. Mostafijur Rahman; Jingyu Lan; Huaping Tang; Pengfei Qi; Jian Ma; Jirui Wang; Guoyue Chen; Xiujin Lan; Mei Deng; et al. (Genetic Resources and Crop Evolution, 2020)

A novel Ursane-type triterpene saponin from Ajuga multiflora - Yunzhi Li; Mingli Liang; Lu Ma; Qi Chen; Xian Huang (Natural Product Research, 2020)

Correction to: Identification and validation of a major and stably expressed QTL for spikelet number per spike in bread wheat - Jian Ma; Puyang Ding; Jiajun Liu; Ting Li; Yaya Zou; Ahsan Habib; Yang Mu; Huaping Tang; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Jirui Wang; et al. (Theoretical and Applied Genetics, 2020)

SIRT3 promotes the invasion and metastasis of cervical cancer cells by regulating fatty acid synthase - Li Xiu Xu; Li Jun Hao; Jun Qi Ma; Jing Kun Liu; Ayshamgul Hasim (Molecular and Cellular Biochemistry, 2020)

LncRNA SNHG3 promotes cell proliferation and invasion through the miR-384/hepatoma-derived growth factor axis in breast cancer - Qiuhong Ma; Xiangqin Qi; Xiaona Lin; Liang Li; Libo Chen; Wei Hu (Human Cell, 2020)

Interaction Between Variations in Dopamine D2 and Serotonin 2A Receptor is Associated with Short-Term Response to Antipsychotics in Schizophrenia - Liansheng Zhao; Huijuan Wang; Yamin Zhang; Jinxue Wei; Peiyan Ni; Hongyan Ren; Gang Li; Qiang Wang; Gavin P Reynolds; Weihua Yue; Wei Deng; Hao Yan; et al. (Neuroscience Bulletin, 2019)

Biogas production from anaerobic co-digestion of waste activated sludge: co-substrates and influencing parameters - Qi Yang; Bo Wu; Fubing Yao; Li He; Fei Chen; Yinghao Ma; Xiaoyu Shu; Kunjie Hou; Dongbo Wang; Xiaoming Li (Reviews in Environmental Science and Bio/Technology, 2019)

Identification and validation of a major and stably expressed QTL for spikelet number per spike in bread wheat - Jian Ma; Puyang Ding; Jiajun Liu; Ting Li; Yaya Zou; Ahsan Habib; Yang Mu; Huaping Tang; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Jirui Wang; et al. (Theoretical and Applied Genetics, 2019)

Isolation and synthesis of a new benzylated alkamide from the roots of Lepidium meyenii - Yan-Qing Ye; Zu-Hong Ma; Qiao-Fen Yang; Yan-Qi Sun; Rui-Qi Zhang; Run-Fang Wu; Xin Ren; Li-Juan Mu; Zhi-Yong Jiang; Min Zhou (Natural Product Research, 2019)

Combining potassium chloride leaching with vertical electrokinetics to remediate cadmium-contaminated soils - Qiang Ma; Jun Li; Charles C. C. Lee; Xinxian Long; Yongmao Liu; Qi-Tang Wu (Environmental Geochemistry and Health, 2019)

Diversification of the downy mildew resistance gene pool by introgression of a new gene, Pl35, from wild Helianthus argophyllus into oilseed and confection sunflowers (Helianthus annuus L.) - L. L. Qi; G. J. Ma; X. H. Li; G. J. Seiler (Theoretical and Applied Genetics, 2019)

Clerodane diterpenoids from Casearia kurzii and their cytotoxic activities - Yuan Shuo; Chenyue Zhang; Xueyuan Yang; Feng Liu; Qi Zhang; Annan Li; Jun Ma; Dongho Lee; Yasushi Ohizumi; Yuanqiang Guo (Journal of Natural Medicines, 2019)

QTL analysis of nodule traits and the identification of loci interacting with the type III secretion system in soybean - Jingyi Zhu; Jinhui Wang; Qingying Li; Jieqi Wang; Yang Liu; Jianyi Li; Lin Chen; Yan Shi; Shuping Li; Yongqian Zhang; Xueying Liu; Chao Ma; et al. (Molecular Genetics and Genomics, 2019)

MicroRNAs Involved in the Regulation of LC-PUFA Biosynthesis in Teleosts: miR-33 Enhances LC-PUFA Biosynthesis in Siganus canaliculatus by Targeting insig1 which in Turn Upregulates srebp1 - Jun Jun Sun; Li Guo Zheng; Cui Ying Chen; Jin Ying Zhang; Cui Hong You; Qing Hao Zhang; Hong Yu Ma; Óscar Monroig; Douglas R. Tocher; Shu Qi Wang; Yuan You Li (Marine Biotechnology, 2019)

A single-base change at a splice site in Wx-A1 caused incorrect RNA splicing and gene inactivation in a wheat EMS mutant line - Mi Luo; Jinjin Ding; Yu Li; Huaping Tang; Pengfei Qi; Jian Ma; Jirui Wang; Guoyue Chen; Zhien Pu; Wei Li; Zhongyi Li; Wendy Harwood; et al. (Theoretical and Applied Genetics, 2019)

Development of a duplex reverse transcription recombinase-aided amplification assay for respiratory syncytial virus incorporating an internal control - Juju Qi; Xinna Li; Yi Zhang; Xinxin Shen; Guowei Song; Jing Pan; Tao Fan; Ruihuan Wang; Lixin Li; Xuejun Ma (Archives of Virology, 2019)

Nodulation and Genomic Capacity of a Novel High-Latitude Bradyrhizobium japonicum HLNEAU001 - Yan Shi; Jianyi Li; Jinhui Wang; Rongsheng Zhu; Shuping Li; Qingying Li; Lin Chen; Jingyi Zhu; Jianan Zou; Jieqi Wang; Huilin Chang; Chao Ma; et al. (Journal of Soil Science and Plant Nutrition, 2019)

The influence of syntectonic sedimentation on thrust belt deformation: a kinematic model example from the triangle zone within the Western Kunlun thrust belt - Tong Sun; Jiafu Qi; Qiang Ni; Peiling Ma; Changwei Han; Qiang Li; Pengyu Gong (International Journal of Earth Sciences, 2019)

Limb Remote Ischemic Preconditioning Reduces Repeated Ketamine Exposure-Induced Adverse Effects in the Developing Brain of Rats - Ying Liu; An Qi Li; Wan Ma; Yu Bo Gao; Li Qin Deng; Chun Zhang; Jin Hai Meng (Journal of Molecular Neuroscience, 2019)

Genome-wide investigation of the MADS gene family and dehulling genes in tartary buckwheat (Fagopyrum tataricum) - Moyang Liu; Qiankun Fu; Zhaotang Ma; Wenjun Sun; Li Huang; Qi Wu; Zizhong Tang; Tongliang Bu; Chenglei Li; Hui Chen (Planta, 2019)

Testing the role of genetic variation of the MC4R gene in Chinese population in antipsychotic-induced metabolic disturbance - Yamin Zhang; Hongyan Ren; Qiang Wang; Wei Deng; Weihua Yue; Hao Yan; Liwen Tan; Qi Chen; Guigang Yang; Tianlan Lu; Lifang Wang; Fuquan Zhang; et al. (Science China Life Sciences, 2019)

Expression of the high molecular weight glutenin 1Ay gene from Triticum urartu in barley - Qiang Yang; Siyu Li; Xiaoyu Li; Jian Ma; Jirui Wang; Pengfei Qi; Guoyue Chen; Zhien Pu; Wei Li; Wendy Harwood; Zhongyi Li; Bao-Long Liu; et al. (Transgenic Research, 2019)

Stable expression and heredity of alien Glu-1Ssh in wheat-Aegilops sharonensis hybrid progenies - Xiaoyu Li; Qian Wang; Siyu Li; Jian Ma; Jirui Wang; Pengfei Qi; Guoyue Chen; Zhien Pu; Wei Li; Zongxiang Tang; Zehong Yan; Xiujin Lan; et al. (Genetic Resources and Crop Evolution, 2019)

Refined assessment of heavy metal-associated health risk due to the consumption of traditional animal medicines in humans - Tian-Tian Zuo; Yao-Lei Li; Huai-Zhen He; Hong-Yu Jin; Lei Zhang; Lei Sun; Fei Gao; Qi Wang; Yuan-Jun Shen; Shuang-Cheng Ma; Lang-Chong He (Environmental Monitoring and Assessment, 2019)

The effect of redox capacity of humic acids on hexachlorobenzene dechlorination during the anaerobic digestion process - Dongyang Li; Beidou Xi; Yingjun Li; Xiaowei Wang; Tianxue Yang; Hong Yu; Caihong Huang; Jianchao Zhu; Qi Li; Xing Peng; Zhifei Ma (Environmental Science and Pollution Research, 2019)

Development and molecular cytogenetic identification of a new wheat-rye 4R chromosome disomic addition line with resistances to powdery mildew, stripe rust and sharp eyespot - Diaoguo An; Pengtao Ma; Qi Zheng; Shulan Fu; Lihui Li; Fangpu Han; Guohao Han; Jing Wang; Yunfeng Xu; Yuli Jin; Qiaoling Luo; Xiaotian Zhang (Theoretical and Applied Genetics, 2019)

A case control study on the prevalence of enterovirus in children samples and its association with diarrhea - Xin-xin Shen; Fang-zhou Qiu; Gui-xia Li; Meng-chuan Zhao; Ji Wang; Chen Chen; Li Zhao; Ju-Ju Qi; Hong Liu; Yi Zhang; Xiao-zhou He; Le Wang; et al. (Archives of Virology, 2019)

Soil micro-food web interactions and rhizosphere priming effect - Xinchang Kou; Tongqing Su; Ningning Ma; Qi Li; Peng Wang; Zhengfang Wu; Wenju Liang; Weixin Cheng (Plant and Soil, 2018)

Frond transformation system mediated by Agrobacterium tumefaciens for Lemna minor - Gui-Li Yang; Yang Fang; Ya-Liang Xu; Li Tan; Qi Li; Yang Liu; Fan Lai; Yan-Ling Jin; An-Ping Du; Kai-Ze He; Xin-Rong Ma; Hai Zhao (Plant Molecular Biology, 2018)

Molecular role of cytokinin in bud activation and outgrowth in apple branching based on transcriptomic analysis - Guofang Li; Ming Tan; Fang Cheng; Xiaojie Liu; Siyan Qi; Hongfei Chen; Dong Zhang; Caiping Zhao; Mingyu Han; Juanjuan Ma (Plant Molecular Biology, 2018)

Lack of Association Between DNMT3B Polymorphisms and Sporadic Parkinson’s Disease in a Han Chinese Population - Hong Pan; Jun-Yi Shen; Juan-Juan Du; Shi-Shuang Cui; Jin Liu; Yi-Qi Lin; Yi-Xi He; Yang Fu; Chao Gao; Gen Li; Sheng-Di Chen; Jian-Fang Ma (Neuroscience Bulletin, 2018)

Ligation Based Assembly and Polymerase Chain Reaction-Based Assembly for Extraordinary Adenine/Thymine Rich DNA - Chen Yu; Li Xu; Wenxian Piao; Xiao Bao; Hairong Wang; Meng Xing; Jieyu Wu; Bang Xu; Penghui Yuan; Yangxiu Wu; Wangyun He; Jinhuan Qi; et al. (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Precipitation characteristics over the steep slope of the Himalayas in rainy season observed by TRMM PR and VIRS - Yunfei Fu; Xiao Pan; Tao Xian; Guosheng Liu; Lei Zhong; Qi Liu; Rui Li; Yu Wang; Ming Ma (Climate Dynamics, 2018)

Transport of dissolved black carbon from the Prydz Bay Shelf, Antarctica to the deep Southern Ocean - Ziming Fang; Weifeng Yang; Min Chen; Aron Stubbins; Haoyang Ma; Renming Jia; Qi Li; Qianna Chen (Limnology and Oceanography, 2018)
Dissolved black carbon (DBC) is one of the largest pools of molecularly identifiable carbon in the ocean. In the deep ocean, DBC appears to persist for millennia, whereas it can be rapidly degraded by sunlight in surface waters. In Antarctica, the downward transport of dense shelf water (DSW) exports a massive volume of water to the deep Southern Ocean each year. If this sinking DSW is enriched in DBC, it may allow a route for DBC to escape degradation by sunlight in the surface ocean and become sequestered in the deep waters of the global ocean. To investigate this possibility, we quantified dissolved organic carbon (DOC), DBC, and ancillary properties in the waters of an Antarctic shelf sea (Prydz Bay) and adjacent waters. DBC concentrations in Prydz Bay DSW (1.2 ± 0.3 μ mol L −1 ) were elevated compared to those in circumpolar deep water (0.49 ± 0.07 μ mol L −1 ). The water column distribution of DBC in Prydz Bay suggested that sediments were the main source of DBC in DSW. A mixing model incorporating seawater oxygen isotopes (H 2 δ 18 O) indicated that Prydz Bay DSW transported DBC and DOC into the deep Southern Ocean. We estimate that the downward transport of DSW from Prydz Bay could contribute 4–9% (66–150 Gg yr −1 ) and 2–4% (3700–8500 Gg yr −1 ) to the DBC and DOC concentrations in Antarctic Bottom Water, respectively. Thus, the downward transport of DBC along the Antarctic shelf/slope is likely a significant source of DBC to the deep waters of the Southern and Global Ocean.

Influence of Bacillus subtilis B068150 on cucumber rhizosphere microbial composition as a plant protective agent - Lihua Li; Jincai Ma; A. Mark Ibekwe; Qi Wang; Ching-Hong Yang (Plant and Soil, 2018)

Development of a reverse transcription recombinase-aided amplification assay for the detection of coxsackievirus A10 and coxsackievirus A6 RNA - Teng-fei Yan; Xin-na Li; Le Wang; Chen Chen; Su-xia Duan; Ju-ju Qi; Li-Xin Li; Xue-jun Ma (Archives of Virology, 2018)

Effect of exogenous inoculants on enhancing oil recovery and indigenous bacterial community dynamics in long-term field pilot of low permeability reservoir - Jing Li; Shuwen Xue; Chunqiu He; Huixia Qi; Fulin Chen; Yanling Ma (World Journal of Microbiology and Biotechnology, 2018)

MicroRNA-30e regulates neuroinflammation in MPTP model of Parkinson’s disease by targeting Nlrp3 - Dongsheng Li; Hongqi Yang; Jianjun Ma; Sha Luo; Siyuan Chen; Qi Gu (Human Cell, 2018)

Evaluation of vulnerable PM2.5-exposure individuals: a repeated-measure study in an elderly population - Haiyan Chu; Junyi Xin; Qi Yuan; Xu Zhang; Wang Pan; Xinying Zeng; Yaoyao Chen; Gaoxiang Ma; Yuqiu Ge; Mulong Du; Na Tong; Xiaobo Li; et al. (Environmental Science and Pollution Research, 2018)

U-tube based near-surface environmental monitoring in the Shenhua carbon dioxide capture and storage (CCS) project - Qi Li; Ranran Song; Hui Shi; Jianli Ma; Xuehao Liu; Xiaochun Li (Environmental Science and Pollution Research, 2018)

Evaluation of strength and failure of brittle rock containing initial cracks under lithospheric conditions - Xiaozhao Li; Chengzhi Qi; Zhushan Shao; Chao Ma (Acta Geophysica, 2018)

The complete mitochondrial genome of Amphioctopus marginatus (Cephalopoda: Octopodidae) and the exploration for the optimal DNA barcoding in Octopodidae - Yan Tang; Xiaodong Zheng; Yuanyuan Ma; Rubin Cheng; Qi Li (Conservation Genetics Resources, 2018)

Use of freeze-dried bone allografts in osteoporotic patients undergoing median sternotomy - Mei Liang; Jianzhou Liu; Qi Miao; Guotao Ma; Xingrong Liu; Xiaofeng Li; Chaoji Zhang (Cell and Tissue Banking, 2018)

An expression atlas of miRNAs in Arabidopsis thaliana - Le Xu; Yugang Hu; Ying Cao; Jingrui Li; Ligeng Ma; Yan Li; Yijun Qi (Science China Life Sciences, 2018)

Low phosphorus and competition affect Chinese fir cutting growth and root organic acid content: does neighboring root activity aggravate P nutrient deficiency? - Pengfei Wu; Guangyu Wang; Taimoor Hassan Farooq; Qi Li; Xianhua Zou; Xiangqing Ma (Journal of Soils and Sediments, 2017)

Abnormal Somatic Embryo Reduction and Recycling in Grapevine Regeneration - Wei Ji; Yaoxing Luo; Rongrong Guo; Xuexue Li; Qi Zhou; Xiaohe Ma; Yuejin Wang (Journal of Plant Growth Regulation, 2017)

Mineral chemistry indicates the petrogenesis of rhyolite from the southwestern Okinawa Trough - Zuxing Chen; Zhigang Zeng; Xiaoyuan Wang; Yuxiang Zhang; Xuebo Yin; Shuai Chen; Yao Ma; Xiaohui Li; Hanyan Qi (Journal of Ocean University of China, 2017)

Association between SSR markers and fibre traits in sea island cotton (Gossypium barbadense) germplasm resources - QI MA; JING ZHAO; HAI LIN; XINZHU NING; PING LIU; FUJUN DENG; AIJUN SI; JILIAN LI (Journal of Genetics, 2017)

Cloning and characterization of Agp1, the gene encoding the small subunit of ADP-glucose pyrophosphorylase from wheat and its relatives - Xiao-Wei Zhang; Qing Wang; Ling-Ling Zhang; Xiao-Juan Zhong; Qian-Tao Jiang; Jian Ma; Peng-Fei Qi; Wei Li; Guo-Yue Chen; Xiu-Jin Lan; Mei Deng; Zhen-Xiang Lu; et al. (Biologia, 2017)

Yimu San improves obstetric ability of pregnant mice by increasing serum oxytocin levels and connexin 43 expression in uterine smooth muscle - Qi-huan Wang; Shuang Zhang; Li-meng Qin; Wen-jun Zhang; Feng-hua Liu; Jian-qin Xu; Yun-fei Ma; Ke-dao Teng (Journal of Zhejiang University-SCIENCE B, 2017)

Occurrence of polycyclic aromatic hydrocarbons in various types of raw oilseeds from different regions of China - Yun-Qi Wen; Yu-Lan Liu; Li-Li Xu; Wen-xiu Yu; Yu-xiang Ma (Food Additives & Contaminants Part B-Surveillance, 2017)

Prevalence of S gene mutations within the major hydrophilic region of hepatitis B virus in patients in Dongguan, southern China - Siping Li; Mingyu Xie; Wenrui Li; Qi Peng; Baimao Zhong; Xiaomei Lu; Qiang Ma (Archives of Virology, 2017)

Novel CD137 Gene Polymorphisms and Susceptibility to Ischemic Stroke in the Northern Chinese Han Population - Shuang Zhang; Zongmin Li; Ruyou Zhang; Xiaoying Li; Hewei Zheng; Qi Ma; Hui Zhang; Wenying Hou; Feng Zhang; Yingnan Wu; Litao Sun; Jiawei Tian (NeuroMolecular Medicine, 2017)

Phylogenetic analysis of IDD gene family and characterization of its expression in response to flower induction in Malus - Sheng Fan; Dong Zhang; Libo Xing; Siyan Qi; Lisha Du; Haiqin Wu; Hongxia Shao; Youmei Li; Juanjuan Ma; Mingyu Han (Molecular Genetics and Genomics, 2017)

Adjuvant effects mediated by the carbohydrate recognition domain of Agrocybe aegerita lectin interacting with avian influenza H9N2 viral surface glycosylated proteins - Li-bao Ma; Bao-yang Xu; Min Huang; Lv-hui Sun; Qing Yang; Yi-jie Chen; Ya-lin Yin; Qi-gai He; Hui Sun (Journal of Zhejiang University-SCIENCE B, 2017)

miR-30a-5p enhances paclitaxel sensitivity in non-small cell lung cancer through targeting BCL-2 expression - Xiaojie Xu; Shuai Jin; Yongfu Ma; Zhongyi Fan; Zhifeng Yan; Wenchao Li; Qi Song; Wenye You; Zhaohui Lyu; Yeqiong Song; Pingan Shi; Ying Liu; et al. (Journal of Molecular Medicine, 2017)

A new three-band spectral index for mitigating the saturation in the estimation of leaf area index in wheat - Zhongsheng Cao; Tao Cheng; Xue Ma; Yongchao Tian; Yan Zhu; Xia Yao; Qi Chen; Shiyao Liu; Ziyu Guo; Qiaomei Zhen; Xin Li (International Journal of Remote Sensing, 2017)

Increases of Galectin-1 and its S-nitrosylated form in the Brain Tissues of Scrapie-Infected Rodent Models and Human Prion Diseases - Yan-Jun Guo; Qi Shi; Xiao-Dong Yang; Jian-Le Li; Yue Ma; Kang Xiao; Cao Chen; Jun Han; Xiao-Ping Dong (Molecular Neurobiology, 2017)

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Genetic diagnosis of a Chinese multiple endocrine neoplasia type 2A family through whole genome sequencing - Zhen-Fang Du; Peng-Fei Li; Jian-Qiang Zhao; Zhi-Lie Cao; Feng Li; Ju-Ming Ma; Xiao-Ping Qi (Journal of Biosciences, 2017)

Production of eicosapentaenoic acid (EPA, 20:5n-3) in maize (Zea mays L.) through the alternative ∆8 desaturation pathway mediated by particle bombardment - Chenchen Wang; Xiao Yang; Haizhen Ma; Jiang Liu; Jing Chen; Jiedao Zhang; Shuting Dong; Baoxiu Qi; Xinzheng Li (Acta Physiologiae Plantarum, 2017)

Molecular cytogenetic identification of a wheat–Thinopyrum ponticum translocation line resistant to powdery mildew - FANG HE; YINGUANG BAO; XIAOLEI QI; YINGXUE MA; XINGFENG LI; HONGGANG WANG (Journal of Genetics, 2017)

A bifunctional type III polyketide synthase from raspberry (Rubus idaeus L.) with both chalcone synthase and benzalacetone synthase activity - Hui-Li Guo; Ya-Dong Yang; Ya-Di Ma; Wen-Bin Liu; Jing Feng; Zai-Qi Luo; He-Shu Lu; Chun-Mei Liu; Ming-Feng Yang; You-Nian Wang; Lan-Qing Ma (Journal of Plant Biochemistry and Biotechnology, 2017)

A Novel Association of the Suppressor of Cytokine Signaling 1 (SOCS1) Gene Polymorphisms in Ischemic Stroke Patients - Qi Ma; Nana Liu; Ruyou Zhang; Xiaoying Li; Hui Zhang; Zongmin Li; Shuang Zhang; Wenying Hou; Qianhui Zhu; Hewei Zheng; Litao Sun (NeuroMolecular Medicine, 2016)

Molecular epidemiology of the enteroviruses associated with hand, foot and mouth disease/herpangina in Dongguan, China, 2015 - Qi Peng; Mingyu Xie; Yinghong Zhang; Qian Liu; Wenrui Li; Siping Li; Qiang Ma; Xiaomei Lu; Baimao Zhong (Archives of Virology, 2016)

Development of a highly sensitive real-time nested RT-PCR assay in a single closed tube for detection of enterovirus 71 in hand, foot, and mouth disease - Peihua Niu; Shunxiang Qi; Benzhang Yu; Chen Zhang; Ji Wang; Qi Li; Xuejun Ma (Archives of Virology, 2016)

Induced growth promotion and higher salt tolerance in the halophyte grass Puccinellia tenuiflora by beneficial rhizobacteria - Shu-Qi Niu; Hui-Ru Li; Paul W. Paré; Mina Aziz; Suo-Min Wang; Huazhong Shi; Jing Li; Qing-Qing Han; Shi-Qian Guo; Jian Li; Qiang Guo; Qing Ma; et al. (Plant and Soil, 2016)

Occurrence and fate of PBDEs and novel brominated flame retardants in a wastewater treatment plant in Harbin, China - Bo Li; Shao-Jing Sun; Chun-Yan Huo; Wen-Long Li; Ning-Zheng Zhu; Hong Qi; Ling-Jun Kong; Yi-Fan Li; Wan-Li Ma (Environmental Science and Pollution Research, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

FGF21 ameliorates nonalcoholic fatty liver disease by inducing autophagy - Shenglong Zhu; Yunzhou Wu; Xianlong Ye; Lei Ma; Jianying Qi; Dan Yu; Yuquan Wei; Guangxiao Lin; Guiping Ren; Deshan Li (Molecular and Cellular Biochemistry, 2016)

Salicylic acid-induced cytosolic acidification increases the accumulation of phenolic acids in Salvia miltiorrhiza cells - Xiuhong Li; Hongbo Guo; Yuexin Qi; Hailong Liu; Xiaoru Zhang; Pengda Ma; Zongsuo Liang; Juane Dong (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

IgG4 anti-phospholipase A2 receptor might activate lectin and alternative complement pathway meanwhile in idiopathic membranous nephropathy: an inspiration from a cross-sectional study - Yang Yang; Chao Wang; Liping Jin; Fagui He; Changchun Li; Qingman Gao; Guanglei Chen; Zhijun He; Minghui Song; Zhuliang Zhou; Fujun Shan; Ka Qi; et al. (Immunologic Research, 2016)

A pilot study on using chlorine dioxide gas for disinfection of gastrointestinal endoscopes - Ying Yi; Li-mei Hao; Shu-ren Ma; Jin-hui Wu; Tao Wang; Song Lin; Zong-xing Zhang; Jian-cheng Qi (Journal of Zhejiang University-SCIENCE B, 2016)

The occurrence and fate of siloxanes in wastewater treatment plant in Harbin, China - Bo Li; Wen-Long Li; Shao-Jing Sun; Hong Qi; Wan-Li Ma; Li-Yan Liu; Zi-Feng Zhang; Ning-Zheng Zhu; Yi-Fan Li (Environmental Science and Pollution Research, 2016)

Structure and expression of phosphoglucan phosphatase genes of Like Sex Four1 and Like Sex Four2 in barley - Jian Ma; Shang Gao; Qian-Tao Jiang; Qiang Yang; Min Sun; Ji-Rui Wang; Peng-Fei Qi; Ya-Xi Liu; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; et al. (Genetica, 2016)

Effects of Saline Water Irrigation and N Application Rate on NH3 Volatilization and N use Efficiency in a Drip-Irrigated Cotton Field - Guangwei Zhou; Wen Zhang; Lijuan Ma; Huijuan Guo; Wei Min; Qi Li; Na Liao; Zhenan Hou (Water, Air, & Soil Pollution, 2016)

Multiple characteristics analysis of Alzheimer’s electroencephalogram by power spectral density and Lempel–Ziv complexity - Xiaokun Liu; Chunlai Zhang; Zheng Ji; Yi Ma; Xiaoming Shang; Qi Zhang; Wencheng Zheng; Xia Li; Jun Gao; Ruofan Wang; Jiang Wang; Haitao Yu (Cognitive Neurodynamics, 2016)

Differential expression of ATP-gated P2X receptors in DRG between chronic neuropathic pain and visceralgia rat models - Lin Chen; Yu-wei Liu; Kai Yue; Qin Ru; Qi Xiong; Bao-miao Ma; Xiang Tian; Chao-ying Li (Purinergic Signalling, 2016)

Involvement of NADPH oxidases and non-muscle myosin light chain in senescence of endothelial progenitor cells in hyperlipidemia - Ting-Bo Li; Jie-Jie Zhang; Bin Liu; Wei-Qi Liu; Yan Wu; Xiao-Ming Xiong; Xiu-Ju Luo; Qi-Lin Ma; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Applying systematic conservation planning to constitute a protection strategy for broad-leaved Korean pine forests in Changbai Mountains, China - Lin Ma; Gong-qi Sun; Yi Qu; Jun-qing Li (Journal of Mountain Science, 2016)

Feasibility of diagnosing unstable plaque in patients with acute coronary syndrome using iMap-IVUS - Jian Liu; Zhao Wang; Wei-min Wang; Qi Li; Yu-liang Ma; Chuan-fen Liu; Ming-yu Lu; Hong Zhao (Journal of Zhejiang University-SCIENCE B, 2015)

Assessment of Sediment Risk in the North End of Tai Lake, China: Integrating Chemical Analysis and Chronic Toxicity Testing with Chironomus dilutus - Hongxue Qi; Ping Ma; Huizhen Li; Jing You (Archives of Environmental Contamination and Toxicology, 2015)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Meiotic chromosome configurations in triploid progeny from reciprocal crosses between wild-type diploid and natural tetraploid loach Misgurnus anguillicaudatus in China - Ya-Juan Li; Yang-Chun Gao; He Zhou; Hai-Yan Ma; Jia-Qi Li; Katsutoshi Arai (Genetica, 2015)

Molecular cloning and characterization of a pathogenesis-related protein SmPR10-1 from Salvia miltiorrhiza - Le Zhao; Li-gang Ma; Zhi-shuang Wang; Mei-lan Chen; Ye Shen; Lu-qi Huang (Acta Physiologiae Plantarum, 2015)

Inhibition of myosin light chain kinase reduces NADPH oxidase-mediated oxidative injury in rat brain following cerebral ischemia/reperfusion - Hong-Feng Zhang; Ting-Bo Li; Bin Liu; Zheng Lou; Jie-Jie Zhang; Jing-Jie Peng; Xiao-Jie Zhang; Qi-Lin Ma; Jun Peng; Xiu-Ju Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Decreased PSD95 expression in medial prefrontal cortex (mPFC) was associated with cognitive impairment induced by sevoflurane anesthesia - Yun-zhi Ling; Wei Ma; Li Yu; Ye Zhang; Qi-sheng Liang (Journal of Zhejiang University-SCIENCE B, 2015)

Characterization of genes encoding Starch Branching Enzyme I from Triticum monococcum and its diploid wheat relatives - Xiu-Ying Wang; Chang-Shui Wang; Jian Ma; Ji-Rui Wang; Ya-Xi Liu; Peng-Fei Qi; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; You-Liang Zheng; Qian-Tao Jiang (Biologia, 2015)

Metabolic engineering of 2-phenylethanol pathway producing fragrance chemical and reducing lignin in Arabidopsis - Guang Qi; Dian Wang; Li Yu; Xianfeng Tang; Guohua Chai; Guo He; Wenxuan Ma; Shengying Li; Yingzhen Kong; Chunxiang Fu; Gongke Zhou (Plant Cell Reports, 2015)

Contribution of mitochondrial function to exercise-induced attenuation of renal dysfunction in spontaneously hypertensive rats - Qi Gu; Li Zhao; Yan-Ping Ma; Jian-Dong Liu (Molecular and Cellular Biochemistry, 2015)

Quantitative trait locus analysis and fine mapping of the qPL6 locus for panicle length in rice - Lin Zhang; Jianjun Wang; Junmin Wang; Linyou Wang; Bin Ma; Longjun Zeng; Yongbin Qi; Qun Li; Zuhua He (Theoretical and Applied Genetics, 2015)

Elevation, moisture and shade drive the functional and phylogenetic meadow communities’ assembly in the northeastern Tibetan Plateau - W. Qi; X. Zhou; M. Ma; J. M. H. Knops; W. Li; G. Du (Community Ecology, 2015)

Development and characterization of 18 microsatellite markers for the Babylonia lutosa - Gang Xiong; Xiao Ma; Xiao-qing Wang; Zhi-Nan Zeng; Dan-Li Zhu; Li Kang; Qi-Sheng Wu (Conservation Genetics Resources, 2015)

The Marginal Division of the Striatum and Hippocampus Has Different Role and Mechanism in Learning and Memory - Si-Yun Shu; Gang Jiang; Qi-Yi Zeng; Bin Wang; Hong Li; Lin Ma; Harry Steinbusch; Cai Song; Wood-Yee Chan; Xu-Hong Chen; Yon-Ming Wu; Rong Bao; et al. (Molecular Neurobiology, 2015)

Association mapping of salinity and alkalinity tolerance in improved japonica rice (Oryza sativa L. subsp. japonica Kato) germplasm - Di Cui; Chang-ying Xu; Chun-gang Yang; Qi-xing Zhang; Jun-guo Zhang; Xiao-ding Ma; Yong-li Qiao; Gui-lan Cao; San-yuan Zhang; Long-zhi Han (Genetic Resources and Crop Evolution, 2015)

Comparative analysis of selected innate immune-related genes following infection of immortal DF-1 cells with highly pathogenic (H5N1) and low pathogenic (H9N2) avian influenza viruses - Ai-ling Liu; Yu-feng Li; Wenbao Qi; Xiu-li Ma; Ke-xiang Yu; Bing Huang; Ming Liao; Feng Li; Jie Pan; Min-xun Song (Virus Genes, 2015)

Polycyclic aromatic hydrocarbons in Chinese surface soil: occurrence and distribution - Wan-Li Ma; Li-Yan Liu; Chong-Guo Tian; Hong Qi; Hong-Liang Jia; Wei-Wei Song; Yi-Fan Li (Environmental Science and Pollution Research, 2015)

Molecular cloning, expression pattern, and 3D structural prediction of the cold inducible RNA-binding protein (CIRP) in Japanese flounder (Paralichthys olivaceus) - Xiao Yang; Jinning Gao; Liman Ma; Zan Li; Wenji Wang; Zhongkai Wang; Haiyang Yu; Jie Qi; Xubo Wang; Zhigang Wang; Quanqi Zhang (Journal of Ocean University of China, 2015)

Humanin attenuates Alzheimer-like cognitive deficits and pathological changes induced by amyloid β-peptide in rats - Gao-Shang Chai; Dong-Xiao Duan; Rong-Hong Ma; Jian-Ying Shen; Hong-Lian Li; Zhi-Wei Ma; Yu Luo; Lu Wang; Xin-Hua Qi; Qun Wang; Jian-Zhi Wang; Zelan Wei; et al. (Neuroscience Bulletin, 2014)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

EPO-Dependent Activation of PI3K/Akt/FoxO3a Signalling Mediates Neuroprotection in In Vitro and In Vivo Models of Parkinson’s Disease - Yu Jia; Shi-Jing Mo; Qi-Qi Feng; Ma-Li Zhan; Li-Si OuYang; Jia-Chang Chen; Yu-Xin Ma; Jia-Jia Wu; Wan-Long Lei (Journal of Molecular Neuroscience, 2014)

Occurrence of Endocrine-Disrupting Phenols and Estrogens in Water and Sediment of the Songhua River, Northeastern China - Zifeng Zhang; Nanqi Ren; Kurunthachalam Kannan; Jun Nan; Liyan Liu; Wanli Ma; Hong Qi; Yifan Li (Archives of Environmental Contamination and Toxicology, 2014)

Antitumor Activity of Gemcitabine Can Be Potentiated in Pancreatic Cancer through Modulation of TLR4/NF-κB signaling by 6-Shogaol - Ling Zhou; Lianwen Qi; Lifeng Jiang; Ping Zhou; Jiang Ma; Xiaojun Xu; Ping Li (The AAPS Journal, 2014)

Alda-1 reduces cerebral ischemia/reperfusion injury in rat through clearance of reactive aldehydes - Si-Hai Fu; Hong-Feng Zhang; Zhong-Bao Yang; Ting-Bo Li; Bin Liu; Zheng Lou; Qi-Lin Ma; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Concentration, Sources and Human Exposure of Polybrominated Diphenyl Ethers in Indoor Dust in Heilongjiang Province, China - Ning-zheng Zhu; Hong Qi; Feng Zhang; Wan-li Ma; Li-yan Liu; Yi-fan Li (Bulletin of Environmental Contamination and Toxicology, 2013)

Polycyclic aromatic hydrocarbons in water, sediment and soil of the Songhua River Basin, China - Wan-Li Ma; Li-Yan Liu; Hong Qi; Zi-Feng Zhang; Wei-Wei Song; Ji-Min Shen; Zhong-Lin Chen; Nan-Qi Ren; Josey Grabuski; Yi-Fan Li (Environmental Monitoring and Assessment, 2013)

Urinary Concentrations of Parabens in Chinese Young Adults: Implications for Human Exposure - Wan-Li Ma; Lei Wang; Ying Guo; Li-Yan Liu; Hong Qi; Ning-Zheng Zhu; Chong-Jing Gao; Yi-Fan Li; Kurunthachalam Kannan (Archives of Environmental Contamination and Toxicology, 2013)

The improvement of the one-dimensional Mellor-Yamada and K-profile parameterization turbulence schemes with the non-breaking surface wave-induced vertical mixing - Yan Li; Fangli Qiao; Xunqiang Yin; Qi Shu; Hongyu Ma (Acta Oceanologica Sinica, 2013)

Implications for long-range atmospheric transport of polycyclic aromatic hydrocarbons in Lhasa, China - Wan-Li Ma; Hong Qi; Sonam Baidron; Li-Yan Liu; Meng Yang; Yi-Fan Li (Environmental Science and Pollution Research, 2013)

New kaurene diterpenoid glycosides from fenugreek seeds - Xu Pang; Li-Ping Kang; He-Shui Yu; Yang Zhao; Cheng-Qi Xiong; Jie Zhang; Bai-Ping Ma (Natural Product Research, 2013)

Molecular cytogenetic characterization of a new wheat–rye 4R chromosome translocation line resistant to powdery mildew - Diaoguo An; Qi Zheng; Yilin Zhou; Pengtao Ma; Zhenling Lv; Lihui Li; Bin Li; Qiaoling Luo; Hongxing Xu; Yunfeng Xu (Chromosome Research, 2013)

β-Orcinol-type depsides from the lichen Thamnolia vermicularis - Wen-Juan Xiang; Qi-Qi Wang; Lei Ma; Li-Hong Hu (Natural Product Research, 2013)

Synchronization regulation in a model of coupled neural masses - Zhen Ma; Weidong Zhou; Shujuan Geng; Qi Yuan; Xueli Li (Biological Cybernetics, 2013)

Overlapping transcription structure of human cytomegalovirus UL140 and UL141 genes - Yanping Ma; Mali Li; Bo Zheng; Ning Wang; Shuang Gao; Lin Wang; Ying Qi; Zhengrong Sun; Qiang Ruan (Journal of Biosciences, 2013)

Cloning and expression analysis of vasa during the reproductive cycle of Korean rockfish, Sebastes schlegeli - Weijie Mu; Haishen Wen; Feng He; Jifang Li; Miao Liu; Ruiqin Ma; Yuanqing Zhang; Jian Hu; Baoxia Qi (Journal of Ocean University of China, 2013)

Transcription characteristics of the human cytomegalovirus UL13 gene - Ning Wang; Yanping Ma; Mali Li; Shuang Gao; Lin Wang; Ying Qi; Yaohua Ji; Zhengrong Sun; Qiang Ruan (Archives of Virology, 2013)

Association of CASP9, CASP10 gene polymorphisms and tea drinking with colorectal cancer risk in the Han Chinese population - He Liu; Xia Jiang; Ming-wu Zhang; Yi-feng Pan; Yun-xian Yu; Shan-chun Zhang; Xin-yuan Ma; Qi-long Li; Kun Chen (Journal of Zhejiang University-SCIENCE B, 2013)

Expression patterns of Nurr1 in rat retina development - Yingmin Li; Qian Qi; Bin Cong; Weibo Shi; Xia Liu; Guozhong Zhang; Chunling Ma (Journal of Molecular Histology, 2012)

Clinical significance of detection of antibodies to fetal and adult acetylcholine receptors in myasthenia gravis - Qi-Guang Shi; Zhi-Hong Wang; Xiao-Wei Ma; Da-Qi Zhang; Chun-Sheng Yang; Fu-Dong Shi; Li Yang (Neuroscience Bulletin, 2012)

Tree-ring reconstruction of summer temperature for A.D. 1475–2003 in the central Hengduan Mountains, Northwestern Yunnan, China - Zong-Shan Li; Qi-Bin Zhang; Keping Ma (Climatic Change, 2012)

Human cytomegalovirus RL13 gene transcripts in a clinical strain - Mali Li; Yanping Ma; Yaohua Ji; Rong He; Ying Qi; Zhengrong Sun; Ning Wang; Shuang Gao; Qiang Ruan (Virus Genes, 2011)

Expression patterns of cytochrome P450 aromatase genes during ovary development and their responses to temperature stress in female yellow catfish (Pelteobagrus fulvidraco) - Miao Liu; Haishen Wen; Feng He; Jifang Li; Dan Shi; Jian Hu; Yuanqing Zhang; Ruiqin Ma; Weijie Mu; Baoxia Qi (Journal of Ocean University of China, 2011)

Synthesis and evaluation of κ-opioid receptor agonistic activity and antinociceptive effect of novel morphine analogues, 7α-phenyl-6α,14α-endo-etheno-tetrahydrothebaine with substituted o-, m- and p-amino group - Hong Qi; Wei Li; Yu Qiu; Yong-yao Cui; Jian Ma; Xiao-ling Gao; Yi-bin Zeng; Jie Yang; Yun Tang; Xing-hai Wang; Wei Sheng; Qiong Xie; et al. (Medicinal Chemistry Research, 2011)

Physiology and cell biology of acupuncture observed in calcium signaling activated by acoustic shear wave - Geng Li; Jie-Ming Liang; Pei-Wen Li; Xiaoqiang Yao; Peter Zhong Pei; Wei Li; Qi-Hua He; Xifei Yang; Queenie C. C. Chan; Paul Y. S. Cheung; Qi Yuan Ma; Siu Kam Lam; et al. (Pflügers Archiv - European Journal of Physiology, 2011)

Development of genetically engineered CD4+ and CD8+ T cells expressing TCRs specific for a M. tuberculosis 38-kDa antigen - Wei Luo; Xiao-Bing Zhang; Yong-Ta Huang; Pei-Pei Hao; Zhen-Min Jiang; Qian Wen; Ming-Qian Zhou; Qi Jin; Li Ma (Journal of Molecular Medicine, 2011)

Interpolation of near offset using surface-related multiples - Shu-Juan Guo; Zhen-Chun Li; Zhao-Qi Tong; Fang-Zheng Ma; Jian-Hui Liu (Applied Geophysics, 2011)

Spatial and seasonal variation of polychlorinated biphenyls in Songhua River, China - Hong You; Jing Ding; Xue-Song Zhao; Yi-Fan Li; Li-Yan Liu; Wan-Li Ma; Hong Qi; Ji-Min Shen (Environmental Geochemistry and Health, 2011)

Characterization of Exserohilum rostratum, a new causal agent of banana leaf spot disease in China - Shan-Hai Lin; Si-Liang Huang; Qi-Qin Li; Chun-Jin Hu; Gang Fu; Li-Ping Qin; Yue-Feng Ma; Ling Xie; Zhen-Lu Cen; Wei-Hong Yan (Australasian Plant Pathology, 2011)

Enhanced protection against nasopharyngeal carriage of Streptococcus pneumoniae elicited by oral multiantigen DNA vaccines delivered in attenuated Salmonella typhimurium - Qiao Zhang; Qianli Ma; Qi Li; Wei Yao; Changzheng Wang (Molecular Biology Reports, 2011)

Seasonal and Spatial Variations of Air Concentrations of Polycyclic Aromatic Hydrocarbons in Northeastern Chinese Urban Region - Wan-li Ma; Hong Qi; Yi-fan Li; Li-yan Liu; De-zhi Sun; De-gao Wang; Zhi Zhang; Chong-guo Tian; Ji-min Shen (Bulletin of Environmental Contamination and Toxicology, 2011)

Cloning and Characterization of the BcTuR3 Gene Related to Resistance to Turnip Mosaic Virus (TuMV) from Non-heading Chinese Cabbage - Jingfan Ma; Xilin Hou; Dong Xiao; Li Qi; Feng Wang; Feifei Sun; Qian Wang (Plant Molecular Biology Reporter, 2010)

Transcription pattern of UL131A-128 mRNA in clinical strains of human cytomegalovirus - Zhengrong Sun; Gaowei Ren; Yanping Ma; Ning Wang; Yaohua Ji; Ying Qi; Mali Li; Rong He; Qiang Ruan (Journal of Biosciences, 2010)

Alleviation of ovariectomy-induced osteoporosis in rats by Panax notoginseng saponins - Yang Shen; Yong-Qi Li; Shao-Ping Li; Lin Ma; Li-Ju Ding; Hui Ji (Journal of Natural Medicines, 2010)

Meiotic nondisjunction in resynthesized Brassica napus and generation of aneuploids through microspore culture and their characterization - Jing Wen; Xin-hua Zeng; Yuan-yuan Pu; Li-ping Qi; Zai-yun Li; Jin-xing Tu; Chao-zhi Ma; Jin-xiong Shen; Ting-dong Fu (Euphytica, 2010)

Polycyclic Aromatic Hydrocarbons and Polychlorinated Biphenyls in Topsoils of Harbin, China - Wan-Li Ma; Yi-Fan Li; De-Zhi Sun; Hong Qi (Archives of Environmental Contamination and Toxicology, 2009)

Complement factor H Y402H polymorphism, plasma concentration and risk of coronary artery disease - Qi Qian; Zhong Chen; Genshan Ma; Yibo Jiang; Yi Feng; Chengxing Shen; Yuyu Yao; Jiandong Ding; Qiming Dai; Yongjun Li (Molecular Biology Reports, 2009)

Three-class classification models of logS and logP derived by using GA–CG–SVM approach - Hui Zhang; Ming-Li Xiang; Chang-Ying Ma; Qi Huang; Wei Li; Yang Xie; Yu-Quan Wei; Sheng-Yong Yang (Molecular Diversity, 2009)

Pathological lesions and viral localization of Influenza A (H5N1) virus in experimentally infected Chinese rhesus macaques: implications for pathogenesis and viral transmission - Yunxin Chen; Wei Deng; Chunshi Jia; Xiaowei Dai; Hua Zhu; Qi Kong; Lan Huang; Yali Liu; Chunmei Ma; Jiamei Li; Chong Xiao; Ying Liu; et al. (Archives of Virology, 2009)

Characterization of Calcium Deposition and Shell Matrix Protein Secretion in Primary Mantle Tissue Culture from the Marine Pearl Oyster Pinctada fucata - Ningping Gong; Zhuojun Ma; Qing Li; Qi Li; Zhenguang Yan; Liping Xie; Rongqing Zhang (Marine Biotechnology, 2008)

Glucose-6-phosphate dehydrogenase plays a central role in modulating reduced glutathione levels in reed callus under salt stress - Xiaomin Wang; Yuanyuan Ma; Chenghong Huang; Qi Wan; Ning Li; Yurong Bi (Planta, 2008)

Membrane Tension Modulates the Effects of Apical Cholesterol on the Renal Epithelial Sodium Channel - Shi-Peng Wei; Xue-Qi Li; Chu-Fang Chou; You-You Liang; Ji-Bin Peng; David G. Warnock; He-Ping Ma (The Journal of Membrane Biology, 2007)

Hyperalgesia in response to traumatic occlusion and GFAP expression in rat parabranchial nucleus: modulation with fluorocitrate - Jinwu Chen; Jun Zhang; Yimin Zhao; Lintian Yuan; Xin Nie; Jianfu Li; Zhiwei Ma; Yongjie Zhang; Qi Wang; YongJin Chen; Yan Jin; Zhiren Rao (Cell and Tissue Research, 2007)

Phylogeography and Origin of Sheep Breeds in Northern China - Yue-Hui Ma; Shao-Qi Rao; Shen-Jin Lu; Guan-Yu Hou; Wei-Jun Guan; Hong-Bin Li; Xia Li; Qian-Jun Zhao; Jun Guo (Conservation Genetics, 2006)

Geology and geochemistry of the Changba SEDEX Pb-Zn deposit, Qinling orogenic belt, China - Guoliang Ma; Georges Beaudoin; Sijing Qi; Ying Li (Mineralium Deposita, 2004)

Forskolin up-regulates metastasis-related phenotypes and molecules via protein kinase B, but not PI-3K, in H7721 human hepato-carcinoma cell line - Shi-liang Wu; Jun Ma; Hui-ling Qi; Ying Zhang; Xia-ying Zhang; Hui-li Chen (Molecular and Cellular Biochemistry, 2003)